Hybrid capacitor comprising an electrochromic film and a polypyridyl organometallic complex as an electrolyte
By using metal ion-coordinated organic complexes and layered composites of carbon nanotubes in energy storage devices, an electrochromic-hybrid supercapacitor was constructed, solving the problem of combining high-performance EC materials and performance monitoring, and achieving efficient and stable electrochemical performance and long-life electrochromic effect.
Patent Information
- Application Number
- CN202180056158.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-06-09
- Filing Date
- 2021-06-09
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2041-06-09
AI Technical Summary
The prior art is difficult to prepare high-performance electrochromic (EC) materials and films containing these materials, and there are challenges in achieving the combination of energy production and performance monitoring in energy storage devices.
The integrated electrochromic-hybrid supercapacitor (EHSC) was constructed using metal ion-coordinated organic complexes as redox active materials, combining multi-walled carbon nanotubes and layered composites of conductive polymers. The device monitors the charge/discharge levels through an electrochromic metal organic layer and exhibits high energy density, power density and Coulomb efficiency at low potentials.
The color and energy stability is achieved in more than 1000 charge-discharge cycles and no significant temperature changes under operating conditions, demonstrating efficient electrochemical performance and long-lived electrochromic effect.
Smart Images

Figure CN116075914B_ABST
Abstract
Description
Field of the Invention
[0001] The present invention encompasses energy storage devices, such as capacitors, comprising metal ion organic complex components. Also provided are processes for preparing the devices and methods of using the same. The electrochromic properties of the devices of the present invention are used to indicate the charge / discharge level of the device. Background of the Invention
[0003] Electrochromic (EC) materials have the unique ability to change their optical transparency in response to the application of a voltage. This property is particularly useful in smart windows, electrochromic windows, smart mirrors, optical filters, frequency doubling devices, spatial light modulators, pulse shapers, displays, signs, plastic electronic devices, lenses, sensors, and many other devices.
[0004] An interesting class of EC materials is metal-coordinated organic complexes, in which metal ions are coordinated to organic molecules (ligands). In order to obtain films of high-performance EC materials, the material should be coated on a conductive substrate in a uniform manner. Film composition, film thickness, film density and film uniformity are properties that can greatly affect the EC performance of the material film. Such properties are important for a variety of applications. EC applications include electronic display systems such as color filter displays, monitors, TVs. Optoelectronic systems such as optical switches and optical / laser systems for optical communications (e.g., for machining, medical treatment, military / military / space), building materials products such as smart windows and filter windows, and products for the automotive industry, such as tintable reflective surfaces (e.g., car mirrors).
[0005] In view of the promising EC properties of metal-coordinated organic complexes, there is a need to find processes for preparing high-performance EC materials and membranes containing such complexes.
[0006] In addition, the growing demand for lightweight and miniaturization of traditional consumer electronic devices has accelerated the research and development of new functional devices. It is very desirable to replace conventional elements of silicon and metal-based circuits and devices with lightweight, high-performance molecular or polymer materials. Many functional organic materials have been developed to produce solar cells, organic field effect transistors, spatial light modulators, organic light emitting diodes and electrochromic windows. Despite the large number of available materials, it is still a challenging task to form a layered, stable architecture. For example, the interface contact between different components of the layered device may be affected by dewetting. It has been shown that the use of a covalently bound monolayer on the surface of a metal oxide electrode can enhance the performance and stability of an organic light emitting diode. Although the introduction of several new materials has led to real-world applications, the full potential of molecular-based devices and polymer-based devices has not yet been unlocked. This is partly because of issues and costs associated with upgrading, but also because stability and device integration hinder large-scale utilization. Combining different functions in organic devices and coupling such devices with conventional technologies is still in its infancy. In this regard, an important goal in energy devices is to combine energy production with other useful functions such as in-operation monitoring of device performance. In this regard, the use of photovoltaic devices with electrochromic materials and the integration of lithium batteries with solar cells have been reported. For example, electrochromic photovoltaic devices that can be used as self-powered smart glasses have been reported. Capacitive smart windows from electrochromic polymers have also been demonstrated. The use of "stand-alone" electrochromic materials is attractive for applications related to smart windows and smart mirrors. The combination of such coatings with electronic devices allows real-time readout of device operation by the naked eye. Therefore, there is a need for advanced electronic devices that can exploit the electrochromic properties of their components. SUMMARY OF THE INVENTION
[0008] In one embodiment, the present invention provides an energy storage device comprising an organic complex coordinated by a metal ion. The energy storage device of the present invention includes electrodes, capacitors, supercapacitors, hybrid supercapacitors and batteries. The organic complex coordinated by the metal ion is used as a redox active material and is disposed on at least one electrode in the device of the present invention. In addition and in some embodiments, the metal ion organic complex material is electrochromic. The color or absorption spectrum of the material changes according to the oxidation state / reduction state of the metal ion in the material. According to this aspect and in one embodiment, the charge / discharge level of the device can be monitored by the color / spectral changes of the metal organic material in the device. In addition, in order to obtain an efficient hybrid supercapacitor, a unique composite capacitor electrode has been developed, as described below in this article.
[0009] One embodiment of the present invention provides an integrated electrochromic-hybrid supercapacitor (EHSC). The operation (charge-discharge) of the device is indicated by an optical change. For example, in one embodiment, the device or a portion thereof is transparent when fully charged and colored when fully discharged. Thus, when the device is charged, a transition from colored to transparent is observed. The core of the device is an electrochromic metal organic layer, which serves as both a battery-type electrode and an optical indicator of charge. In this electrode, the color indicates the charge. The second electrode is a capacitor electrode. In one embodiment, the other electrode (capacitor electrode) is a layered composite of multi-walled carbon nanotubes (MWCNTs) and a conductive polymer (poly (3,4-ethylenedioxythiophene): polystyrene sulfonate, PEDOT:PSS). In some embodiments, the device of the present invention operates at a low potential (e.g., -0.6V to 2V), showing a high energy density and a high power density (e.g., ~2.2Wh·kg, respectively). -1 and ~2529W·kg -1 ), high Coulombic efficiency (e.g., 99%), short charging time (e.g., ~2s), and charge retention time (V 1 / 2 ). In one embodiment, stability in both color and energy over more than 1000 consecutive charge-discharge cycles is demonstrated for the device of the present invention. In some embodiments, there is no significant change in the temperature of the device under operating conditions. In one embodiment, the EHSC is wired with a conventional circuit board to be charged and then discharged and operate the diode.
[0010] In one embodiment, the present invention encompasses a method of depositing a multilayer electrochromic material onto a substrate to produce a multilayer EC assembly or EC film. The present invention also encompasses a multilayer electrochromic material. In addition, the present invention provides uses of electrochromic materials. In one embodiment, the present invention provides uses of the electrochromic material of the present invention in supercapacitors. The present invention also provides supercapacitors comprising the electrochromic material of the present invention. According to this aspect and in one embodiment, one electrode of the supercapacitor comprises the electrochromic material of the present invention. In one embodiment, the supercapacitor or a portion thereof changes color in response to a change in the charge / discharge state of the capacitor. According to this aspect and in one embodiment, the electrochromic material in the capacitor changes color in response to the degree of charge / discharge of the capacitor. In one embodiment, the charge / discharge of the supercapacitor involves oxidation / reduction of metal ions in the electrochromic material. In one embodiment, the change in oxidation state is accompanied by a change in the color of the material.
[0011] According to this aspect and in one embodiment, the device color is an indication of the charge level of the device.In some embodiments, the optical indication of charge level is a useful property of the device.
[0012] In one embodiment, the present invention provides a capacitor comprising:
[0013] A first electrode comprising an electrochromic film;
[0014] A second electrode;
[0015] an electrolyte in contact with the first electrode and the second electrode;
[0016] The electrochromic film comprises an organic complex coordinated by metal ions.
[0017] In one embodiment, the metal ion is an Fe ion. In one embodiment, the second electrode comprises carbon. In one embodiment, the carbon comprises carbon nanotubes. In one embodiment, the carbon nanotubes are multi-walled carbon nanotubes. In one embodiment, the second electrode comprises a polymer. In one embodiment, the polymer comprises PEDOT and PSS. In one embodiment, the electrode comprises a conductive material. In one embodiment, the electrode comprises a conductive oxide. In one embodiment, the conductive oxide is selected from ITO and FTO. In one embodiment, the conductive oxide is attached to silicon oxide. In one embodiment, silicon oxide is a substrate. In one embodiment, the capacitor is arranged in layers as follows:
[0018] a. The first substrate layer is attached to the first conductive oxide layer;
[0019] b. The first conductive oxide layer is attached to the metal ion coordinated organic complex layer;
[0020] c. The metal ion coordinated organic complex layer is in contact with the electrolyte layer;
[0021] d. The electrolyte layer is in contact with the carbon layer;
[0022] e. The carbon layer is in contact with the polymer layer;
[0023] f. The polymer layer is attached to the second conductive oxide layer;
[0024] g. The second conductive oxide layer is attached to the second substrate layer.
[0025] In one embodiment, the first substrate, the second substrate, or a combination thereof are selected from the group consisting of silicon dioxide and an organic polymer. In one embodiment, the first substrate, the second substrate, or a combination thereof comprise a material selected from glass, quartz, polyethylene terephthalate, PDMS, or any combination thereof. In one embodiment, the first substrate, the second substrate, or a combination thereof comprise aluminum oxide. In one embodiment, the capacitor is a supercapacitor.
[0026] In one embodiment, the capacitor is a hybrid capacitor, wherein the first electrode is a battery-type electrode, and the second electrode is a capacitive electrode. In one embodiment, the electrochromic film comprising an organic complex of metal ion coordination has a transmittance difference of 10% and higher between an oxidized state and a reduced state. In one embodiment, the electrochromic film comprising an organic complex of metal ion coordination has a transmittance difference of 64% and higher between an oxidized state and a reduced state. In one embodiment, the electrochromic film comprising an organic complex of metal ion coordination can maintain at least 40% of its maximum contrast ratio after 50 switching cycles between an oxidized state and a reduced state. In one embodiment, the electrochromic film comprising an organic complex of metal ion coordination can maintain at least 54% of its maximum contrast ratio after 1000 switching cycles between an oxidized state and a reduced state. In one embodiment, the capacitor comprises:
[0027] o a first electrode, the first electrode comprising:
[0028] a first substrate comprising a first conductive oxide surface; and
[0029] a membrane comprising a metal ion coordinated organic complex attached to the conductive oxide surface;
[0030] o a second electrode, the second electrode comprising:
[0031] a second substrate comprising a second conductive oxide surface; and
[0032] a layer comprising a capacitive material attached to the conductive oxide surface;
[0033] oElectrolytes, which are in contact with:
[0034] a film of an organic complex coordinated to the metal ion of the first electrode; and
[0035] • A layer of said capacitive material of said second electrode.
[0036] In one embodiment, the layer of the capacitor material includes a polymer or carbon or a combination thereof. In one embodiment, the layer of the capacitor material includes a polymer layer attached to a layer comprising carbon. In one embodiment, the first conductive oxide and the second conductive oxide each independently include electrical contacts capable of independently connecting the conductive oxide to an external device / circuit. In one embodiment, the metal ion coordinated organic complex includes a metal ion polypyridyl complex. In one embodiment, the electrochromic film comprising the metal ion coordinated organic complex includes from 2 layers to 80 layers of the metal ion coordinated organic complex, and the layers are connected to each other by a metal connector. In one embodiment, the metal ion in the metal connector is at least one metal ion selected from the group consisting of: Zn, Os, Ru, Fe, Pt, Pd, Ni, Ir, Rh, Co, Cu, Re, Tc, Mn, V, Nb, Ta, Hf, Zr, Cr, Mo, W, Ti, Sc, Ag, Au and Y. In one embodiment, the metal ion coordinated organic complex includes a polypyridyl complex represented by formula I as described below. In one embodiment, the metal ion coordinated organic complex comprises a polypyridyl complex represented by formula II as described herein below. In one embodiment, the following formula II represents an organic complex comprising Fe (iron) as a metal ion. However, in other embodiments of the present invention, the Fe ion in formula II is replaced by any other metal ion that can be coordinated by the ligand of formula II. All such metal ion organic complexes are included in embodiments of the present invention.
[0037] In one embodiment, the metal ion coordinated organic complex comprises a polypyridyl complex selected from 1DB, 2DB, 1SB, 2SB, 1TB, 2TB or any combination thereof, wherein M = Fe, and the pyridyl complex is represented by the corresponding formula illustrated herein below. In one embodiment, the metal ion coordinated organic complex comprises a mixture of the formulas described above, or a combination of these formulas with molecules containing different metal centers or ligands (according to Formula I and Formula II). In one embodiment, the polypyridyl complex is a mixture of polypyridyl complexes.
[0038] In one embodiment, the present invention provides a method of using a capacitor as described herein above, the method comprising:
[0039] · independently connecting the first electrode and the second electrode of the capacitor to a power source;
[0040] charging the capacitor using the power supply;
[0041] Connecting the capacitor to a load;
[0042] discharging the capacitor through the load;
[0043] The charging and the discharging are accompanied by a color change of the first electrode.
[0044] In one embodiment, the color change is an indication of the charge / discharge level of the capacitor. In one embodiment, the capacitor is in a bleached state when charged, and the capacitor is in a colored state when discharged. In one embodiment, the colored state is a more stable state of the molecule, and the bleached state requires an applied potential. In one embodiment, the color change is detected by an optical detector. In one embodiment, the color change is detected by the eyes. In one embodiment, the device or a system including the device also includes a light source for detecting the color change of the device or for the enhanced detection of the color change.
[0045] In one embodiment, the present invention provides an apparatus comprising:
[0046] o An electrochromic hybrid supercapacitor comprising:
[0047] A first electrode comprising an electrochromic film;
[0048] A second electrode;
[0049] an electrolyte in contact with the first electrode and the second electrode;
[0050] o a power source connected to the first electrode via a first electrical contact and to the second electrode via a second electrical contact;
[0051] o a load connected to the first electrode via a first electrical contact and to the second electrode via a second electrical contact.
[0052] In one embodiment, the electrical contacts include an on / off switch or other on / off mechanism to allow or prevent current from flowing through the contacts. In one embodiment, the device also includes an optical detector. In one embodiment, the device also includes a light source. In one embodiment, the device also includes a processor for receiving an input signal from the optical detector and providing a control signal to the device. In one embodiment, the control includes at least one of: starting charging, stopping charging, starting discharging, and stopping discharging.
[0053] One embodiment of the present invention encompasses a method for preparing an EC material (or EC film), the method comprising providing a substrate, applying at least one metal connector, applying at least one metal coordinated organic complex to form a layer, and repeating the applying steps to obtain a multilayer EC material.
[0054] In one embodiment, the metal organic complex comprises at least one functional group capable of binding to the metal linker. In one embodiment, the binding comprises a coordination bond between the functional group and the metal linker. In one embodiment, the metal coordinated organic complex is a polypyridyl complex.
[0055] In one embodiment, the applying step comprises a deposition technique such as roll-to-roll, spin coating, dip coating, spray coating, physical vapor deposition (PVD), chemical vapor deposition (CVD) or a combination thereof. In one embodiment, the polypyridyl complex comprises one isomer or more isomers of the same compound. In one embodiment, the polypyridyl complex comprises a mixture of isomers. In one embodiment, the polypyridyl complex comprises any mixture of isomers of the same compound. In one embodiment, the isomer is an enantiomer. In one embodiment, the polypyridyl complex comprises one or two enantiomers of the same compound. In one embodiment, the polypyridyl complex comprises a mixture of the one or two enantiomers. In one embodiment, the enantiomeric mixture is a racemic mixture. In one embodiment, the applying step comprises spin coating.
[0056] According to this aspect and in one embodiment, the present invention encompasses a method for preparing an EC material, the method comprising providing a substrate, applying at least one metal linker by spin coating, applying at least one polypyridyl complex by spin coating to form a layer, and repeating the application step to obtain a multilayer EC material. In one embodiment of the present invention, the spin coating step of applying the metal linker has a first spin rate and a first spin time. In one embodiment of the present invention, the first spin rate is from about 100 rpm to about 2000 rpm. In one embodiment of the present invention, the first spin time is from about 0.3 seconds to about 60 seconds. In one embodiment of the present invention, the spin coating step of applying the metal linker has a second spin rate and a second spin time. In one embodiment of the present invention, the second spin rate is from about 200 rpm to about 3000 rpm. In one embodiment of the present invention, the second spin time is in the range of 1 second to 120 seconds. In one embodiment, the spin rate and spin time for applying the metal ion organic complex are in the same range as the spin rate and spin time for applying the metal linker. In other embodiments, the spin rate and spin time for applying the metal ion organic complex are different from the range of the spin rate and spin time for applying the metal linker.
[0057] In one embodiment, after application of the metallic linker, or after application of the organic complex, or after application of the linker and after application of the complex, the layer is washed and / or dried.
[0058] In one embodiment of the invention, the washing solvent is selected from the group consisting of tetrahydrofuran THF, alcohols, ethers, esters, halogenated solvents, hydrocarbons and ketones. In one embodiment of the invention, the two application steps are repeated to obtain from about 1 layer to about 80 layers.
[0059] In one embodiment of the present invention, the substrate is selected from the group consisting of: ITO-coated polyethylene terephthalate, ITO-coated glass, and FTO-coated glass. In one embodiment of the present invention, the metal link is selected from the group consisting of: Zn, Os, Ru, Fe, Pt, Pd, Ni, Ir, Rh, Co, Cu, Re, Tc, Mn, V, Nb, Ta, Hf, Zr, Cr, Mo, W, Ti, Sc, Ag, Au, and Y.
[0060] In one embodiment of the present invention, the polypyridyl complex is represented by Formula I:
[0061]
[0062] in
[0063] M is a transition metal selected from Mn, Fe, Co, Ni, Cu, Zn, Ti, C, Cr, Rh, Ru, Os or Ir;
[0064] n is the formal oxidation state of the transition metal, where n is 0-6;
[0065] X is a counterion;
[0066] m is a number ranging from 0 to 6;
[0067] R1 to R 18 Each is independently selected from H, halogen, -OH, -N3, -NO2, -CN, -N(R 20 )2.-CON(R 20 2. -COOR 20 、-SR 20 , -SO3H, -CH=CH-pyridyl, -(C1-C 10 )alkyl, -(C2-C 10 )alkenyl, -(C2-C 10 )alkynyl, -(C1-C 10 ) alkoxy, cycloalkyl, heterocycloalkyl, aryl, heteroaryl, protected carboxyl or protected amino, wherein (C1-C 10 )alkyl, (C2-C 10 )alkenyl, (C2-C 10 ) alkynyl, cycloalkyl, heterocycloalkyl, aryl or heteroaryl may be optionally substituted with halogen, -OR 20 、-COR20 、-COOR 20 、-OCOOR 20 、-OCON(R 20 )2, -(C1-C8)alkylene-COOR 20 、-CN、-N(R 20 )2, -NO2, -SR 20 , -(C1-C8)alkyl, -O-(C1-C8)alkyl, -CON(R 20 )2 or -SO3H substituted;
[0068] A1 to A6 are each independently 19 a group of formula III, i.e. a pyridine or pyridine derivative moiety, or a group of formula IV, i.e. a pyrimidine or pyrimidine derivative moiety, attached to the ring structure of the complex of general formula I,
[0069]
[0070] R 19 Each independently selected from a covalent bond, H2C-CH2, HC=CH, C≡C, N=N, HC=N, N=CH, H2C-NH, HN-CH2-COO-, -CONH-, -CON(OH)-, -NR 20 -,-Si(R 20 )2-, alkylene, phenylene, biphenylene, optionally interrupted by one or more heteroatoms selected from O, S or N, a peptide moiety consisting of 3 to 5 amino acid residues,
[0071] R x and R y Each is independently selected from H, halogen, -OH, -N3, -NO2, -CN, -N(R 20 )2.-CON(R 20 2. -COOR 20 、-SR 20 , -SO3H, -CH=CH-pyridyl, -(C1-C 10 )alkyl, -(C2-C 10 )alkenyl, -(C2-C 10 )alkynyl, -(C1-C 10 ) alkoxy, cycloalkyl, heterocycloalkyl, aryl, heteroaryl, protected carboxyl or protected amino, wherein (C1-C 10 )alkyl, (C2-C 10 )alkenyl, (C2-C 10 ) alkynyl, cycloalkyl, heterocycloalkyl, aryl or heteroaryl may be optionally substituted with halogen, -OR 20 、-COR20 、-COOR 20 、-OCOOR 20 、-OCON(R 20 )2, -(C1-C8)alkylene-COOR 20 、-CN、-N(R 20 )2, -NO2, -SR 20 , -(C1-C8)alkyl, -O-(C1-C8)alkyl, -CON(R 20 )2 or -SO3H; and
[0072] R 20 Each is independently H, (C1-C6) alkyl or aryl.
[0073] In another embodiment of the present invention, the polypyridyl complex is represented by Formula II (wherein M = Fe as an example):
[0074]
[0075] in
[0076] n is the formal oxidation state of Fe, where n is 0-6;
[0077] X is a counterion;
[0078] m is a number ranging from 0 to 6;
[0079] R1 to R 18 Each is independently selected from H, halogen, -OH, -N3, -NO2, -CN, -N(R 20 )2.-CON(R 20 2. -COOR 20 、-SR 20 , -SO3H, -CH=CH-pyridyl, -(C1-C 10 )alkyl, -(C2-C 10 )alkenyl, -(C2-C 10 )alkynyl, -(C1-C 10 ) alkoxy, cycloalkyl, heterocycloalkyl, aryl, heteroaryl, protected carboxyl or protected amino, wherein (C1-C 10 )alkyl, (C2-C 10 )alkenyl, (C2-C 10 ) alkynyl, cycloalkyl, heterocycloalkyl, aryl or heteroaryl may be optionally substituted with halogen, -OR 20 、-COR 20 、-COOR 20 、-OCOOR 20 、-OCON(R 20)2, -(C1-C8)alkylene-COOR 20 、-CN、-N(R 20 )2, -NO2, -SR 20 , -(C1-C8)alkyl, -O-(C1-C8)alkyl, -CON(R 20 )2 or -SO3H substituted;
[0080] A1, A3 and A5 are each independently 19 a group of formula III, i.e. a pyridine or pyridine derivative moiety, or a group of formula IV, i.e. a pyrimidine or pyrimidine derivative moiety, attached to the ring structure of the complex of general formula II,
[0081]
[0082] R 19 Each independently selected from a covalent bond, H2C-CH2, cis / trans HC=CH, C≡C, N=N, HC=N, N=CH, H2C-NH, HN-CH2-COO-, -CONH-, -CON(OH)-, -NR 20 -,-Si(R 20 )2-, alkylene, phenylene, biphenylene, optionally interrupted by one or more heteroatoms selected from O, S or N, a peptide moiety consisting of 3 to 5 amino acid residues,
[0083] R x and R y Each is independently selected from H, halogen, -OH, -N3, -NO2, -CN, -N(R 20 )2.-CON(R 20 2. -COOR 20 、-SR 20 , -SO3H, -CH=CH-pyridyl, -(C1-C 10 )alkyl, -(C2-C 10 )alkenyl, -(C2-C 10 )alkynyl, -(C1-C 10 ) alkoxy, cycloalkyl, heterocycloalkyl, aryl, heteroaryl, protected carboxyl or protected amino, wherein (C1-C 10 )alkyl, (C2-C 10 )alkenyl, (C2-C 10 ) alkynyl, cycloalkyl, heterocycloalkyl, aryl or heteroaryl may be optionally substituted with halogen, -OR 20 、-COR 20 、-COOR 20 、-OCOOR 20 、-OCON(R20 )2, -(C1-C8)alkylene-COOR 20 、-CN、-N(R 20 )2, -NO2, -SR 20 , -(C1-C8)alkyl, -O-(C1-C8)alkyl, -CON(R 20 )2 or -SO3H substituted;
[0084] B1 to B3 are each independently selected from H, halogen, -OH, -N3, -NO2, -CN, -N(R 20 )2.-CON(R 20 2. -COOR 20 、-SR 20 , -SO3H, -CH=CH-pyridyl, -(C1-C 10 )alkyl, -(C2-C 10 )alkenyl, -(C2-C 10 )alkynyl, -(C1-C 10 ) alkoxy, cycloalkyl, heterocycloalkyl, aryl, heteroaryl, protected carboxyl or protected amino, wherein (C1-C 10 )alkyl, (C2-C 10 )alkenyl, (C2-C 10 ) alkynyl, cycloalkyl, heterocycloalkyl, aryl or heteroaryl may be optionally substituted with halogen, -OR 20 、-COR 20 、-COOR 20 、-OCOOR 20 、-OCON(R 20 )2, -(C1-C8)alkylene-COOR 20 、-CN、-N(R 20 )2, -NO2, -SR 20 , -(C1-C8)alkyl, -O-(C1-C8)alkyl, -CON(R 20 )2 or -SO3H; and
[0085] R 20 Each is independently H, (C1-C6) alkyl or aryl.
[0086] According to this aspect and in one embodiment, in Formula II represented herein above, instead of M=Fe, M is a transition metal selected from Mn, Fe, Co, Ni, Cu, Zn, Ti, C, Cr, Rh, Ru, Os or Ir.
[0087] In yet another embodiment of the present invention, the pyridyl complex is represented by Formula 1 or Formula 2, having a double bond (1DB / 2DB), a single bond (1SB / 2SB) and a triple bond (1TB / 2TB) as shown below:
[0088]
[0089]
[0090] In the embodiments shown above, the charge on the counterion is (X 1- In other embodiments, other counterions with higher negative charges, such as X 2- , X 3- , X 4- .
[0091] One embodiment of the invention encompasses a substrate selected from the group consisting of: ITO coated polyethylene terephthalate or FTO coated polyethylene terephthalate, ITO coated glass or quartz, and FTO coated glass or quartz. One embodiment of the invention encompasses an EC material prepared by the method of the invention, the EC material having a transmittance difference between an oxidized state and a reduced state of 10% and higher. In one embodiment, the EC material prepared by the method is capable of maintaining at least 40% of its maximum contrast ratio after 50 switching cycles.
[0092] One embodiment of the present invention encompasses a method for preparing an EC material, the method comprising providing a substrate, applying at least one metal linker by spin coating, applying at least one polypyridyl complex by spin coating to form a layer, and repeating the applying steps to obtain a multilayer EC material, wherein the step of applying the metal linker has a first rotation rate, a second rotation rate, a first rotation time, and a second rotation time. In another embodiment, the step of applying the polypyridyl complex has a first rotation rate, a second rotation rate, a first rotation time, and a second rotation time. In one embodiment, the metal linker is applied as a metal complex. According to this aspect and in one embodiment, the metal linker is present as a metal ion in a metal complex (e.g., PdCl2(PhCN)2). The metal complex comprises a metal ion and an organic ligand, an inorganic ligand, or a combination thereof. The metal complex is a coordination complex according to this embodiment. In some embodiments, such a metal complex is referred to as a metal linker, a metal linker complex, or a metal linker coordination complex.
[0093] In one embodiment, the metal linker is a mixture of metal linkers. In one embodiment, the polypyridyl complex is a mixture of polypyridyl complexes. In one embodiment, the step of washing the layer is performed after applying the metal linker, after applying the metal ion coordinated organic complex, or after both steps. In one embodiment, the step of drying the layer is performed after applying the metal linker, after applying the metal ion coordinated organic complex, or after both steps. In one embodiment, the step of washing the material or the step of drying the material or both the washing step and the drying step are performed only after all repeated application steps to obtain the multilayer EC material are performed. In some embodiments, the washing step is not performed during or after the preparation of the EC material. In one embodiment, the drying step is not actively performed during or after the preparation of the EC material.
[0094] In one embodiment, in the method of the present invention, the step of applying at least one metal linker comprises applying the metal linker from a solution comprising the linker, and wherein the step of applying at least one polypyridyl complex comprises applying the polypyridyl complex from a solution comprising the polypyridyl complex, and wherein the solution comprises a solvent selected from the group consisting of THF, alcohols, ethers, esters, halogenated solvents, hydrocarbons, ketones, or mixtures thereof. In one embodiment, the concentration of the linker in the solution and the concentration of the polypyridyl complex in the solution are in the range between 0.1 mM and 10 mM. In one embodiment, the EC material prepared by the method of the present invention has a transmittance difference of 10% and above between the oxidized state and the reduced state. In one embodiment, the EC material prepared by the method of the present invention has a transmittance difference of 25% and above between the oxidized state and the reduced state. In one embodiment, the EC material prepared by the method of the present invention has a transmittance difference of 64% and above between the oxidized state and the reduced state. In one embodiment, the EC material prepared by the method of the present invention is capable of maintaining at least 40% of its maximum contrast ratio after 50 switching cycles between the oxidized state and the reduced state. In one embodiment, the EC material prepared by the method of the present invention is capable of maintaining at least 54% of its maximum contrast ratio after 1000 switching cycles between the oxidized state and the reduced state. In one embodiment, the EC material prepared by the method of the present invention is capable of maintaining at least 90% of its maximum contrast ratio after 1000 switching cycles between the oxidized state and the reduced state. In one embodiment, the metal linker is applied as a metal complex.
[0095] In one embodiment, the present invention provides a catalyst. In one embodiment, the present invention provides a catalyst for water decomposition. In one embodiment, the beginning of water decomposition can be monitored by a color change of at least a portion of the device. In one embodiment, the color change is caused by a change in the redox state of ions in the device. In one embodiment, the catalyst is used to convert water into H2 and O2. In one embodiment, the catalyst includes a multilayer comprising catalyst ions. In one embodiment, the catalyst ions are metal ions. In one embodiment, the metal ions are Pd ions. In one embodiment, the multilayer used as a catalyst for water decomposition reaction includes an electrochromic entity. In another embodiment, the multilayer used as a catalyst for water decomposition reaction does not include an electrochromic entity. The embodiments described herein below with respect to metal organic multilayers can be applied to embodiments of catalysts comprising such multilayers or similar multilayers as described above herein.
[0096] In one embodiment, the present invention provides a data storage device. In one embodiment, the data storage device includes at least one redox center. In one embodiment, each redox center provides at least two states according to its oxidation state. In one embodiment, the charge required to achieve each state using electrochemical means can be calculated. In one embodiment, each state is also characterized by a specific color. According to this aspect and in one embodiment, each state has a different color and requires a different amount of charge to be set. According to this aspect and in one embodiment, the data storage device can be set to a specific state by electrochemical means (e.g., by applying a voltage to the multilayer), and the state can be evaluated or read using charge calculation (electrochemically) or using optical detection. In one embodiment, when more than one redox center is included in the device, so that two centers are different in their state and / or in their color and / or in the metal ion used, the color of the device can be a combination of the colors of each redox center. Therefore, in one embodiment, two different redox centers each having two redox states can result in a device comprising a total of three different states (e.g., 2 centers are reduced, 2 centers are oxidized, and 1 center is oxidized, while another center is reduced). Each overall device state is characterized by a different color and can be achieved using a specific amount of charge. In some embodiments, the device is based on an organic multilayer comprising metal ions, wherein at least a portion of the metal ions in the multilayer are capable of assuming more than one oxidation state. In some embodiments, the data storage device described herein is referred to as a memory device. The embodiments described herein below with respect to metal-organic multilayers may be applicable to embodiments of data storage devices / memory devices comprising such multilayers or similar multilayers as described herein above. BRIEF DESCRIPTION OF THE DRAWINGS
[0098] This patent or application file contains at least one drawing executed in color. Copies of this patent or patent application publication with color drawing(s) will be provided by the Office upon request and payment of the necessary fee.
[0099] The subject matter which is regarded as the invention is particularly pointed out and distinctly claimed in the concluding portion of the specification. Figure 1 The invention, both as to its organization and method of operation, together with objects, features and advantages thereof, may be best understood by reference to the following detailed description when read in conjunction with the accompanying drawings:
[0100] Figure 1 are the transmission spectra of a bare ITO / glass (green, less wavy) substrate and a bare FTO / glass (blue, more wavy) substrate.
[0101] Figure 2A-2B yes( Figure 2A ) Bare FTO / glass substrate and ( Figure 2B ) SEM image of bare ITO / glass substrate.
[0102] Figure 3 Molecular structures of polypyridyl complexes (1DB M=Fe) and (2DB M=Fe) are shown.
[0103] Figure 4 A schematic diagram of one embodiment of film formation is shown. The film was formed by alternately depositing the PdCl2 linker and the compound 1DB M=Fe or 2DB M=F using spin coating, layer-by-layer deposition.
[0104] Figure 5A-Figure 5B Shown is film growth on ITO / glass substrate. Figure 5A is a graph of the optical absorption spectra after each deposition cycle. The baseline is the absorbance of the bare ITO substrate. Figure 5B The intensity of the absorption band at λ = 578 nm (R 2 =0.998).
[0105] Figure 6 The graph shows the cyclic voltammetry results of an EC assembly made of compound 1DB M=Fe as EC material and PdCl2 as a linker on an ITO / glass substrate. The material cycled for 2000 redox cycles with a slight drop in current of <2%. The CV was recorded in 0.1M TBAPF6 / ACN at a scan rate of 0.1V / sec.
[0106] Figure 7The spectroelectrochemical behavior of an EC assembly made of compound 1DB M=Fe as EC material and PdCl2 as linker on an ITO / glass substrate is shown, as well as the difference in transmittance values of the assembly between the oxidized and reduced states at λ=578 nm.
[0107] Figure 8A-8B The different colors of EC assemblies made of compounds 1DB M═Fe or 2DB M═Fe as EC material and PdCl 2 as linker (18 deposition steps) on FTO / glass substrate are shown. Fig. 8A The purple color of the EC assembly made of compound 1DB M=Fe on a 6cm×6cm FTO / glass substrate film area is shown, while Figure 8B The black color of an EC assembly made of compound 2DB M=Fe on a 4 cm x 4 cm FTO / glass substrate film area is shown.
[0108] Figure 9A-9D The diagram shows film growth on FTO / glass substrate. Fig. 9A and Fig. 9C Shown are the optical absorption spectra of EC assemblies made of compound 1DB M═Fe and compound 2DB M═Fe, respectively, on FTO / glass substrates after every three deposition cycles using PdCl 2 as a linker. Fig. 9B and Fig.9D The intensities of the absorption bands of the EC component of compound 1DB M=Fe at λ=578 nm (R2=0.999) and the EC component of compound 2DB M=Fe at λ=598 nm (R2=0.999) are shown respectively.
[0109] Figure 10A-10B The surface of an EC assembly made of compound 1DB M═Fe as EC material and PdCl 2 as linker on a FTO / glass substrate is shown, analyzed using optical microscopy and atomic force microscopy (AFM). Fig. 10A is the surface observed by optical microscopy. Fig. 10B is the surface observed by AFM.
[0110] Figures 11A-11C The surface and structure of the EC assembly made of compound 1DB M=Fe as EC material and PdCl2 as a linker on FTO / glass substrate are shown; Fig.11A is a cross-sectional SEM image of a component, which was performed using a focused ion beam (FIB) and shows different cross sections of the component; Fig. 11B is a scheme showing different cross-sections of the component; and Fig. 11C is a SEM image of the surface of the component.
[0111] Fig.12 Photographs of films of different sizes [Compound 1DB M=Fe, 18 deposition steps, substrate is FTO / glass] are shown.
[0112] Fig.13 The thermal and photostability of EC assemblies made of compound 1DB M=Fe as EC material and PdCl2 as linker on FTO / glass substrates are illustrated, an initial slight decrease in absorbance was observed for both samples followed by stabilization over time.
[0113] Fig.14 Shown are cyclic voltammograms of [Compound 1DB M=Fe, 18 deposition steps, substrate is FTO / glass]. CVs were recorded in 0.1 M TBAPF6 / ACN at a scan rate of 0.1 V / sec.
[0114] Figure 15A-15B The electrochemical stability of [compound 1DB M=Fe, 18 deposition steps, substrate is FTO / glass] is shown; ( Fig.15A ) Cyclic voltammograms up to 1500 switching cycles. Fig. 15B )As in ( Fig.15A ) relative to the number of switching cycles.
[0115] Fig.16 Illustration of the electrochemical switching of an EC assembly made of compound 1DB M=Fe as EC material and PdCl2 as a linker (18 deposition cycles) on FTO / glass substrate; optical absorption spectra corresponding to the oxidized (grey) and reduced (purple) states of the assembly. The electrochemical switching was performed by applying a double potential step in the potential window of 0.2 V-1.8 V. Inset: Photographs of the colored (upper) and decolorized (lower) states of a 4 cm×4 cm film.
[0116] Fig.17 Spectroelectrochemical behavior showing the difference in transmittance values at λ=578 nm between oxidized and reduced states of EC assemblies made of compound 1DB M=Fe as EC material and PdCl2 as linker (18 deposition cycles) on FTO / glass substrates.
[0117] Figure 18A-18B The difference in transmittance of EC assemblies made of compound 1DB M=Fe as EC material and PdCl2 as connector on FTO / glass substrate is shown. Fig.18A The contrast ratio at different switching times is shown. The contrast ratio is defined as the difference in transmittance values at a certain wavelength between the oxidized and reduced states of the film. Fig.18BPlotted is the contrast ratio versus switching time. The switching time is defined as the time the system is kept at a certain potential value. All experiments were performed at room temperature in 0.1 M TBAPF6 / ACN.
[0118] Fig.19 The diagram shows a 2×2 cm 2 Switching efficiency of EC assembly made of compound 1DB M=Fe as EC material and PdCl2 as linker on FTO / glass substrate. Switching efficiency is defined as the time taken for the system to achieve 95% of its final optical change. In the system discussed, in the case of oxidation, 95% of the optical change is achieved after 1.92s, while in the case of reduction, 1.48s are required for 95% of the change to occur.
[0119] Figure 20A-20C Electrochemical switching of an EC assembly made of compound 1DB M=Fe as EC material and PdCl2 as a linker on FTO / glass substrate at different scan rates is shown. Electrochemical switching refers to the switching of a material between oxidized and reduced states due to the application of an external potential. Fig. 20A Shown are cyclic voltammograms taken at scan rates of 0.01 V / sec to 1.0 V / sec. Fig. 20B An exponential dependence of the peak current on the scan rate is shown (R2 = 0.99). Fig. 20C The linear dependence of the peak current on the square root of the scan rate is shown (R2 = 0.99).
[0120] Figure 21A-21B The diagram shows a 2×2 cm 2 Electrochemical relevance of EC assemblies made of compound 1DB M=Fe as EC material and PdCl2 as connector on FTO / glass substrate. Fig.21A Cyclic voltammograms of assemblies consisting of 1, 3, 6, 9, 12, 15 and 18 deposition cycles are shown. Fig. 21B The dependence of the maximum current on the number of deposition cycles is shown.
[0121] Figure 22A-22B The diagram shows a 2×2 cm 2 Spectroelectrochemical behavior of the EC assembly made of compound 1DB M=Fe as EC material and PdCl2 as connector on FTO / glass substrate. Fig.22A The contrast ratio (R) of assemblies consisting of 1, 3, 6, 9, 12, 15, and 18 deposition cycles is shown. 2 =0.96). Fig. 22B The contrast ratio is plotted against the number of deposition cycles (R 2 =0.92).
[0122] Figure 23A-23B The graph shows the spectroelectrochemical behavior of [compound 1DB M=Fe│1-18│FTO / glass]. Film size: 2cm×2cm. ( Fig.23A ) Charge difference of films consisting of 1, 3, 6, 9, 12, 15, and 18 deposition cycles. (R 2 =0.96). Fig. 23B ) Coloring efficiency relative to the number of deposition cycles (R 2 =0.92). All experiments were performed at room temperature in 0.1M TBAPF6 / ACN.
[0123] Fig.24 Cyclic voltammograms of [Compound 2DB M=Fe|18|FTO / Glass] are shown. CVs were recorded in 0.1 M TBAPF6 / ACN at a scan rate of 0.1 V / sec.
[0124] Fig.25 2×2 cm made of compound 2DB M=Fe as EC material and PdCl2 as linker on FTO / glass 2 Photographs of the colored and decolorized states of the Ec component, where electrochemical switching was performed by applying double potential steps in the potential window of 0.2 V–1.8 V.
[0125] Figure 26A-26B The spectroelectrochemical behavior of an EC assembly made of compound 2DB M=Fe as EC material and PdCl2 as linker on FTO / glass substrate is shown. Fig.26A The difference in transmittance values between the oxidized and reduced states of the film at λ = 598 nm is illustrated. Fig.26B The graph shows the stability of the contrast ratio when the assembly is cycled for 1000 switching cycles with a switching time of 2 seconds.
[0126] Figure 27A-27F The film growth of an EC assembly made from a mixture of compounds 1DB M=Fe and 2DB M=Fe is shown. Fig.27A The growth behavior of an assembly comprising an equimolar mixture of compound 1 DB M=Fe and compound 2 DB M=Fe on FTO / glass is illustrated. Each deposition cycle was performed using a solution comprising the two compounds in a 1:1 ratio. Fig.27B The growth behavior of an assembly comprising a block of compound 1 DB M=Fe followed by a block of compound 2 DB M=Fe on FTO / glass (9 deposition cycles each) is illustrated. Fig.27CThe growth behavior of an assembly comprising a block of compound 1 DB M=Fe followed by a block of compound 2 DB M=Fe on FTO / glass (13:5 deposition cycles respectively) is illustrated. The baseline (black) is the absorbance of the bare FTO substrate. Fig.27D The diagram shows Fig.27A The intensity of the absorption band at λ = 585 nm obtained for the components presented in 2 =0.99). Fig.27E The diagram shows Fig.27B The intensity of the absorption band at λ = 581 nm obtained for the components presented in 2 =0.99). Fig.27F The diagram shows Fig.27C The intensity of the absorption band at λ = 584 nm obtained for the components presented in 2 =0.99).
[0127] Figure 28A-28C Electrochemical switching of an EC assembly made from a mixture of compounds 1DB M=Fe and 2DB M=Fe is illustrated. Fig.28A The optical absorption spectrum of an assembly comprising an equimolar mixture of EC materials made of compound 1 DB M=Fe and compound 2 DB M=Fe (18 deposition cycles) on FTO / glass is shown. Fig.28B Shown are optical absorption spectra of an assembly comprising a block of compound 1 DB M=Fe followed by a block of compound 2 DB M=Fe on FTO / glass (9 deposition cycles for each compound). Fig.28C Plotted are the optical absorbance of an assembly comprising a bulk of compound 1 DB M=Fe on FTO / glass (13 deposition cycles) followed by a bulk of compound 2 DB M=Fe (5 deposition cycles).
[0128] Figure 29A-29F The spectroelectrochemical behavior of an EC assembly made from a mixture of compounds 1DB M=Fe and 2DB M=Fe is shown. Fig.29A and Fig.29D Shown are cyclic voltammograms and SEC of an EC assembly comprising an equimolar mixture of Compound 1DB M=Fe and Compound 2DB M=Fe on FTO / glass (18 deposition cycles). Fig.29B and Fig.29E Shown are cyclic voltammograms and SEC of an EC assembly comprising bulk of compound 1 DB M=Fe (9 deposition cycles) followed by bulk of compound 2 DB M=Fe (9 deposition cycles) on FTO / glass. Fig.29C and Fig.29FShown are cyclic voltammograms and SEC of an EC assembly comprising bulk of compound 1DB M═Fe on FTO / glass (13 deposition cycles) followed by bulk of compound 2DB M═Fe (5 deposition cycles).
[0129] Figures 30A-30D The color of the assembly after 18 deposition cycles for a combination comprising compounds 1DB M=Fe and 2DB M=Fe using PdCl2 as a linker is shown. Fig. 30A EC material made of bulk of compound 1DB M═Fe (9 deposition cycles) followed by bulk of compound 2DB M═Fe (9 deposition cycles) on FTO / glass. Fig. 30B It is an EC assembly comprising an equimolar mixture of compound 1DB M=Fe and compound 2DB M=Fe on FTO / glass. Fig. 30C is an EC assembly comprising compound 2DB M=Fe on FTO / glass (18 deposition cycles). Fig.30D is an EC assembly comprising compound 1DB M=Fe on FTO / glass (18 deposition cycles).
[0130] Figure 31A-Figure 31B The growth behavior of an EC assembly comprising compound 1DB M═Fe on ITO / PET is shown. Fig.31A Optical absorption spectra of the components obtained every three deposition cycles are shown. The black baseline is the absorbance of the ITO / PET substrate before deposition. Fig.31B The absorption intensity (R 2 =0.998).
[0131] Fig.32 Shown are the results of CV measurements of an EC assembly comprising compound 1DB M═Fe on a flexible ITO / PET substrate, recorded in 0.1 M TBAPF6 / ACN at a scan rate of 0.1 V / sec.
[0132] Figure 33A-Figure 33B The electrochemical stability of the EC assembly comprising compound 1DB M═Fe on an ITO / PET substrate is shown. Fig.33A Cyclic voltammograms covering up to 1500 switching cycles are shown. Fig.33B Plotted are the maximum current versus the number of switching cycles, where CVs were recorded at a scan rate of 0.1 V / sec in 0.1 M TBAPF6 / ACN.
[0133] Fig.34 Schematic diagram of an electrochromic device composed of the material of the present invention, wherein the substrate is a transparent conductive electrode and the spacer is 3M 9088 double-sided tape.
[0134] Fig.35 Electrochemical switching of an electrochromic device is illustrated, where the working electrode is an EC assembly comprising compound 1DB M=Fe (18 deposition cycles) deposited on FTO / glass, and the counter electrode is a bare FTO substrate. In the optical absorption spectrum, the colorless oxidized state is represented in gray (lower curve), and the purple reduced state is represented in purple (peak curve).
[0135] Figure 36A-36B The spectroelectrochemical behavior of a 0.5 cm x 1 cm electrochromic device including an EC assembly of compound 1DB M=Fe deposited on FTO / glass and bare FTO / glass as a counter electrode is shown. Fig.36A The difference in transmittance values of the device between the oxidized and reduced states at λ = 571 nm is illustrated. Fig.36B The contrast ratio is shown when the device is cycled for 100 switching cycles with a switching time of 4 seconds.
[0136] Fig.37 The decay rate of a rigid solid-state EC device based on an EC assembly comprising compound 1DB M=Fe is shown. The kinetics of the redox process was tested by applying a suitable potential that resulted in decolorization of the device, followed by turning off the potential and disconnecting the circuit while monitoring the transmittance value of the device.
[0137] Figure 38A-Figure 38B Photograph of an electrochromic device where the working electrode is [Compound 1DB M=Fe|18|FTO / glass] and the counter electrode is a bare FTO substrate. ( Fig.38A )4cm×4cm device. ( Fig.38B )6cm×6cm device.
[0138] Figure 39A-Figure 39B The growth behavior of an assembly comprising an equimolar mixture of compound 1DB M=Fe and compound 2DB M=Fe on ITO / PET is illustrated. Fig.39A The optical absorption spectra after every three deposition cycles are shown, where the baseline (black) is the absorbance of the bare ITO / PET substrate; and Fig.39B The absorption band (R 2 =0.99).
[0139] Fig.40 The cyclic voltammograms of an assembly comprising an equimolar mixture of Compound 1DB M=Fe and Compound 2DB M=Fe on a 6 cm×2 cm ITO / PET substrate are shown. The orange curve indicates the CV of the assembly before any bending force is applied, and the green curve indicates the CV of the assembly when the assembly is kept bent with a radius of curvature of 2.5 cm.
[0140] Fig.41 The chronoamperometry (CA) of an assembly comprising an equimolar mixture of compound 1DB M=Fe and compound 2DB M=Fe on a 6 cm×1 cm ITO / PET substrate with a resistivity of 60 ohm / sq is shown. CA was recorded when the assembly was held in the following positions: (blue) upright (red) bent at a radius of curvature of 2.5 cm; (black) upright after being bent at a radius of curvature of 2.5 cm for 10 s.
[0141] Fig.42 Photographs of the colored and decolorized states of an assembly comprising an equimolar mixture of compound 1DB M=Fe and compound 2DB M=Fe on a 6 cm×1 cm ITO / PET substrate, wherein the resistivity is 60 ohm / sq. The photographs were taken when the assembly was held in the following positions: upright (left) and bent with a curvature radius of 2.5 cm (right).
[0142] Fig.43 is a schematic diagram of a flexible electrochromic device, where the substrate is a transparent conductive electrode and the spacer is 3M9088 double-sided tape.
[0143] Fig.44 The electrochemical behavior of a 6 cm x 1 cm electrochromic device is shown, where the working electrode is an assembly comprising an equimolar mixture of compound 1 DB M = Fe and compound 2 DB M = Fe on ITO / PET 60 ohm / sq (after 18 deposition cycles), and the counter electrode is bare 60 ohm / sq ITO / PET. CA was recorded when the assembly was held in the following positions: (blue) upright (red) bent with a radius of curvature of 2.5 cm; (black) upright after bending with a radius of curvature of 2.5 cm for 10 s.
[0144] Fig.45 Photographs of the colored state (left) and the decolorized state (right) of the flexible electrochromic device are shown, where the working electrode is an assembly comprising an equimolar mixture of compound 1DB M=Fe and compound 2DB M=Fe on ITO / PET 60ohm / sq (after 18 deposition cycles), and the counter electrode is bare 60ohm / sq ITO / PET.
[0145] Fig.46Photographs of the colored state (left) and the decolorized state (right) of a flexible electrochromic device are shown, where the working electrode is an assembly comprising an equimolar mixture of compound 1DB M=Fe and compound 2DB M=Fe on ITO / PET 60ohm / sq (after 18 deposition cycles), and the counter electrode is bare 60ohm / sq ITO / PET. The device undergoes switching when held bent.
[0146] Figure 47A-47B The crystal structures of the complexes 1DB M=Fe and 2DB M=Fe are shown. Fig.47A ) Crystal structure of the isomer of complex 1DB M=Fe. Left side: facial; right side: meridional. ( Fig.47B ) Crystal structure of the enantiomers of the complex 2DB M=Fe. Left: Λ; right: Δ. The crystal structure is shown in the ORTEP view using thermal ellipsoids set at the 50% probability level. Hydrogen atoms are omitted for clarity, black, carbon; blue, nitrogen; yellow, iron.
[0147] Fig.48 Molecular structures of polypyridyl complexes 1DB-2DB with various metal ions (Fe, Ru, and Os as shown) are shown.
[0148] Figure 49A-49B Color variety. ( Fig.49A ) A palette consisting of a combination of complexes (1DB M=Fe and 2DB M=Fe); and (1DB M=Fe and 1DB M=Ru), and (1DB M=Os) as well as assemblies of complexes 1DB-2DB, with different numbers of deposition cycles. Fig.49B ) is a color definition in the RGB color space with all its different components.
[0149] Figure 50A-Figure 50B Spectroelectrochemical (SEC) activity of different assemblies on FTO / glass in electrolyte solution. Fig.50A ) Optical absorption spectra corresponding to the sequential oxidation and reduction of assemblies based on the complexes 1DB M=Fe, 2DB M=Fe, (1DB M=Fe and 2DB M=Fe), 1DB M=Ru, (1DB M=Fe and 1DB M=Ru) and 1DB M=Os (from top to bottom). The bare FTO substrate was used as a baseline. Inset: Dependence of the contrast ratio on the switching time. ( Fig.50B) Top part: Photographs of the colored and decolorized states of the assembly. Bottom part: SEC at λ = 573 nm, 598 nm, 589 nm, 495 nm, 573 nm (purple trace) and 495 nm (orange trace) and 510 nm (from top to bottom). Switching was performed at double potential steps between 0.4 V - 1.6 V, 0.4 V - 1.8 V, 0.4 V - 2.0 V, 0.7 V - 1.7 V, 0.4 V - 1.8 V and 0.2 V - 1.4 V (from top to bottom).
[0150] Fig.51 Selective switching. Reduced (left) and oxidized (right) states of a patterned electrochromic surface of FTO / glass modified with complex 1DB M=Fe.
[0151] Fig.52 Open circuit stability. Each pulse was generated by applying 1.6 V (oxidation potential) on the complex 1DB M=Fe-modified FTO / glass surface.
[0152] Fig.53 Devices connected in parallel. Left: device in its reduced state, right: device in its oxidized state after experiencing the usual potential window for solid-state devices.
[0153] Figure 54A-Figure 54C Cyclic voltammograms of components made from compound 1DB M═Fe and compound 1DB M═Ru. Fig.54A ) mixed hierarchy. Fig.54B ) Block hierarchy when complex 1DB M=Fe is on top of complex 1DB M=Ru. Fig.54C ) Block hierarchy when complex 1DB M=Ru is on top of complex 1DB M=Fe.
[0154] Figure 55A-Figure 55C Cyclic voltammograms of components made from compound 2DB M═Fe and compound 1DB M═Os. Fig.55A ) mixed hierarchy. Fig.55B ) Block hierarchy when complex 1DB M=Os is on top of complex 2DB M=Fe. Fig.55C ) Block hierarchy when complex 2DB M=Fe is on top of complex 1DB M=Os.
[0155] Figure 56A-Figure 56DSchematic diagram of electrochromic hybrid supercapacitor (EHSC); materials, structure, and device operation. (A) Schematic diagram of building blocks used to construct electrodes; molecular structures of iron polypyridyl complex (top), PdCl2(PhCN)2, PEDOT:PSS, and MWCNT (bottom). (B) Composition of electrodes; composition of Fe-containing electrode, electrochromic cell element (top) and PPC-containing electrode, composite capacitive element (bottom); (C) Schematic diagram of the EHSC structure of electrochromic hybrid supercapacitor laminate: (i) [PPC|FTO / glass], as counter and reference electrodes, (ii) a piece of Whatman filter paper soaked in electrolyte (PC:ACN, 1:1 (v / v), 0.1 M LiClO4), placed in the middle of an insulating spacer (210-μm-thick double-sided tape frame), and (iii) [Fe|FTO / glass], as a working electrode. (D) Illustration of the operation of the electrochromic hybrid supercapacitor; the charge storage mechanism and the color of the EHSC during charging and discharging.
[0156] Figure 57A-Figure 57F Device electrochemical characterization and color-charge correlation. (A) Cyclic voltammograms (CVs; the second cycle of each CV is shown) of three different devices (2 cm×2 cm): (i) [glass / FTO|Fe||PPC|FTO / glass] (red trace for EHSC), (ii) [glass / FTO||Fe|FTO / glass] (purple trace—Fe complex), (iii) [glass / FTO||PPC|FTO / glass] (black trace—PPC) (scan rate = 0.1 Vs -1 ). (B) Representative galvanostatic charge-discharge (GCD) curves of EHSC at different currents. The total mass includes both PPC and electrochromic layer. (C, D) UV / Vis spectra and photographs at five different potentials for charge (C) and discharge (D) are shown. Scale bar is 2 mm. (E) At 0.25 A·g -1 (F) GCD profile of current density and in situ transmittance (λ = 573 nm). (F) In situ optical transmittance and charge as a function of time and potential.
[0157] Fig.58A - Figure 58 Energy and color stability performance of EHSC. (A) at 0.9 A·g -1 The cycling stability of the current density measured by GCD in the potential range of −0.4 V to 1.8 V. (B) The first and last 5 GCD cycles, and (C) the corresponding in situ transmittance change (λ max=573 nm) and a pulse width of 2 s. (D) Self-discharge of the EHSC followed by the change in potential (black trace) measured by CP, and the corresponding in situ transmittance change (λ max =573 nm, blue trace). The EHSC was charged to 1.4 V by applying 0.005 A for 20 seconds.
[0158] Figure 59A-Figure 59B Demonstration of the functionality of an EHSC. (A) Photographs of an EHSC device and circuit. (B) Photographs of an EHSC (i) before charging, (ii) during charging, (iii) during discharging, and (iv) at discharge.
[0159] Figure 60A-Figure 60F Components, fabrication process, and characterization of the capacitive electrode [PPC|FTO / glass]. (A) [PPC|FTO / glass] was formed by spin coating PEDOT:PSS on fluorine-doped tin oxide (FTO) on glass, followed by drop casting of a CHCl3 solution of MWCNTs and EP-PDI (1:1 w / w). EP-PDI was removed by washing with CHCl3 and the resulting film was dried at 120 °C in air. (B) SEM image of [PPC|FTO / glass] before washing with CHCl3. (C) SEM image of [PPC|FTO / glass] after removal of EP-PDI with CHCl3. (D) Cyclic voltammograms (CV) of [PPC|FTO / glass] at different scan rates. (E) Linear correlation between scan rate and specific capacitance (R 2 >0.99). (F) Representative CVs of (i) [PEDOT:PSS|FTO / glass] (lowest blue trace), (ii) [MWCNT|FTO / glass] (middle black trace), and (iii) [PPC|FTO / glass] (highest red trace). CVs were recorded at a scan rate of 0.1 V / s. [PPC|FTO / glass] (2 cm × 2 cm) (or i / ii) was used as the working electrode, Ag / Ag + was used as a reference electrode, a Pt wire was used as a counter electrode, and LiClO4 0.1 M in propylene carbonate:acetonitrile = 1:1, v / v was used as a supporting electrolyte.
[0160] Fig.61 Cyclic voltammograms (CV) of the first cycle (black trace), second cycle (red trace), and third cycle (blue trace) of EHSC. The measurements were performed at a scan rate of 0.1 V / s.
[0161] Fig.62The amount of charge stored in the EHSC is relative to the number of layers of the iron complex. The working electrode [Fe|FTO / glass] consisted of 1, 5, 10, 15, or 18 Fe complex layers. CVs were recorded at room temperature in the potential range of -0.4 V to 1.8 V with a scan rate of 0.1 V / s.
[0162] Fig.63 Ragone plot showing the performance of EHSC. Energy density and power density were calculated using Equation 1 and Equation 2, respectively. Each spot was generated using the same device and the same current density (0.2 A g -1 To 1.8A·g -1 The total mass includes both the PPC and the electrochromic layer.
[0163] (1)
[0164] (2)
[0165] where t1 and t2 are the start and end time of the discharge process (s), I is the constant current (A), V is the voltage (v), m is the mass of the active material (kg), and Δt is the discharge time.
[0166] Figure 64A-Figure 64B Constant current charge-discharge (GCD) curves of reference devices. (A) [Glass / FTO||PPC|FTO / Glass]. (B) [Glass / FTO||Fe|FTO / Glass]. CP was recorded at a current of 0.5 mA in the potential range of -0.6 V to 2 V and -2.0 V to 3.0 V, respectively. In this experiment, the current is constant and only its polarity changes. Each time the potential of the device reaches the highest or lowest potential (e.g. -0.6 V or 2 V), the polarity changes. The time it takes is variable and depends on the device.
[0167] Fig.65 At 0.9A·g -1 The current density and the coulombic efficiency of the EHSC measured by constant current charge-discharge (GCD) in the potential range of -0.4V to 1.8V (measured / limited potential range). The coulombic efficiency is calculated as follows:
[0168]
[0169] Fig.66 The temperature of the EHSC was monitored during the CP measurement with an infrared thermometer. The CP was recorded at a current of 0.5 mA in the potential range of -0.6 V to 2 V (measured potential range). The temperature is in °C.
[0170] Fig.67 A circuit diagram of two paths is shown. The charging path (top) of the EHSC includes: (1) the EHSC, (2) a 5V charging source that is stepped down to 1.8V via a 5kOhm trimpot resistor (the resistivity of the resistor can be changed as desired, e.g., to 1kOhm), and (3) current indication via a red LED connected in series with the charging portion of the circuit and illuminated by the charging current. Two LEDs (LED1 and LED2) are used to step down the voltage; the discharge path (bottom) of the EHSC includes (4) the input diode of the optocoupler that drives the gate of the phototransistor to the "on" state and (5) current indication via a yellow LED (LED3) connected in series with the phototransistor.
[0171] Fig.68 Depend on Fig.67 The diagram describes an electrical plate.
[0172] Fig. 69 Organic memory cell, building blocks, fabrication and states. A) 3-electrode electrochemical cell composed of OMC. B) Molecular components used to form nanoscale metal-organic assemblies. Positive charges of complexes and counterions omitted for clarity C) Layer-by-layer deposition steps using [PdCl2(PhCN)2] complex for bonding. D) Schematic diagram of OMC operation and states.
[0173] Fig.70 Energy dispersive x-ray spectroscopy (EDS) assisted transmission electron microscopy (TEM) of membrane cross sections (by focused ion beam FIB milling).
[0174] Fig.71 Electronic and optical properties of OMC. Top) Input OMC operating potential. Middle) Chrono current (CA) of random sequence of read and write operations. Bottom) At λ max = UV-vis absorbance monitoring at 570 nm while applying a random sequence at A.
[0175] Fig.72 Functional demonstration of OMC operation.
[0176] Figure 73 Operation and application. Fig.73A : Time over threshold (TOT) refers to the time it takes for CE to return to 1.6 V for each state. Fig.73B are the optical absorption spectra of states 0-3: 1.6 V (grey, state 0), 0.2 V (orange, state 1), -1.4 V (red, state 2), and -2.1 V (Bordeaux, state 3). Fig.73C 10 consecutive read-write cycles of states 0-3 in λ max = 500 monitored spectroelectrochemistry. Fig.73DThe CA measurements of the OMC operation represent the charge density at 1.6 V applied. Fig.73E is a table showing the reading and writing process.
[0177] Fig. 74 Charge trapping phenomenon in OMC. Fig.74A Cyclic voltammetry scan at 0.1 V / s; Fig.74B Transmittance (500nm) corresponds to Fig.74A The CV presented in the figure.
[0178] Figure 75 Photostability and electrical stability of OMC. Fig.75A Chronoamperometric measurements (CA) at double potential step: 0.2 V to 1.6 V for state 1. Fig.75B For state 2 it is -1.4V to 1.6V and Fig.75C : -2.1V to 1.6V for state 3. Fig.75D )、State 2( Fig.75E ) and state 3 ( Fig.75F ) in λ max = SEC measurement value at 500 nm.
[0179] Figure 76 Illustration of some building blocks ( Fig.76A ); forming multiple layers by automated spin coating ( Fig.76B ); electrochromism and water splitting in the corresponding voltage (V) range.
[0180] Figure 77: Fig.77A Electrochromism and water splitting at or above a specific voltage (V); Fig.77B In Fe 2+ / Fe 3+ Absorbance graph of a multilayer with iron ions in the state; Inset: Cyclic voltammogram showing the transition between the oxidized iron ion state and the reduced iron ion state; Fig.77C Transmittance (T%) versus switching cycle; Fig.77D Cyclic voltammograms showing the potential range for the onset of electrochromic change and water splitting; Fig.77E Tafel plot of potential (V) versus logJ (mA / cm 2 ); Fig.77F Current density J (mA / cm 2 ) relative to time (hours); Figure 77G XPS measurements of the multilayers before and after CPE, intensity versus binding energy showing the Fe 2+ , N and Pd 2+ The peak.
[0181] Fig.78 Scheme showing the onset of water decomposition accompanied by a color change of the multilayer structure.
[0182] Figure 79 Fig.79A ) Cyclic voltammograms of MA1 at different scan rates (0.1V / s-0.9V / s). Fig.79B ) Correlation between peak current and scan rate during oxidation (upper) and reduction (lower) (for all fitted R 2 >0.99). A 0.1M LiClO4 aqueous solution was used as the supporting electrolyte.
[0183] Fig.80 In an aqueous electrolyte solution (0.1 M LiClO4) on FTO / glass (active substrate area: 1.2 cm 2 ) Electrocatalytic performance of MA1 after 15 deposition cycles on . CVs were recorded using a scan rate of 0.1 V / s.
[0184] Fig.81 Comparison of UV-Vis spectra of MA1 membranes, 0 h (red trace) and 1 h (red trace) of electrolysis.
[0185] Figure 82 Fabrication and electrocatalytic activity of MA2 in 0.1M LiClO4 aqueous electrolyte solution. Fig.82A : Ligands (building blocks) used to form MA2. Fig.82B )MA2 was formed layer by layer using automated spin coating of FTO / glass. A solution of PdCl2(PhCN)2 (4.0 mM in THF) and ligand L (2.0 mM in MeOH:DCM, 1:1). Fig.82C ) UV-Vis spectra of MA2 at different deposition steps. Inset: Linear fit of the absorption maximum (λ = 325 nm) versus the number of deposition cycles (R 2 >0.98). ( Fig.82D ) Cyclic voltammograms (CV) of MA2 (yellow) and bare FTO / glass (grey) (scan rate = 0.1 V / s). Inset: Photograph of MA2 showing the formation of O2. Active substrate area: 1.1 cm 2 . ( Fig.82E ) Controlled potential electrolysis (CPE) of MA2 (yellow) and bare FTO / glass (grey) at 1.75 V (vs. Ag / AgCl). An aqueous electrolyte solution (0.1 M LiClO4) was used at pH = 6.9. Fig.82F ) shows the N1s and Pd before and after electrolysis 2+ X-ray photoelectron spectroscopy (XPS) spectra in the 3d region.
[0186] Fig.83 Energy dispersive X-ray spectroscopy (EDS) spectra of MA1 before (top) and after (bottom) 7 h electrolysis.
[0187] Fig.84 Before electrolysis (top), after 1500 electrochromic cycles (middle), and at 1.75 V vs. Ag / Ag + SEM image of MA1 after 7 h of electrolysis (bottom).
[0188] Fig.85 Before electrolysis (top), after 1500 electrochromic cycles (center), at 1.75 V vs. Ag / Ag + SEM image of MA1 after 7 h of electrolysis (bottom).
[0189] Figure 86 Fig.86A ) After electrolysis, Cl - With ClO4 - Proposed exchange of anions. Fig.86B ) XPS spectra of MA1 film before (black trace) and after (red trace) electrolysis for 7 h.
[0190] Fig.87 Before electrolysis for 7 h (left) and after electrolysis relative to Ag / Ag + SEM image of MA2 after electrolysis at 1.75 V for 7 h (bottom).
[0191] Fig.88 Before electrolysis for 7 h (left) and after electrolysis relative to Ag / Ag + SEM image of MA2 after electrolysis at 1.75 V for 7 h (bottom).
[0192] Figure 89( Fig.89A )Tafel diagram of MA2. Fig.89B ) shows the X-ray photoelectron spectroscopy (XPS) spectra of the Cl 2p region before and after electrolysis of MA2.
[0193] Figure 90( Fig.90A ) CPE measurement of MA1, the electrolyte was renewed after 6 h. Fig.90B ) Catalytic current of bare FTO / glass (black trace) before and after CPE (6 h). Fig.90C ) CPE measurements of MA2, the electrolyte was renewed after 6 h. Fig.90D ) Catalytic current of bare FTO / glass before and after CPE (6 h).
[0194] Figure 91 For MA1( Fig.91A )、MA2( Fig.91B ) and blank FTO / glass in 0.1M LiClO4 aqueous electrolyte ( Fig.91C), comparison of the CV performance measured at a scan rate of 0.1 V / s with the CPE measurements at a holding potential of 1.75 V.
[0195] Figure 92 Overlapping CV of Figure 91 of MA1 relative to MA2, full CV scan (left) and zoomed-in area (right); at 0h ( Fig.92A ); at 1 hour ( Fig.92B ); at 5 hours ( Fig.92C ).
[0196] Figure 93 Sketch and real view of a custom designed airtight bulk cell for electrolysis, with wax covering the open space around the electrodes ( Fig.93A , Fig.93B ). During electrolysis, the gas outlet was also covered with wax. The volume of the headspace was 26 mL.
[0197] Fig.94 Calibration curve used to quantify the amount of H2 formed, as detected by gas chromatography (GC).
[0198] It will be understood that, for simplicity and clarity of illustration, the elements shown in the drawings are not necessarily drawn to scale. For example, for clarity, the size of some elements may be enlarged relative to other elements. In addition, reference numerals may be repeated in the drawings to indicate corresponding elements or similar elements where deemed appropriate.
[0199] Details
[0200] In the following detailed description, many specific details are set forth in order to provide a thorough understanding of the present invention. However, it will be appreciated by those skilled in the art that the present invention can be practiced without these specific details. In other cases, well-known methods, procedures and components are not described in detail to avoid obscuring the present invention.
[0201] In one embodiment, the present invention provides capacitors, batteries and electrodes comprising organic complexes coordinated by metal ions. In one embodiment, the present invention provides capacitors, batteries and electrodes comprising electrochromic films. In one embodiment, the present invention provides integrated electrochromic hybrid supercapacitors (EHSC). In one embodiment, the operation (charge-discharge) of the device is indicated by optical changes. In one embodiment, the core of the device is an electrochromic metal organic layer, which is used as both a battery-type electrode and an optical indicator of charge. In one embodiment, the second electrode is a capacitor electrode comprising a capacitor material. In one embodiment, the capacitor material is a layered composite of carbon nanotubes and conductive polymers, or a layered composite comprising carbon nanotubes and conductive polymers. The device operates at low potentials, showing high energy density and high power density, high coulomb efficiency and short charging time. In one embodiment, the stability of both color and energy over 1000 continuous charge-discharge cycles is demonstrated. In one embodiment, there is no significant change in the temperature of the indicating device under operating conditions. In one embodiment, the EHSC is connected to conventional circuit board lines to be charged and then effectively operate the diode.
[0202] The device of the present invention
[0203] In one embodiment, the present invention provides capacitors, batteries, and electrodes comprising an EC membrane, wherein the EC membrane comprises a metal ion organic complex.
[0204] In one embodiment, the present invention provides a hybrid supercapacitor in which the charge state of the capacitor is indicated by a color. The device is based on a molecular network that acts as both a battery-type electrode and a charge indicator. In some embodiments, the device also includes a layered composite of multi-walled carbon nanotubes and a conductive polymer that acts as a capacitive (second) electrode.
[0205] In one embodiment, the present invention provides a capacitor comprising:
[0206] A first electrode comprising an electrochromic film;
[0207] A second electrode;
[0208] an electrolyte in contact with the first electrode and the second electrode;
[0209] The electrochromic film comprises an organic complex coordinated by metal ions.
[0210] In one embodiment, the metal ion is an Fe ion. In one embodiment, the second electrode comprises carbon. In one embodiment, the carbon comprises carbon nanotubes. In one embodiment, the carbon nanotubes are multi-walled carbon nanotubes. In one embodiment, the carbon nanotubes are single-walled carbon nanotubes. In one embodiment, the second electrode comprises a polymer. In one embodiment, the second electrode comprises a conductive polymer. In one embodiment, the polymer comprises PEDOT and PSS. In one embodiment, the polymer is a conductive polymer selected from polyaniline, poly(9-vinyl carbazole) (PVK), polypyrrole (PPy), or comprises a conductive polymer selected from polyaniline, poly(9-vinyl carbazole) (PVK), polypyrrole (PPy). Combinations of conductive polymers can be used in embodiments of the present invention. In one embodiment, the second electrode comprises any material with capacity. MWCNT has a relatively high capacity and is therefore used in some embodiments. Other useful materials with high capacity that can be used for the second electrode are conductive metal organic frameworks (MOFs) and layered materials, such as graphene and MXenes. In one embodiment, the second electrode comprises two layers of capacitive material. According to this aspect and in one embodiment, one layer includes a conductive polymer and another layer includes carbon. In one embodiment, one layer includes PEDOT:PSS and another layer includes CNT. In other embodiments, the second electrode includes only one layer of one material (e.g., there is a polymer or carbon). According to this aspect and in one embodiment, if only CNT is applied to the electrode, it can fall off easily. If only PEDOT:PSS is used, less energy is obtained and the color is less stable. Therefore, in some embodiments, the two-layer structure provides a device with better stability, higher energy obtained and more stable color. In one embodiment, the polymer layer is first attached to the conductive material, and the layer containing carbon is attached to the polymer layer. In one embodiment, the carbon-containing material is first attached to the conductive material, and then the polymer layer is deposited, covering the carbon material and contacting the conductive material.
[0211] In one embodiment, the second electrode comprises a mixed layer of polymer and carbon. According to this aspect and in one embodiment, instead of a layer of polymer and another layer comprising carbon, a layer comprising a mixture of polymer and carbon is present in / on the second electrode. The carbon in such a mixed layer can be in any form as described herein, such as MWCNT, SWCNT, graphene, other porous carbon materials, etc. In one embodiment, the second electrode comprises a porous material. In one embodiment, the second electrode comprises porous carbon. In embodiments of the present invention, any other material known in the art for capacitor electrodes may be included in the second electrode.
[0212] In some embodiments, both PEDOT:PSS and CNTs have the same function. However, in some embodiments, PEDOT:PSS is also used to create better adhesion of CNTs to FTO / ITO.
[0213] In one embodiment, the electrode comprises a conductive material. In one embodiment, the electrode comprises a conductive oxide. In one embodiment, the conductive oxide is selected from ITO and FTO. In one embodiment, the conductive oxide is attached to a substrate. In one embodiment, the conductive oxide is attached to silicon oxide. In one embodiment, silicon oxide is a substrate. In one embodiment, the conductive oxide is a transparent conductive oxide. According to this aspect and in one embodiment, the indication of the color change is achieved or promoted by the transparent conductive oxide layer. According to this aspect and in one embodiment, the indication of the color change is achieved or promoted by optical / light transmission through the transparent conductive oxide layer. In other embodiments, the conductive material is not transparent. In one embodiment, one electrode comprises a transparent conductive material, and the other electrode comprises an opaque conductive material. In one embodiment, both electrodes include a transparent conductive material. In one embodiment, both electrodes include an opaque conductive material. The embodiments described above in this article are applicable to electrodes / devices that require detection of electrochromic states / use transmittance to obtain detection of electrochromic states, or to situations where detection of electrochromic states is required / uses reflection to obtain detection of electrochromic states, or to situations where detection of electrochromic states is not required / is not obtained.
[0214] In some embodiments, transparent means transparent to the eyes, transparent in the visible light range. In some embodiments, transparent means transparent in the UV range, in the IR range, in the visible light range or in any part thereof, wherein a change in optical absorbance is detected. In some embodiments, transparent means transparent at a specific wavelength or in a specific wavelength range. In one embodiment, transparent also refers to the absorption that the material has is not zero but is low enough to detect the change in the optical signal transmitted through the material. It should be noted that the transparency or translucency or low absorption of the transparent material is only required at the wavelength region where the change in the absorption spectrum of the metal ion organic complex is detected. In some embodiments, the transparent material may be opaque in other wavelength ranges. Therefore, in one embodiment, the conductive material (e.g., conductive oxide) is transparent or translucent, or it presents low optical absorption in a certain wavelength range.
[0215] In one embodiment, the capacitor is arranged in layers as follows:
[0216] a. The first substrate layer is attached to the first conductive oxide layer;
[0217] b. The first conductive oxide layer is attached to the metal ion coordinated organic complex layer;
[0218] c. The metal ion coordinated organic complex layer is attached to the electrolyte layer;
[0219] d. The electrolyte layer is attached to the carbon layer;
[0220] e. The carbon layer is attached to the polymer layer;
[0221] f. The polymer layer is attached to the second conductive oxide layer;
[0222] g. The second conductive oxide layer is attached to the second substrate layer.
[0223] In one embodiment, the thickness of the metal ion coordinated organic complex layer (EC film) is in the range of 5 nm and 1000 nm. In one embodiment, the thickness of the metal ion coordinated organic complex layer is in the range of 100 nm and 800 nm. In one embodiment, the thickness of the metal ion coordinated organic complex layer is in the range of 50 nm and 500 nm, or between 100 nm and 600 nm, or between 50 nm and 10 μm, or between 5 nm and 100 μm, or between 5 nm and 1 mm. In one embodiment, the thickness of the EC film is 280 nm. In one embodiment, the thickness of the EC film is in the range of 150 nm and 700 nm.
[0224] In one embodiment, the number of bilayers (each bilayer = metal linker layer + metal ion organic complex layer) is in the range of between 2 and 50 layers. In one embodiment, the number of bilayers is 18 layers (18 linkers + 18 complexes). In one embodiment, the number of (linker / organic complex) layers is in the range of between 2 and 40 layers, between 5 and 30 layers, between 10 and 20 layers. In one embodiment, the number of (linker / organic complex) layers is in the range of between 4 and 100 layers, between 5 and 1000 layers, or between 10 and 50,000 layers or between 10 and 100,000 layers. Any other number of layers may be applied to embodiments of the present invention. As described herein, the layers may be formed by any method including spin coating, dip coating, spray coating, CVD, PVD, and other methods as described herein. Some embodiments described herein below with respect to spin coating of layers may be applicable to other coating methods (e.g., spray coating and / or dip coating) as known to those skilled in the art. These embodiments are included in the present invention when other coating technologies are involved.
[0225] In one embodiment, the thickness of the PPC layer is in the range between 15 μm and 20 μm. In one embodiment, the thickness of the PPC layer is in the range between 10 μm and 30 μm. In one embodiment, the thickness of the PPC layer is in the range between 10 μm and 20 μm, or between 1 μm and 10 μm, or between 500 nm and 50 μm, or between 50 nm and 5 mm. Any other thickness of the PPC layer may be suitable for embodiments of the present invention. In one embodiment, the thickness of the polymer layer on the second substrate is in the range between 50 nm and 500 nm. In one embodiment, the thickness of the polymer layer is in the range between 100 nm and 1000 nm or between 200 nm and 400 nm. In one embodiment, the thickness of the polymer layer on the second substrate is 300 nm. In one embodiment, the thickness of the carbon layer on the second substrate is in the range between 10 μm and 20 μm. In one embodiment, the thickness of the carbon layer on the second substrate is 15 μm ± 5 μm. In one embodiment, the thickness of the carbon layer on the second substrate is 15 μm. In one embodiment, the thickness of the carbon layer on the second substrate is at least 5 μm or at least 1 μm or at least 15 μm or at least 20 μm. In one embodiment, the thickness of the carbon layer on the second substrate ranges between 1 μm and 200 μm.
[0226] In one embodiment, the thickness of the electrolyte layer is between 100 μm and 200 μm or in the range between 100 μm and 300 μm. In one embodiment, the thickness of the electrolyte layer is 180 μm. In one embodiment, the thickness of the electrolyte layer is 280 μm. In one embodiment, the thickness of the electrolyte layer is any thickness suitable for the operation of the device as known in the art. In one embodiment, the electrolyte layer includes an absorbent material soaked in a liquid electrolyte. In one embodiment, the absorbent (or adsorbent) material is paper. In one embodiment, the absorbent material is cloth. In one embodiment, the absorbent material is a porous material. In one embodiment, the absorbent material is a polymer. In one embodiment, the absorbent material is clay. In one embodiment, the electrolyte absorbent material includes a metal, a metal oxide, a metal alloy or a combination thereof. In one embodiment, the electrolyte is not provided with additional absorbent / adsorbent materials. In one embodiment, the electrolyte is in liquid form. In one embodiment, the electrolyte is a gel electrolyte. In one embodiment, the electrolyte is a solid electrolyte. In one embodiment, a spacer is provided. According to this aspect and in one embodiment, the spacer is a closed frame or a partially closed frame to which the electrolyte is added. In one embodiment, the spacer encapsulates the electrolyte. In one embodiment, the spacer is a frame placed between the first electrode and the second electrode, and within the space formed within the spacer between the electrodes, the electrolyte is held. In one embodiment, the purpose of the spacer is to fix the electrolyte in place. In one embodiment, the purpose of the spacer is to prevent leakage of the electrolyte. Fig.56C An embodiment of a spacer is shown in . In one embodiment, the spacer is made of plastic. In one embodiment, the spacer is tape. In one embodiment, the spacer is double-sided tape. In one embodiment, the spacer is made of glue. In one embodiment, the spacer is made of a polymer. In one embodiment, the spacer is made of an organic polymer. In one embodiment, the electrolyte includes ACN. In one embodiment, the electrolyte includes PC / ACN (PC is propylene carbonate). In one embodiment, the electrolyte is PC:ACN, LiClO4, or includes PC:ACN, LiClO4. Other electrolyte materials / solutions and compositions can be used in embodiments of the present invention as known in the art.
[0227] In one embodiment, the first substrate, the second substrate or a combination thereof are made of a material selected from the group consisting of silicon dioxide and an organic polymer, or include the material. In one embodiment, the first substrate, the second substrate or a combination thereof include a material selected from glass, quartz, polyethylene terephthalate (PET), PDMS or any combination thereof. In one embodiment, the substrate is flat. In one embodiment, the substrate is curved. In one embodiment, the substrate has a cylindrical shape. In one embodiment, the substrate geometry is selected from circular, spherical, rectangular, square, cubic, cylindrical, spiral, triangular, box-shaped, teardrop shape. Any other shape or geometry may be applicable to the substrate of the present invention, as known in the art. In one embodiment, the substrate is rigid. In one embodiment, the substrate is flexible. According to this aspect and in one embodiment, the substrate can be bent, bent, folded, rolled up or twisted to fit the desired geometry. In one embodiment, the capacitor is a supercapacitor. In one embodiment, the substrate is attached to a conductive oxide as described herein. In some embodiments, the substrate is a conductive oxide. According to this aspect and in one embodiment, the substrate and the conductive oxide are one. In such a case, the substrate and the conductive oxide are referred to as "substrate" or "conductive substrate". Any embodiment described herein about the conductive oxide on the substrate is also applicable to the "substrate" which is a conductive material itself. In one embodiment, the capacitor is a hybrid capacitor in which the first electrode is a battery-type electrode and the second electrode is a capacitive electrode. In one embodiment, the first electrode is used as an electrochemical electrode (wherein a redox reaction occurs), and the second electrode is used as an electrostatic electrode (capable of holding a charge such as an electron). In one embodiment, the electrochromic film comprising an organic complex coordinated by a metal ion has a transmittance difference between an oxidized state and a reduced state of 10% and higher. In one embodiment, the electrochromic film comprising an organic complex coordinated by a metal ion has a transmittance difference between an oxidized state and a reduced state of 64% and higher. In one embodiment, the electrochromic film comprising an organic complex coordinated by a metal ion has a transmittance difference (ΔT) between an oxidized state and a reduced state of 30% and higher, or 20% and higher, or 40% and higher, or 50% and higher, or 60% and higher, or 70% and higher, or 80% and higher. Parameters such as the metal ions in the organic complex, the ligands of the complex, and the selection of the electrolyte can affect the difference in transmittance between the oxidized and reduced states of the membrane. In one embodiment, the transmittance contrast ratio of the device of the present invention is in the range of between 24% and 27%. In one embodiment, the transmittance in one state (e.g., the charged state) is about 40%, while the transmittance in another state (e.g., the discharged state) is about 12%.In one embodiment, the transmittance contrast ratio between the charged state and the discharged state of the device of the present invention is in the range of between 20% and 50%, or between 10% and 60%, or between 10% and 80%, or between 5% and 90%. In one embodiment, the charge stability V of the device of the present invention is between 10% and 60%, or between 10% and 80%, or between 5% and 90%. 1 / 2 In one embodiment, the color stability V of the device of the present invention is at least 60 minutes. 1 / 2 For at least 38 minutes.
[0228] In one embodiment, the device operates at a low potential, such as -0.6V to 2V. According to this aspect and in one embodiment, the device is charged by a constant current, and the voltage generated across the device is limited to a specific range. For example, the voltage is limited to a range of -0.6V to 2V. According to this aspect and in one embodiment, other potential ranges can be defined for charge / discharge voltage limits. For example, during the charge / discharge cycle, a voltage range of -1.0V-2.5V can be set as the voltage limit of the device. The device of the present invention shows high energy density and high power density. For example, the device of the present invention has been measured to ~2.2Wh·kg in one embodiment. -1 The energy density and ~2529W·kg -1 In an embodiment of the present invention, the energy density of the device of the present invention is between 1Wh / kg and 52Wh·kg -1 In some embodiments, the energy density of the device of the present invention is between 1Wh / kg and 100Wh·kg -1 In one embodiment, the device retains at least 90% of its initial energy density after 3000 charge / discharge cycles. In one embodiment, the device retains at least 75% of its initial energy density after 3000 charge / discharge cycles. Other energy density values can be obtained with the device of the present invention, depending on the active materials used in embodiments of the present invention. In some embodiments, the power density of the device of the present invention is between 930 W·kg -1 and 6500W·kg -1 In some embodiments, the power density of the device of the present invention is within the range of 100 W·kg -1 and 20,000W·kg -1In the range between . Other power density values can be obtained with the device of the present invention, depending on the active materials (e.g., organic complexes and capacitor materials) used in the embodiments of the present invention. The device of the present invention has a high Coulombic efficiency. For example and in one embodiment, the Coulombic efficiency of the device of the present invention is 99%. In one embodiment, the Coulombic efficiency of the device of the present invention is higher than 99%. In one embodiment, the Coulombic efficiency of the device of the present invention is higher than 90% or higher than 95% or higher than 99.5%. In one embodiment, the Coulombic efficiency of the device of the present invention is in the range between 90% and 99.99%. In one embodiment, the Coulombic efficiency of the device of the present invention is in the range between 75% and 99.99%. In some embodiments, the device of the present invention provides a short charging time. For example and in one embodiment, the charging time of the device of the present invention is ~2s. In some embodiments, the charging time of the device of the present invention is in the range between 2s and 60s. In some embodiments, the charging time of the device of the present invention is in the range between 1s and 5min. The charging time depends on the amount of current applied. In some embodiments, the charge retention time (V 1 / 2 ) is ~60min. In some embodiments, the charge retention time of the device of the present invention is in the range of between 25min and 60min. In some embodiments, the charge retention time of the device of the present invention is in the range of between 20min and 180min. Other charge retention time values can be obtained with the device of the present invention, depending on the active materials and other parameters of the device used in the embodiments of the present invention. In some embodiments, the capacitance of the PPC layer is 10.7F / g. In one embodiment, devices with different capacitive materials, different geometries or compositions exhibit other capacitance values. In one embodiment, other capacitive layers can be used as described above herein.
[0229] The device of the present invention provides stability of both color and energy for many charge-discharge cycles. For example, in one embodiment, more than 1000 continuous charge-discharge cycles have been demonstrated for the device of the present invention. In one embodiment, for more than 500 cycles, for more than 1000 cycles, for more than 2000 cycles, for more than 3000, 5000 or 10000 charge-discharge cycles, the device of the present invention exhibits stability of color and energy. In one embodiment, for more than 500 cycles, for more than 1000 cycles, for more than 2000 cycles, for more than 3000, 5000 or 10,000 charge-discharge cycles, the device of the present invention exhibits / maintains color stability of more than 90% in terms of ΔT% compared to the initial ΔT% value, and energy stability of more than 90% compared to the initial energy value. In some embodiments, the device of the present invention exhibits a controlled temperature during operation. In some embodiments, there is no significant change in the temperature of the device under operating conditions. In one embodiment, there is no change in the temperature of the device during operation. In some embodiments, the temperature change of the device of the present invention under operation is small. In some embodiments, the temperature change of the device of the present invention during operation is less than 1°C. In some embodiments, the temperature change of the device of the present invention during operation is less than 2°C. In some embodiments, the temperature change of the device of the present invention during operation is less than 3°C or less than 5°C or less than 10°C or less than 15°C or less than 20°C. In some embodiments, when the device operation lasts for at least 1000 charge / discharge cycles, or when the device operation lasts for at least 2000 charge / discharge cycles or lasts for at least 5000 charge / discharge cycles or lasts for multiple cycles in the range between 1 and 10,000 cycles or lasts for multiple cycles in the range between 1 and 5000 cycles, or between 1 and 2000 cycles, or between 1 and 1000 cycles, the temperature change described above herein (e.g., less than 1°C) is effective. In some embodiments, the temperature change of the device under operation is small. In some embodiments, the device temperature change does not interfere with the function of the device.
[0230] In one embodiment, the electrochromic film comprising the organic complex of metal ion coordination can keep at least 40% of its maximum contrast ratio after 50 switching cycles between oxidation state and reduction state. In one embodiment, the electrochromic film comprising the organic complex of metal ion coordination can keep at least 54% of its maximum contrast ratio after 1000 switching cycles between oxidation state and reduction state. In one embodiment, the electrochromic film comprising the organic complex of metal ion coordination can keep at least 90% of its maximum contrast ratio after 1000 switching cycles between oxidation state and reduction state. In one embodiment, the electrochromic film comprising the organic complex of metal ion coordination can keep at least 70% of its maximum contrast ratio after 1000 switching cycles between oxidation state and reduction state or after 1300 switching cycles or after 1500 switching cycles or after 2000 or 3000 or 5000 or 10,000 cycles. The choice of metal ion organic complex used may affect the % stability described herein above in terms of contrast ratio after a certain number of cycles.
[0231] In one embodiment, a capacitor of the present invention comprises:
[0232] o a first electrode, the first electrode comprising:
[0233] a first substrate comprising a first conductive oxide surface; and
[0234] a membrane comprising a metal ion coordinated organic complex attached to the surface of the first conductive oxide;
[0235] o a second electrode, the second electrode comprising:
[0236] a second substrate comprising a second conductive oxide surface; and
[0237] a layer comprising a capacitive material attached to the second conductive oxide surface;
[0238] oElectrolytes, which are in contact with:
[0239] a film of an organic complex coordinated to the metal ion of the first electrode; and
[0240] • The capacitive material of the second electrode.
[0241] In one embodiment, the electrochromic film comprises an organic complex coordinated by metal ions. In one embodiment, the layer of the capacitor material comprises a polymer or carbon or a combination thereof. In one embodiment, the layer of the capacitor material comprises a polymer layer attached to a layer comprising carbon. In one embodiment, the first conductive oxide and the second conductive oxide each independently comprise an electrical contact capable of independently connecting the conductive oxide to an external device / circuit. In one embodiment, the organic complex coordinated by metal ions comprises a metal ion polypyridyl complex. In one embodiment, the electrochromic film comprising an organic complex coordinated by metal ions comprises an organic complex coordinated by metal ions from 2 to 80 layers, and the layers are connected to each other by a metal connector. In one embodiment, the metal ion in the metal connector is at least one metal ion selected from the group consisting of: Zn, Os, Ru, Fe, Pt, Pd, Ni, Ir, Rh, Co, Cu, Re, Tc, Mn, V, Nb, Ta, Hf, Zr, Cr, Mo, W, Ti, Sc, Ag, Au and Y.
[0242] In one embodiment, the metal ion coordinated organic complex comprises a polypyridyl complex represented by Formula I.
[0243]
[0244] in
[0245] M is a transition metal selected from Mn, Fe, Co, Ni, Cu, Zn, Ti, C, Cr, Rh or Ir;
[0246] n is the formal oxidation state of the transition metal, where n is 0-6;
[0247] X is a counterion;
[0248] m is a number ranging from 0 to 6;
[0249] R1 to R 18 Each is independently selected from H, halogen, -OH, -N3, -NO2, -CN, -N(R 20 )2.-CON(R 20 2. -COOR 20 、-SR 20 , -SO3H, -CH=CH-pyridyl, -(C1-C 10 )alkyl, -(C2-C 10 )alkenyl, -(C2-C 10 )alkynyl, -(C1-C 10 ) alkoxy, cycloalkyl, heterocycloalkyl, aryl, heteroaryl, wherein (C1-C 10 )alkyl, (C2-C10 )alkenyl, (C2-C 10 ) alkynyl, cycloalkyl, heterocycloalkyl, aryl or heteroaryl may be optionally substituted with halogen, -OR 20 、-COR 20 、-COOR 20 、-OCOOR 20 、-OCON(R 20 )2, -(C1-C8)alkylene-COOR 20 、-CN、-N(R 20 )2, -NO2, -SR 20 , -(C1-C8)alkyl, -O-(C1-C8)alkyl, -CON(R 20 )2 or -SO3H substituted;
[0250] A1 to A6 are each independently 19 A group of formula III, i.e., a pyridine or pyridine derivative moiety, or a group of formula IV, i.e., a pyrimidine or pyrimidine derivative moiety, attached to the ring structure of the complex of general formula I
[0251]
[0252] R 19 Each independently selected from a covalent bond, H2C-CH2, HC=CH, C≡C, N=N, HC=N, N=CH, H2C-NH, HN-CH2-COO-, -CONH-, -CON(OH)-, -NR 20 -,-Si(R 20 )2-, alkylene, phenylene, biphenylene, optionally interrupted by one or more heteroatoms selected from O, S or N, a peptide moiety consisting of 3 to 5 amino acid residues,
[0253] R x and R y Each is independently selected from H, halogen, -OH, -N3, -NO2, -CN, -N(R 20 )2.-CON(R 20 2. -COOR 20 、-SR 20 , -SO3H, -CH=CH-pyridyl, -(C1-C 10 )alkyl, -(C2-C 10 )alkenyl, -(C2-C 10 )alkynyl, -(C1-C 10 ) alkoxy, cycloalkyl, heterocycloalkyl, aryl, heteroaryl, protected carboxyl or protected amino, wherein (C1-C 10 )alkyl, (C2-C10 )alkenyl, (C2-C 10 ) alkynyl, cycloalkyl, heterocycloalkyl, aryl or heteroaryl may be optionally substituted with halogen, -OR 20 、-COR 20 、-COOR 20 、-OCOOR 20 、-OCON(R 20 )2, -(C1-C8)alkylene-COOR 20 、-CN、-N(R 20 )2, -NO2, -SR 20 , -(C1-C8)alkyl, -O-(C1-C8)alkyl, -CON(R 20 )2 or -SO3H; and
[0254] R 20 Each is independently H, (C1-C6) alkyl or aryl.
[0255] In one embodiment, the metal ion coordinated organic complex comprises a polypyridyl complex represented by Formula II:
[0256]
[0257] in
[0258] n is the formal oxidation state of Fe, where n is 0-6;
[0259] X is a counterion;
[0260] m is a number ranging from 0 to 6;
[0261] R1 to R 18 Each is independently selected from H, halogen, -OH, -N3, -NO2, -CN, -N(R 20 )2.-CON(R 20 2. -COOR 20 、-SR 20 , -SO3H, -CH=CH-pyridyl, -(C1-C 10 )alkyl, -(C2-C 10 )alkenyl, -(C2-C 10 )alkynyl, -(C1-C 10 ) alkoxy, cycloalkyl, heterocycloalkyl, aryl, heteroaryl, wherein (C1-C 10 )alkyl, (C2-C 10 )alkenyl, (C2-C 10 ) alkynyl, cycloalkyl, heterocycloalkyl, aryl or heteroaryl may be optionally substituted with halogen, -OR 20 、-COR20 、-COOR 20 、-OCOOR 20 、-OCON(R 20 )2, -(C1-C8)alkylene-COOR 20 、-CN、-N(R 20 )2, -NO2, -SR 20 , -(C1-C8)alkyl, -O-(C1-C8)alkyl, -CON(R 20 )2 or -SO3H substituted;
[0262] A1, A3 and A5 are each independently 19 A group of formula III, i.e., a pyridine or pyridine derivative moiety, or a group of formula IV, i.e., a pyrimidine or pyrimidine derivative moiety, attached to the ring structure of the complex of general formula II
[0263]
[0264] R 19 Each independently selected from a covalent bond, H2C-CH2, cis / trans HC=CH, C≡C, N=N, HC=N, N=CH, H2C-NH, HN-CH2-COO-, -CONH-, -CON(OH)-, -NR 20 -,-Si(R 20 )2-, alkylene, phenylene, biphenylene, optionally interrupted by one or more heteroatoms selected from O, S or N, a peptide moiety consisting of 3 to 5 amino acid residues,
[0265] R x and R y Each is independently selected from H, halogen, -OH, -N3, -NO2, -CN, -N(R 20 )2.-CON(R 20 2. -COOR 20 、-SR 20 , -SO3H, -CH=CH-pyridyl, -(C1-C 10 )alkyl, -(C2-C 10 )alkenyl, -(C2-C 10 )alkynyl, -(C1-C 10 ) alkoxy, cycloalkyl, heterocycloalkyl, aryl, heteroaryl, protected carboxyl or protected amino, wherein (C1-C 10 )alkyl, (C2-C 10 )alkenyl, (C2-C 10 ) alkynyl, cycloalkyl, heterocycloalkyl, aryl or heteroaryl may be optionally substituted with halogen, -OR 20 、-COR20 、-COOR 20 、-OCOOR 20 、-OCON(R 20 )2, -(C1-C8)alkylene-COOR 20 、-CN、-N(R 20 )2, -NO2, -SR 20 , -(C1-C8)alkyl, -O-(C1-C8)alkyl, -CON(R 20 )2 or -SO3H substituted;
[0266] B1 to B3 are each independently selected from H, halogen, -OH, -N3, -NO2, -CN, -N(R 20 )2.-CON(R 20 2. -COOR 20 、-SR 20 , -SO3H, -CH=CH-pyridyl, -(C1-C 10 )alkyl, -(C2-C 10 )alkenyl, -(C2-C 10 )alkynyl, -(C1-C 10 ) alkoxy, cycloalkyl, heterocycloalkyl, aryl, heteroaryl, protected carboxyl or protected amino, wherein (C1-C 10 )alkyl, (C2-C 10 )alkenyl, (C2-C 10 ) alkynyl, cycloalkyl, heterocycloalkyl, aryl or heteroaryl may be optionally substituted with halogen, -OR 20 、-COR 20 、-COOR 20 、-OCOOR 20 、-OCON(R 20 )2, -(C1-C8)alkylene-COOR 20 、-CN、-N(R 20 )2, -NO2, -SR 20 , -(C1-C8)alkyl, -O-(C1-C8)alkyl, -CON(R 20 )2 or -SO3H; and
[0267] R 20 Each is independently H, (C1-C6) alkyl or aryl.
[0268] Formula II is shown above herein, wherein M = Fe. However, other transition metals may be the metal ion M in Formula II above. For example and in one embodiment, the metal ion M is a transition metal selected from Mn, Fe, Co, Ni, Cu, Zn, Ti, Cr, Rh, Ru, Os or Ir.
[0269] In one embodiment, the metal ion coordinated organic complex comprises a polypyridyl complex represented by one of the following formulae, or a mixture of the following formulae, or a combination of the following formulae and molecules containing different metal centers or ligands (according to Formula I and Formula II):
[0270]
[0271]
[0272] In one embodiment, the polypyridyl complex is a mixture of polypyridyl complexes.
[0273] In one embodiment, the present invention provides an apparatus comprising:
[0274] o An electrochromic hybrid supercapacitor comprising:
[0275] A first electrode comprising an electrochromic film;
[0276] A second electrode;
[0277] an electrolyte in contact with the first electrode and the second electrode;
[0278] o a power source, optionally connected to the first electrode via a first electrical contact and to the second electrode via a second electrical contact;
[0279] o a load, optionally connected to the first electrode via a first electrical contact and to the second electrode via a second electrical contact.
[0280] In one embodiment, the device further comprises an optical detector. In one embodiment, the device further comprises a light source. In one embodiment, the device further comprises a processor for receiving an input signal from the optical detector and providing a control signal to the device. In one embodiment, the control comprises at least one of: starting charging, stopping charging, starting discharging, and stopping discharging. Fig.67 and Fig.68In the figure, an embodiment of such a device is illustrated. For the sake of clarity, optional electronic components such as optical detectors, light sources, processors, displays are not shown in the figure, but these components are added in the embodiment of the device, system and / or equipment of the present invention. In one embodiment, the connection (e.g., electrical contacts) of the first electrode, the second electrode or both to the power supply, the load or both is a direct connection or indirect connection through other electronic components or electronic devices. In one embodiment, the connection of the first electrode, the second electrode or both to the power supply, the load, other electronic circuit components or any combination thereof is optional, so that it can be connected and disconnected as needed. According to this aspect and in one embodiment, the connection of the power supply / load / other circuit elements to the capacitor is activated by one or more switches. In one embodiment, the switch can be an on / off switch, and in one embodiment, the switch turns on / off the circuit or electrical contacts or connection between the power supply / load and the capacitor or any other energy storage device of the present invention.
[0281] In one embodiment, the term "optionally" in the phrase describing the power supply optionally connected to the first electrode / second electrode through the first electrical contact / second electrical contact means that the electrical contacts can be connected or disconnected as needed. Therefore and in one embodiment, the connection between the power supply and the electrode includes a switch, a gate or any other electronic component or optoelectronic component, which can allow or interrupt, form or disconnect the electrical contact between the power supply and the electrode as needed. The electrical contacts can also be manually established or removed by manually connecting / disconnecting a clamp, a wire, a plug to establish / disconnect the connection. The above description of "optionally" also refers to the optional connection of the load to the electrode in the phrase describing the load, and the load is optionally connected to the first electrode / second electrode through the first electrical contact / second electrical contact, as described herein. According to this aspect and in one embodiment, the electrical contacts of the present invention include or are attached to a switch or a gate or a plug, or a clamp or any other on / off element, for electrically connecting / disconnecting two or more elements in the device of the present invention as known in the art.
[0282] In one embodiment, the battery-type electrode is also referred to as a battery-like electrode. In one embodiment, the battery-type electrode includes only one type of active material film (one type of film includes a linker and a metal ion organic complex). According to this aspect and in one embodiment, the battery-type electrode includes only one type of metal ion in an organic complex coordinated by the metal ion. In one embodiment, the membrane on the first electrode does not include two separate membranes, so that one membrane includes one type of metal ion in a metal ion organic complex, and the other membrane includes another type of metal ion in a metal ion organic complex. In one embodiment, the device of the present invention does not require optical irradiation to induce charging. In one embodiment, the device of the present invention does not require optical irradiation to induce discharge. In one embodiment, the device of the present invention does not require electromagnetic irradiation to induce charging. In one embodiment, the device of the present invention does not require electromagnetic irradiation to induce discharge. In one embodiment, the device of the present invention does not require an applied potential to induce discharge. According to this aspect and in one embodiment, the device of the present invention can discharge without applying an external potential / voltage to the device. According to this aspect and in one embodiment, the discharge of the device of the present invention occurs spontaneously. In one embodiment, the first electrode of the present invention does not comprise two layers, wherein the first layer comprises one type of metal ions in an organic complex and the second layer comprises a second type of metal ions in an organic complex.
[0283] In one embodiment, the device of the present invention includes a type of metal ion in a metal ion organic complex selected from: Fe or Ru or Os or Cu or Ni or Co or Zn. Other metal ions can be used as the metal ion in the metal ion organic complex. For example and in one embodiment, any transition metal ion that can undergo oxidation / reduction within the potential range suitable for the device can be included as the metal ion in the metal ion organic complex used on the electrode of the present invention.
[0284] In one embodiment, the device of the present invention as described herein above is arranged without a load or a circuit comprising a load. According to this aspect and in one embodiment, the device of the present invention is provided with a power supply and can be connected to any circuit / load as required. Therefore, in one embodiment, the present invention provides a device comprising:
[0285] o An electrochromic hybrid supercapacitor comprising:
[0286] A first electrode comprising an electrochromic film;
[0287] A second electrode;
[0288] an electrolyte in contact with the first electrode and the second electrode;
[0289] o a power source, optionally connected to the first electrode via a first electrical contact and to the second electrode via a second electrical contact;
[0290] The electrochromic film comprises an organic complex coordinated by metal ions.
[0291] Battery of the present invention
[0292] In one embodiment, the present invention provides a battery comprising:
[0293] A first electrode comprising an electrochromic film;
[0294] a second electrode capable of inducing an oxidation, reduction, or oxidation and reduction reaction on a surface of the second electrode;
[0295] an electrolyte in contact with the first electrode and the second electrode;
[0296] The electrochromic film comprises an organic complex coordinated by metal ions.
[0297] According to this aspect and in one embodiment, the two electrodes (the first electrode and the second electrode) are electrochemical electrodes or battery-type electrodes. In one embodiment, during operation, the reaction at the two electrodes is an oxidation / reduction reaction. According to this aspect and in one embodiment, the two electrodes include electrochromic materials. In one embodiment, the battery is a rechargeable battery. In one embodiment, the charge level of the battery can be determined by the color of one or two electrodes. In one embodiment, the second electrode includes a metal. In one embodiment, the second electrode includes a conductive surface. In one embodiment, the second electrode includes a conductive oxide. In one embodiment, the second electrode includes a metal ion organic complex. In one embodiment, the metal ion organic complex on the second electrode is different from the metal ion organic complex on the first electrode. In one embodiment, the metal ion in the metal ion organic complex on the second electrode is different from the metal ion in the organic complex present on the first electrode. In one embodiment, the metal ion organic complex on the first electrode or on the second electrode or on both the first electrode and the second electrode is a polypyridyl complex.
[0298] In one embodiment, the present invention provides a battery comprising:
[0299] a first electrode comprising an organic material;
[0300] a second electrode capable of inducing an oxidation, reduction, or oxidation and reduction reaction on a surface of the second electrode;
[0301] an electrolyte in contact with the first electrode and the second electrode;
[0302] The organic material comprises an organic complex coordinated by metal ions.
[0303] Electrode of the present invention
[0304] In one embodiment, the present invention provides an electrode comprising an electrochromic material. In one embodiment, the electrochromic material comprises an organic complex coordinated by a metal ion. In one embodiment, the electrode further comprises an electrical contact. In one embodiment, the electrode comprises a conductive surface attached to the electrochromic material. In one embodiment, the electrical contact is attached to the conductive surface. In one embodiment, the present invention provides an electrode comprising:
[0305] a substrate comprising a conductive surface;
[0306] an electrochromic film in contact with the surface;
[0307] The electrochromic film comprises an organic complex coordinated by metal ions.
[0308] In one embodiment, the present invention provides an electrode comprising:
[0309] a substrate comprising a conductive surface;
[0310] an organic material in contact with the surface;
[0311] The organic material comprises an organic complex coordinated by metal ions.
[0312] In some embodiments, the present invention provides an electrode comprising a polymer and carbon. In one embodiment, the electrode is a capacitor electrode. In one embodiment, the electrode also includes an electrical contact. In one embodiment, the polymer is a conductive polymer. In one embodiment, the polymer includes PEDOT, PSS or any combination thereof. In one embodiment, carbon includes CNT, graphene, carbon nanoparticles or other porous carbon materials. In one embodiment, CNT is MWCNT. In one embodiment, CNT is SWCNT. In one embodiment, CNT is a mixture of MWCNT and SWCNT. In one embodiment, polymer and carbon are provided as different layers in the electrode of the present invention. According to this aspect and in one embodiment, in the electrode of the present invention, a polymer layer is attached to a layer comprising carbon. In one embodiment, the electrode includes a layer comprising a mixture of a polymer and a carbonaceous material. In one embodiment, the electrode includes both a separate layer (comprising a polymer or a carbon material, but not both) and a mixed layer comprising both carbon and polymer. It should be noted that in some embodiments, the term "carbon" refers here to a material comprising only carbon atoms or mainly comprising carbon atoms or comprising a portion where only carbon atoms are present. Except the group that surface is combined, such carbon material is inorganic material in the sense that it does not include, for example, H atom in its main chain.Therefore, in some embodiments, term " carbon " does not refer to the organic material that includes carbon atom in its skeleton / main chain.According to this aspect and in one embodiment, carbon material is selected from the group consisting of: CNT, graphene, fullerene, carbon nanoparticle, the aggregate of carbon nanoparticle, carbon sheet, carbon rod, porous carbon, graphite or any combination thereof.In one embodiment, term carbon refers to the material that at least 70% or at least 80% or at least 90% or at least 95% or at least 99% of its atoms are carbon atoms.
[0313] In some embodiments, PEDOT:PSS is also used to create better adhesion of CNTs to FTO / ITO.
[0314] In another embodiment, the capacitor, battery, electrode or other device of the present invention is not electrochromic or exhibits less obvious electrochromic properties. According to this aspect and in one embodiment, the metal ion organic complex in such a device does not show obvious electrochromic behavior. In one embodiment, the color difference between the oxidized state and the reduced state of the device is not obvious, or it is undetectable, or it does not remain stable for a large number of charge / discharge cycles. However, in view of their energy storage properties, such devices are also included in the present invention as capacitors, batteries and electrodes. Therefore, any aspect described herein about electrochromic devices (except for the embodiment describing electrochromic properties) can be applied to non-electrochromic devices, only slightly electrochromic devices or devices that do not utilize electrochromic properties. Such embodiments and devices are included in the present invention.
[0315] In one embodiment, the electrochromic electrode of the present invention changes color from purple to transparent when charging, and changes color from transparent to purple when discharging. However, many other colors and color changes are included in the embodiments of the electrode of the present invention. In one embodiment, the color change depends on the ligands in the redox ion and the metal ion organic complex. Therefore, changing the metal ion (for example, changing to another metal ion instead of Fe) may result in different colors in the charged state / discharged state. Changing the metal ion (for example, changing to another metal ion instead of Fe) may result in different colors in the oxidized state / reduced state. In addition, changing the ligands of the metal ion organic complex can change the color of the complex, and thus change the color of the electrode in the charged state / discharged state. See, for example, in Fig.49A and Fig.49BThe colors of the Ru and Os complexes shown in Figure 1 and the colors of the Fe complexes with different ligands. All colors presented by a variety of complexes / metal ions / ligands and all possible color changes between the reduced and oxidized states of metal ions in organic complexes are included in the present invention and can be applied to the device of the present invention. In addition, in some embodiments, instead of or in addition to the color change between the oxidized and reduced states of the metal ions in the complex visible to the naked eye, there is a change in the light absorption spectrum, which is not manifested by a color change visible to the naked eye. For example, a change in the absorption spectrum of the complex in the UV range or in the IR range may be accompanied by an oxidation / reduction change of the metal ions in the complex. In addition, a small color change obtained from a small change in the absorption spectrum within a limited wavelength range or a small change in the intensity of a certain color may be accompanied by a reduction / oxidation change of the metal ions in the complex. All such changes may not be visible to the naked eye. However, in some embodiments, any of these changes that can be detected by an optical detector is sufficient to evaluate the charge / discharge level of the electrode / device. Therefore, all such absorption spectrum changes are included in the embodiments of the present invention. The embodiments described herein with respect to color changes are also applicable to absorption spectrum changes that are unrelated to color changes visible to the naked eye. All such embodiments are included in the present invention.
[0316] Process for producing the device of the present invention
[0317] In one embodiment, the present invention provides a process for producing the electrodes, capacitors, batteries and any other energy storage devices of the present invention.
[0318] In one embodiment, the present invention provides a process for producing a capacitor, the capacitor comprising:
[0319] o a first electrode comprising an electrochromic material;
[0320] oSecond electrode;
[0321] o an electrolyte in contact with the first electrode and the second electrode;
[0322] The electrochromic material comprises an organic complex coordinated by metal ions;
[0323] The process comprises:
[0324] o providing a first substrate comprising a first conductive oxide surface;
[0325] o applying a film comprising a metal ion coordinated organic complex onto the first conductive oxide surface, thereby forming a first electrode;
[0326] o providing a second substrate comprising a second conductive oxide surface;
[0327] o applying a polymer layer onto the second conductive oxide surface;
[0328] o applying a layer comprising carbon onto the polymer, thereby forming a second electrode;
[0329] o Providing an electrolyte layer so that the first electrode and the second electrode are independently in contact with the electrolyte layer.
[0330] In one embodiment, the order of the process steps is changed. According to this aspect and in one embodiment, the second electrode can be prepared before the first electrode is prepared, or vice versa. In one embodiment, the electrolyte is first arranged on the first electrode, and then the second electrode is attached to the electrolyte on the other side of the electrolyte. In another embodiment, the electrolyte is first attached / arranged on the second electrode, and then the first electrode is attached to the electrolyte on the other side of the electrolyte. In one embodiment, the first electrode, the second electrode or both are prepared in advance, and are kept until the capacitor is assembled with the electrolyte. A batch of the first electrode / second electrode can be prepared in advance, and the capacitor can be constructed by adding an electrolyte layer as needed. In one embodiment, the first conductive oxide and the second conductive oxide each independently include an electrical contact capable of independently connecting the conductive oxide to an external device. The electrical contact is known in the art. For example and in one embodiment, the electrical contact is a metal contact. In one embodiment, the metal contact is a metal wire / strip attached to the conductive oxide of the electrode on one side and attached to a power source / load / other electronic circuit element, etc. on the other side directly or through another wire / clamp, or through an on / off switch, or through other circuit elements. In one embodiment, the step of applying a film comprising a metal ion coordinated organic complex onto the first conductive oxide surface, thereby forming a first electrode comprises:
[0331] Applying at least one metallic connector to the conductive surface of the first substrate either through a template layer or directly;
[0332] applying at least one metal ion coordinated organic complex to form a layer; and
[0333] • Repeat the application steps to obtain multiple layers of EC material.
[0334] In one embodiment, the metal ion coordinated organic complex comprises at least one functional group that is capable of binding to the metal linker. In one embodiment, the binding comprises a coordination bond between the functional group and the metal linker. In one embodiment, the metal ion coordinated organic complex is a metal ion polypyridyl complex. In one embodiment, the applying step comprises one or more of roll-to-roll, spin coating, dip coating, spray coating, PVD, CVD. In one embodiment, the polypyridyl complex comprises one or more isomers of the same compound or a mixture thereof. In one embodiment, the isomer is an enantiomer, and the polypyridyl complex comprises one or two enantiomers of the same compound or a mixture of the one or two enantiomers. In one embodiment, the applying step comprises a spin coating step. In one embodiment, the spin coating step of applying the metal linker has a first rotation rate and a first rotation time, and the step of applying the metal ion coordinated organic complex has a first rotation rate and a first rotation time. In one embodiment, the first rotation rate is from 100 rpm to 2000 rpm, and the first rotation time is from 0.3 seconds to 60 seconds. In one embodiment, the spin coating step of applying the metal connector has a second rotation rate and a second rotation time, and the step of applying the metal ion coordinated organic complex has a second rotation rate and a second rotation time. In one embodiment, the second rotation rate is from 200 rpm to 3000 rpm, and the second rotation time is from 1 second to 120 seconds.
[0335] In one embodiment, the two application steps are repeated to obtain from 2 to 80 layers. In one embodiment, the metallic interconnect is applied as a metal ion complex.
[0336] In one embodiment, after the step of applying at least one metal ion coordinated organic complex to form a layer and before the step of repeating the applying step to obtain a multilayer EC material, one or both of the following steps are performed:
[0337] · Steps for washing the layer;
[0338] · Drying layer step.
[0339] In one embodiment, the solvent used in the washing step is selected from the group consisting of alcohols, ethers, esters, halogenated solvents, hydrocarbons, ketones or mixtures thereof. In one embodiment, the metal ion in the metal linker is at least one metal ion selected from the group consisting of Zn, Os, Ru, Fe, Pt, Pd, Ni, Ir, Rh, Co, Cu, Re, Tc, Mn, V, Nb, Ta, Hf, Zr, Cr, Mo, W, Ti, Sc, Ag, Au and Y.
[0340] In one embodiment, the metal ion coordinated organic complex comprises a polypyridyl complex represented by formula I as described herein below. In one embodiment, the metal ion coordinated organic complex comprises a polypyridyl complex represented by formula II as described herein above. Formula II with M=Fe is shown above herein. However, other transition metals can be the metal ion M in formula II above. For example and in one embodiment, the metal ion M in formula II is a transition metal selected from Mn, Fe, Co, Ni, Cu, Zn, Ti, C, Cr, Rh, Ru, Os or Ir.
[0341] In one embodiment, the metal ion coordinated organic complex comprises a polypyridyl complex represented by one of the following formulae, or a mixture of the following formulae, or a combination of the following formulae and molecules containing different metal centers or ligands (according to Formula I and Formula II): 1DB M=Fe, 2DB M=Fe, 1SB M=Fe, 2SBM=Fe, 1TB M=Fe, 2TB M=Fe. The structural formulae of these compounds are shown above herein. In one embodiment, the Fe ions in 1DB, 2DB, 1SB, 2SB, 1TB, 2TB shown above herein can be replaced by any other metal ion capable of undergoing oxidation / reduction reactions, such as transition metal ions selected from Mn, Co, Ni, Cu, Zn, Ti, Cr, Rh, Ru, Os or Ir.
[0342] In one embodiment, the metal linker is a mixture of metal linkers. In one embodiment, the polypyridyl complex is a mixture of polypyridyl complexes. In one embodiment, the step of applying at least one metal linker comprises applying the metal linker from a solution comprising the linker, and wherein the step of applying at least one metal-coordinated organic complex comprises applying the metal-coordinated organic complex from a solution comprising the metal-coordinated organic complex, and wherein the solution comprises a solvent selected from the group consisting of THF, alcohols, ethers, esters, halogenated solvents, hydrocarbons, ketones, or mixtures thereof. In one embodiment, the concentration of the linker in the solution and the concentration of the metal-coordinated organic complex in the solution are in the range between 0.1 mM and 10 mM.
[0343] Methods of using the device of the present invention
[0344] In one embodiment, the present invention provides methods of using the electrodes, capacitors, batteries and any other energy storage devices of the present invention.
[0345] In one embodiment, the present invention provides a method of using a capacitor of the present invention, the method comprising:
[0346] · independently connecting the first electrode and the second electrode of the capacitor to a power source;
[0347] charging the capacitor using the power supply;
[0348] Connecting the capacitor to a load;
[0349] discharging the capacitor through the load;
[0350] The charging and the discharging are accompanied by a color change of the first electrode.
[0351] In one embodiment, any portion or step of the method of use herein above is itself a method of using the capacitor of the present invention and is included in the method of the present invention.
[0352] In one embodiment, the color change is an indication of the charge / discharge level of the capacitor. In one embodiment, the capacitor is in a colorless state when charged, and the capacitor is in a colored state when discharged. In one embodiment, the colored state is a more stable state of the molecule, and the colorless state requires an applied potential. In one embodiment, the color change is detected by an optical detector. In one embodiment, "connection" means closing one or more switches in a previously assembled electronic circuit including a capacitor and a power supply.
[0353] In one embodiment, the device (capacitor / battery) of the present invention is used as a current indicator. In one embodiment, the electrochromic device (capacitor / battery / electrode) of the present invention is used as an optical gate.
[0354] In one embodiment, the use of the present invention comprises:
[0355] A device is provided, the device comprising:
[0356] o An electrochromic hybrid supercapacitor comprising:
[0357] A first electrode comprising an electrochromic film;
[0358] A second electrode;
[0359] an electrolyte in contact with the first electrode and the second electrode;
[0360] o a power source, optionally connected to the first electrode via a first electrical contact and to the second electrode via a second electrical contact;
[0361] o a load, optionally connected to the first electrode via a first electrical contact and to the second electrode via a second electrical contact;
[0362] optionally charging the device using the power source;
[0363] discharging the device through the load;
[0364] Detecting the charging / discharging of the device by detecting a color change of the device or a portion thereof
[0365] Discharge level.
[0366] In one embodiment, the device further comprises an optical detector for detecting the color change. In one embodiment, the color change is detected by the eye. In one embodiment, the device further comprises a light source to illuminate the color changing portion of the device (e.g., to illuminate the first electrode). In one embodiment, the device further comprises a processor for receiving an input signal from the optical detector. In one embodiment, the processor provides control signals to the device.
[0367] In one embodiment, the control signal is used to control at least one of the following: start charging, stop charging, start discharging, stop discharging. In one embodiment, the control signal is used to control at least one of the following: open circuit, close circuit, open switch, close switch.
[0368] In one embodiment, the devices of the present invention, including electrodes, batteries, capacitors and supercapacitors, can be used according to their function as components / components in any electronic circuit that requires such components / components. For example and in one embodiment, any electronic circuit that utilizes supercapacitors or capacitors can include supercapacitors / capacitors of the present invention. Any device that requires electrodes / batteries / capacitors or supercapacitors can utilize one or more of the electrodes / batteries / capacitors or supercapacitors of the present invention according to the needs of the device.
[0369] Method for preparing the EC film of the present invention
[0370] In one embodiment, the present invention provides a method of depositing multiple layers of electrochromic materials onto a substrate to produce a multilayer EC assembly. In embodiments of the present invention, the multilayer EC assembly is also referred to as an EC film or EC material or EC component or EC layer. For certain embodiments of the present invention, these terms are interchangeable.
[0371] In one embodiment, the present invention encompasses multilayer EC materials comprising molecules of metal polypyridyl complexes. In one embodiment, one type of complex is used. In another embodiment, two or more different metal polypyridyl complexes are present in the EC material of the present invention. The present invention also encompasses multilayer EC materials comprising a mixture of at least two metal polypyridyl complexes.
[0372] Without being limited by theory, it is believed that the metal linker is complexed with the polypyridyl compound to form a layer, wherein the metal linker can be complexed with a second polypyridyl compound to produce a multilayer EC assembly. The combination of the layer-by-layer principle and the spin-coating layering technique enables well-designed nanostructures. For example, it is shown that in one case, different layers consisting of Fe-polypyridyl-complexes and Pd metal linkers form a 3D coordination network with particularly advantageous properties. Figure 4 Schematic diagram of film formation by alternating deposition of metal linkers and polypyridyl complexes.
[0373] A method of the present invention produces EC materials with thermal and electrochemical robustness having very high contrast ratios (on / off ratios) in air. EC materials can be operated at low voltages and have practical switching times. Therefore, EC materials with very high on / off ratios, uniform coatings, low voltage operation, high electrochemical stability and durability (such as light and thermal durability), color versatility, and low switching times are useful in a variety of applications as described herein. In addition to the energy storage devices described above herein, multilayer EC materials have unique electrical properties that are suitable for applications such as smart windows, electrochromic windows, smart mirrors, optical filters, frequency doubling devices, spatial light modulators, pulse shapers, displays, signs, plastic electronic devices, lenses, sensors, to name a few. The method of the present invention can be used to form electrochromic coatings such as films.
[0374] As used herein, and unless otherwise defined, the term "high electrochemical stability" refers to the ability of an EC material to maintain a high %ΔT value, i.e., >90%, >95% or >97%, after at least 1000, but preferably more than 3,000, 5,000 or 10,000 electrochemical switching cycles when immersed in an electrolyte solution / exposed to an electrolyte gel / attached to a solid electrolyte over a period of hours to days and exposed to air and visible / UV light. In one embodiment, high electrochemical stability refers to the ability of the EC material to maintain high %ΔT values, i.e., >80%, >90%, >95%, or >97% or >99%, after at least 1000, but preferably more than 3,000, 5,000, 10,000 or 100,000 electrochemical switching cycles when immersed in an electrolyte solution or in contact with an electrolyte gel or solid electrolyte for a period of hours to years and exposed to air, extreme atmospheric temperatures, and visible / UV light.
[0375] In one embodiment, the EC material of the invention retains >90% of its initial value of contrast ratio after >1000 switching cycles.
[0376] The layer-by-layer (LBL) film construction method is a method based on the use of different kinds of interlayer interactions such as electrostatic interactions and hydrogen bonds for the purpose of adhering layers of different materials to each other to form a film. See, Ariga et al., Phys. Chem. Chem. Phys. 2007, 9 (19), 2319, which is hereby incorporated by reference. The LBL method involves the formation of a film by depositing alternating layers of materials, which are known to have some type of interaction between the layers of materials.
[0377] The inventors of the present invention have discovered that coordination interactions can be used as interactions between different layers deposited according to the LBL method. Coordination interactions have never been used for LBL assembly of material layers before. All previous methods are based on electrostatic interactions or hydrogen bonds as discussed above in this article. In one embodiment, only coordination interactions are used to attach different layers in the film of the present invention.
[0378] EC materials can be applied to substrates using a variety of deposition methods and techniques. The present invention encompasses a new method for preparing EC materials by applying linker metals and polypyridyl compounds using layer-by-layer (LBL) deposition. The new LBL process of the present invention can be used with any known deposition technique. For example, in various embodiments of the present invention, LBL film formation using coordination bonding is combined with roll-to-roll, dip coating, spin coating, spray coating, PVD, CVD, or a combination thereof.
[0379] In one embodiment, the LBL process of the present invention is combined with spin coating technology. LBL is used to produce films of two or more components. Therefore, in this embodiment, the deposition of EC materials onto the substrate is performed using a combination of LBL and spin coating technology.
[0380] The inventors have found that when LBL deposition of films comprising coordination interactions between layers is combined with spin coating techniques, very uniform films of a relatively wide range of thicknesses are quickly and easily fabricated. The combination of LBL and spin coating is particularly suitable for well-designed nanostructures.
[0381] In one embodiment, the present invention encompasses a method for preparing an EC material by applying a metallic connector and a polypyridyl compound or complex to a substrate using layer-by-layer (LBL) deposition combined with a spin coating technique. In particular, the method comprises preparing a multilayer EC material comprising different layers of at least one metallic connector layer and at least one polypyridyl complex layer by LBL and spin coating to form a 3D coordination network. The method encompasses providing a substrate, applying at least one metallic connector by spin coating, applying at least one polypyridyl complex by spin coating to form a layer, and optionally washing the layer with a solvent, optionally drying the layer, and repeating the application steps to obtain an EC material of a desired thickness.
[0382] The applying step should be performed for a sufficient amount of time to ensure application of the metal linker solution or pyridyl compound / complex.
[0383] Generally, methods of preparing EC materials encompass providing a substrate, applying at least one metallic linker to the substrate by spin coating, applying at least one polypyridyl compound or complex to the metallic linker by spin coating to produce a coated substrate, optionally washing the coated substrate, optionally drying the washed coated substrate, and repeating the application sequence to obtain an EC material of a desired thickness.
[0384] Typically, the step of applying the metal connector by spin coating requires applying a metal, metal salt, metal complex, or a combination thereof to the substrate, optionally in solution. Subsequently, the substrate may be rotated at a first suitable rate and for a first suitable time to obtain a uniform coating. In other embodiments, the substrate may be rotated first, and only while rotating is the metal connector or other material applied to the substrate.
[0385] If necessary, the substrate is rotated at a second suitable speed and a second suitable time. Typically, the first rotation speed is between 100rpm and 2000rpm, preferably the speed is between 400rpm and 1600rpm, and more preferably the first rotation speed is between 500rpm and 800rpm. Typically, the first rotation time is between 0.3 seconds and 60 seconds, preferably the first rotation time is between 5 seconds and 40 seconds, and more preferably the first rotation time is between 10 seconds and 20 seconds. Typically, the second rotation speed is between 200rpm and 3000rpm, preferably the speed is between 400rpm and 2000rpm, and more preferably the second rotation speed is between 600rpm and 1500rpm. Typically, the second rotation time is between 1 second and 120 seconds, preferably the second rotation time is between 15 seconds and 90 seconds, and more preferably the second rotation time is between 30 seconds and 60 seconds.
[0386] Without being bound by any theory, it is believed that programming the spin coating process in two steps allows for a distinction between two subsequent processes that occur during the spin: The first process is the spreading of the material and the attachment of the material to the substrate or layer on the substrate. This step requires a relatively long time and is therefore performed at a lower rate. The subsequent step involves the disposal of unattached molecules. This step requires a higher speed because physical adsorption must be overcome in order to dispose of unattached material.
[0387] Typically, the step of applying the polypyridyl compound or complex by spin coating requires applying the polypyridyl compound or polypyridyl metal complex to a substrate coated with a metal linker, optionally, these materials can be in solution. Suitable solvents for the solution include, but are not limited to, tetrahydrofuran, ether, dichloromethane, methanol, acetonitrile. Similar solvents can be used to dissolve / disperse the metal linker; for example, the PdCl2 linker is soluble in THF. However, depending on the metal linker and the metal complex, other solvents can be used as long as the metal linker or metal complex is dissolved or dispersed in such a solvent.
[0388] Substrate can rotate with the first suitable speed and continue the first suitable time, to obtain uniform coating.If necessary, with the second suitable speed and the second suitable time rotation substrate.In one embodiment, the first rotation rate is between 200rpm and 800rpm, and preferably the first rotation rate is between 400rpm and 600rpm, and more preferably the first rotation rate is about 500rpm.Usually, the first rotation time is between 1 second and 30 seconds, and preferably the first rotation time is between 5 seconds and 20 seconds, and more preferably the first rotation time is about 10 seconds.Usually, the second rotation rate is between 700rpm and 1300rpm, and preferably the second rotation rate is between 900rpm and 1100rpm, and more preferably the second rotation rate is about 1000rpm.Usually, the second rotation time is between 10 seconds and 60 seconds, and preferably the second rotation time is between 15 seconds and 45 seconds, and more preferably the second rotation time is about 30 seconds.
[0389] In one embodiment, the substrate includes, but is not limited to, a material selected from glass, doped glass, ITO-coated glass, FTO-coated glass, silicon dioxide, silicon, doped silicon, Si(100), Si(111), SiO2, SiH, silicon carbide mirror, quartz, metal, metal oxide, mixture of metal and metal oxide, IV group element, polydimethylsiloxane (PDMS) and related organic polymers / inorganic polymers, mica, organic polymers, plastics, zeolites, clay, wood, fabrics, films, optical fibers, ceramics, metallized ceramics, alumina, conductive materials, semiconductors, steel or stainless steel. Organic polymers include, but are not limited to, polyacrylamide, polystyrene and polyethylene terephthalate. The substrate can be in the form of beads, microparticles, nanoparticles, quantum dots, nanotubes, films, flat flexible surfaces or flat rigid surfaces. The substrate can also be optically transparent to ultraviolet (UV), infrared (IR), near IR (NIR) and / or other visible and invisible spectral ranges or portions thereof. Preferably, the substrate is a rigid support comprising ITO or FTO coated glass or a flexible support of ITO coated PET. More preferably, the substrate is selected from the group consisting of: ITO or FTO coated polyethylene terephthalate, ITO coated glass or quartz and FTO coated glass or quartz. Optionally, the substrate may include a template or a coupling layer.
[0390] Preferably, the substrate is transparent and has conductive properties. The substrate can be an n-type semiconductor with high carrier concentration, which results in low resistivity. In some embodiments, high transmittance in the visible region and near IR region of the electromagnetic spectrum due to a wide band gap is also a desired property of the substrate.
[0391] The metal used in the present invention includes those that can act as a metal connector between a substrate and a pyridyl compound or complex or between two pyridyl compounds or complex materials. In the latter case, the pyridyl complex can be the same or different. Typical metals include, but are not limited to, transition metals, lanthanides, actinides or main group elements. Transition metals include Zn, Os, Ru, Fe, Pt, Pd, Ni, Ir, Rh, Co, Cu, Re, Tc, Mn, V, Nb, Ta, Hf, Zr, Cr, Mo, W, Ti, Sc, Ag, Au and Y. Lanthanides include La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb or Lu. Actinides include Ac, Th, Pa, U, Np, Pu, Am, Cm, Bk, Cf, Es, Fm, Md, No or Lr. Main group elements include Zn, Ga, Ge, Al, Cd, In, Sn, Sb, Hg, Tl or Pb. Preferably, the metal is Pd. The metal can be used as a coordinated metal in a neutral state or an oxidized state. For example, Pd can be used as Pd or a complex based on Pd (II). An example of a complex based on Pd (II) is PdCl2 (PhCN)2. In addition, in one embodiment, the metal or metal complex is applied from a solution. Suitable solutions include, but are not limited to, ethers such as tetrahydrofuran and diethyl ether. Suitable metals and metal complexes and methods for preparing complexes can be found in PCT publication WO 2014 / 061018, which is hereby incorporated by reference. The metal in the metal-coordinated organic complex of the present invention can be any metal described above herein.
[0392] As used herein, unless otherwise defined, the term "pyridyl complex" refers to a metal having coordinated thereto one or more, for example two, three or four, pyridyl compounds.
[0393] The bipyridyl complex used in the present invention is typically a terpyridyl complex of formula (I) and formula (II) as described herein above.
[0394] One family of pyridyl complexes for use in the present invention are iron-based terpyridyl complexes of formula II as described herein above.
[0395] Formula II with M = Fe is shown above herein. However, other transition metals may replace the metal ion M in Formula II above. For example and in one embodiment, the metal ion M is a transition metal selected from Mn, Fe, Os, Ru, Co, Ni, Cu, Zn, Ti, C, Cr, Rh or Ir.
[0396] In Formula I and Formula II described herein above, X is a counterion and may be any suitable anion having a negative charge, such as -1 or -2. Counterions include, but are not limited to, Br - , Cl - 、F - ,I - PF6 - 、BF4 - 、BH4 - ,BPh4 - OH - 、ClO4 - 、NO3 - 、SO3 2- 、SO4 3- ,CF3OO - , CN - , alkyl COO - , aryl COO - 、Alkyl SO3 - 、Aryl SO3 - or a combination thereof. The value of "m" represents the ratio between the oxidation state of the metal and the valence of the anion. The value of "m" includes, but is not limited to, 0.5, 1, 1.5, 2, 2.5, 3, 4, 5, or 6.
[0397] In certain specific compounds, the terpyridyl complex is a complex of formula I, wherein M is Fe; n and m are each 2 or 3; X is PF6 - ; R1 to R 18 Each is H, and A1 to A6 are each independently a group of formula III, wherein R x is H; and (i) R 19 each is CC, that is, [tris[4,4'-bis(2-(4-pyridyl)ethyl)-2,2'-bipyridyl]iron(II)]bis(hexafluorophosphate) or [tris[4,4'-bis(2-(4-pyridyl)ethyl)-2,2'-bipyridyl]iron(III)]tris(hexafluorophosphate); (ii) R 19 each is C═C, that is, [tris[4,4′-bis(2-(4-pyridyl)vinyl)-2,2′-bipyridyl]iron(II)]bis(hexafluorophosphate) or [tris[4,4′-bis(2-(4-pyridyl)vinyl)-2,2′-bipyridyl]iron(III)]tris(hexafluorophosphate); or R 19 Each is C≡C, [tris[4,4'-bis(2-(4-pyridyl)ethynyl)-2,2'-bipyridyl]iron(II)]bis(hexafluorophosphate) or [tris[4,4'-bis(2-(4-pyridyl)ethynyl)-2,2'-bipyridyl]iron(III)]tris(hexafluorophosphate).
[0398] Other compounds include terpyridyl complexes of formula I, wherein M is Fe; n and m are each 2 or 3; X is PF6 - ; R1 in R 18 Each is H, and A1 to A6 are each independently a group of formula IV, wherein R y is H; and (i) R 19 each is CC, that is, [tris[4,4'-bis(2-(4-pyrimidinyl)ethyl)-2,2'-bipyridyl]iron(II)]bis(hexafluorophosphate) or [tris[4,4'-bis(2-(4-pyrimidinyl)ethyl)-2,2'-bipyridyl]iron(III)]tris(hexafluorophosphate); (ii) R 19 each is C═C, i.e., [tris[4,4′-bis(2-(4-pyrimidinyl)vinyl)-2,2′-bipyridyl]iron(II)]bis(hexafluorophosphate) or [tris[4,4′-bis(2-(4-pyrimidinyl)vinyl)-2,2′-bipyridyl]iron(III)]tris(hexafluorophosphate); or R 19 Each is C≡C, [tris[4,4'-bis(2-(4-pyrimidinyl)ethynyl)-2,2'-bipyridyl]iron(II)]bis(hexafluorophosphate) or [tris[4,4'-bis(2-(4-pyrimidinyl)ethynyl)-2,2'-bipyridyl]iron(III)]tris(hexafluorophosphate).
[0399] In certain specific compounds, the iron-based terpyridyl complex is a complex of formula II, wherein n and m are each 2 or 3; X is PF6 - ; R1 to R 18 Each is H, and A1, A3 and A5 are each independently a group of formula III, wherein R x is H; B1 to B3 are each methyl; and (i) R 19 each is CC, i.e., [tris[4'-methyl-4-(2-(4-pyridyl)ethyl)-2,2'-bipyridyl]iron(II)]bis(hexafluorophosphate) or [tris[4'-methyl-4-(2-(4-pyridyl)ethyl)-2,2'-bipyridyl]iron(III)]tris(hexafluorophosphate); (ii) R 19 each is C═C, i.e., [tris[4′-methyl-4-(2-(4-pyridyl)vinyl)-2,2′-bipyridyl]iron(II)]bis(hexafluorophosphate) or [tris[4′-methyl-4-(2-(4-pyridyl)vinyl)-2,2′-bipyridyl]iron(III)]tris(hexafluorophosphate); or R 19Each is C≡C, [tris[4'-methyl-4-(2-(4-pyridyl)ethynyl)-2,2'-bipyridyl]iron(II)]bis(hexafluorophosphate) or [tris[4'-methyl-4-(2-(4-pyridyl)ethynyl)-2,2'-bipyridyl]iron(III)]tris(hexafluorophosphate).
[0400] Other compounds include iron-based terpyridyl complexes of formula II, wherein n and m are each 2 or 3; X is PF6 - ; R1 to R 18 Each is H, and A1, A3 and A5 are each independently a group of formula IV, wherein R y is H; B1 to B3 are each methyl; and (i) R 19 each is CC, i.e., [tris[4'-methyl-4-(2-(5-pyrimidinyl)ethyl)-2,2'-bipyridyl]iron(II)]bis(hexafluorophosphate) or [tris[4'-methyl-4-(2-(5-pyrimidinyl)ethyl)-2,2'-bipyridyl]iron(III)]tris(hexafluorophosphate); (ii) R 19 each is C═C, i.e., [tris[4′-methyl-4-(2-(5-pyrimidinyl)vinyl)-2,2′-bipyridyl]iron(II)]bis(hexafluorophosphate) or [tris[4′-methyl-4-(2-(5-pyrimidinyl)vinyl)-2,2′-bipyridyl]iron(III)]tris(hexafluorophosphate); or R 19 Each is C≡C, [tris[4'-methyl-4-(2-(5-pyrimidinyl)ethynyl)-2,2'-bipyridyl]iron(II)]bis(hexafluorophosphate) or [tris[4'-methyl-4-(2-(5-pyrimidinyl)ethynyl)-2,2'-bipyridyl]iron(III)]tris(hexafluorophosphate).
[0401] Pyridyl compounds and complexes and methods for preparing them can be found in PCT publications WO 2015 / 075714 and WO2014 / 061018, which are hereby incorporated by reference. Preferred pyridyl moieties in the present invention include, but are not limited to, those represented by the following formulas, as described and represented above in detail herein: 1DB M=Fe, 2DB M=Fe, 1SB M=Fe, 2SB M=Fe, 1TB M=Fe, 2TB M=Fe. These formulas are shown above herein, where M=Fe. However, other transition metals may replace the metal ion M in Formula II above. For example and in one embodiment, the metal ion M is a transition metal selected from Mn, Fe, Os, Ru, Co, Ni, Cu, Zn, Ti, C, Cr, Rh or Ir.
[0402] A method of the present invention produces an EC material, such as a thin film, based on compound 1DB M=Fe or 2DB M=Fe, which is prepared by a method comprising providing a substrate, applying a palladium dichloride complex and a pyridyl complex (compound 1DB M=Fe or 2DB M=Fe or a mixture) in a stepwise manner using spin coating together with LBL to form a layer, optionally washing and drying the layer, and repeating the application steps until the EC material has the desired number of layers or thickness. The combination of spin coating and LBL is referred to as a single deposition cycle. The present invention encompasses a method of repeating deposition cycles to obtain an EC material having 2 to 40 layers, preferably 5 to 30 layers, and more preferably 10 to 20 layers. In a specific case, such as a film, the method includes 18 deposition cycles, wherein after each deposition cycle, the modified substrate is washed with acetone and dried under a flow of N2. The film manufacturing process occurs at ambient conditions.
[0403] In a specific embodiment, the method of the present invention includes providing a substrate, applying a metal linker complex solution by spin coating to form a metal linker layer, applying a pyridyl compound or complex by spin coating to form a pyridine-based layer, optionally washing the pyridine-based layer, optionally drying the washed pyridine-based layer, and repeating the applying steps to obtain an EC material having 2 to 80 layers.
[0404] The metal linker solution and the pyridyl compound or complex are described above. Typically, the rinsing (washing) step is performed with at least one volatile organic solvent. In one embodiment, such volatile organic solvents include those that can evaporate at room temperature. Typical volatile organic solvents include, but are not limited to, CH2Cl2, acetone, methanol, ethanol, THF, acetonitrile, and others.
[0405] Gases suitable for the drying step of the present invention include, but are not limited to, nitrogen, argon, helium, neon, xenon and radon. Preferably, the gas is nitrogen. Alternatively, the drying step may be air drying.
[0406] One embodiment of the present invention encompasses a method for preparing an EC material, the method comprising providing a substrate, applying at least one metal connector, applying at least one metal coordinated organic complex to form a layer, washing the layer, drying the layer, and repeating the applying steps to obtain a multilayer EC material.
[0407] In one embodiment, the metal organic complex comprises at least one functional group capable of binding to a metal linker. In one embodiment, the binding comprises a coordination bond between the functional group and the metal linker. In one embodiment, the metal complex is a polypyridyl complex. In one embodiment, "pyridyl" is short for "polypyridyl".
[0408] In one embodiment, the applying step comprises a deposition technique such as roll-to-roll, spin coating, dip coating, spray coating, physical vapor deposition (PVD), chemical vapor deposition (CVD), or a combination thereof. In one embodiment, the metal-coordinated organic complex comprises one or more isomers of the same compound. In one embodiment, the metal-coordinated organic complex comprises any mixture of isomers of the same compound. In one embodiment, the isomers are enantiomers. In one embodiment, the metal-coordinated organic complex comprises one or two enantiomers of the same compound. In one embodiment, the metal-coordinated organic complex comprises a mixture of the one or two enantiomers. In one embodiment, the enantiomeric mixture is a racemic mixture. In one embodiment, the applying step comprises spin coating.
[0409] In one embodiment, in the EC material of the present invention, no template or coupling layer is used or present between the substrate and the metal interconnect layer. In one embodiment, the layer application step is performed manually. In one embodiment, the layer application step is performed in a partially automated manner or in a fully automated manner. In one embodiment, automation of the layer application technique results in rapid manufacturing of the EC material.
[0410] The embodiments described herein with respect to polypyridyl complexes are also applicable to other metal-coordinated organic complexes. The embodiments described herein with respect to Pd metal linkers are also applicable to other metal linkers. The counterions in the metal-coordinated organic complexes of the present invention can be any counterions as known to those skilled in the art. In one embodiment, the layers in the assembly of the present invention are grown such that the thickness of each layer is the same or similar to the thickness of the other layers in the assembly. In other embodiments, a variety of layer thicknesses can be obtained for different layers in the EC material of the present invention.
[0411] Catalyst of the present invention
[0412] In one embodiment, the present invention provides a catalyst. In one embodiment, the present invention provides a catalyst for water decomposition. In one embodiment, the start of water decomposition can be monitored by a color change of at least a portion of the device. In one embodiment, the color change is caused by a change in the redox state of ions within the device. In one embodiment, the catalyst is used to convert water into H2 and O2. In one embodiment, the catalyst includes a multilayer comprising catalyst ions. In one embodiment, the catalyst ions are metal ions. In one embodiment, the metal ions are Pd ions. In one embodiment, the multilayer used as a catalyst for the water decomposition reaction includes an electrochromic entity. In another embodiment, the multilayer used as a catalyst for the water decomposition reaction does not include an electrochromic entity.
[0413] Data storage device / memory device of the present invention
[0414] In one embodiment, the present invention provides a data storage device. In one embodiment, the data storage device includes at least one redox center. In one embodiment, each redox center provides at least two states according to its oxidation state. In one embodiment, the charge of each state can be calculated. In one embodiment, each state is also characterized by a specific color. According to this aspect and in one embodiment, each state has a different color and requires a different amount of charge to be set. According to this aspect and in one embodiment, the data storage device can be set to a specific state by electrochemical means, and the state can be evaluated or read using charge calculation (by electrochemical means) or using optical detection. In one embodiment, when more than one redox center is included in the device, so that two or more centers are different in their oxidation state and / or in their color and / or in the metal ion used, the color of the device can be a combination of the colors of each redox center. Therefore, in one embodiment, two different redox centers each having two oxidation states can result in a device comprising three different device states. Each state is characterized by a different color and can be achieved using a specific amount of charge. In some embodiments, the device is based on an organic multilayer comprising metal ions, wherein at least a portion of the metal ions in the multilayer can present more than one oxidation state. In some embodiments, the data storage devices described herein are referred to as memory devices. Embodiments described herein below with respect to metal-organic multilayers may be applicable to embodiments of data storage devices / memory devices comprising such multilayers or similar multilayers as described herein above.
[0415] definition
[0416] As defined herein, in a metal-coordinated organic complex, a metal ion is coordinated to at least one organic molecule (ligand). In some embodiments, a metal-coordinated organic complex is referred to as a "metal complex". In some embodiments, a metal-coordinated organic complex is referred to as a "metal ion-coordinated organic complex". Similar names are used in embodiments of the present invention, including metal ion-coordinated organic complexes, metal ion organic complexes, organic complexes, and metal-organic complexes.
[0417] In some embodiments, the EC material is referred to as an EC component, an EC layer, an EC film. In embodiments of the present invention, these terms are interchangeable.
[0418] The term supercapacitor defines or describes the properties of a capacitor. When compared to a capacitor, a supercapacitor generally has a higher specific energy, but a lower specific power.
[0419] Compared to batteries, capacitors have a smaller energy density. However, capacitors can be charged / discharged much faster than batteries. Supercapacitors are devices that can be described as bridging the gap between capacitors and batteries. The range of specific energy and specific power of supercapacitors is between the range of specific energy and specific power of batteries and the range of specific energy and specific power of capacitors (although there may obviously be some overlap). When compared to capacitors, supercapacitors can accumulate more energy. However, their charge / discharge rate is slower. When compared to batteries, supercapacitors can accumulate less energy, but can be charged / discharged faster. This description of supercapacitors is obvious from the Ragone diagram of power density relative to energy density (or specific power relative to specific energy) as known in the art. The Ragone diagram shows the amount of energy available per unit mass relative to how fast the energy can be delivered.
[0420] The term "hybrid supercapacitor" refers to a hybrid of two electrodes with different energy storage mechanisms: one is a battery-type electrode and the other is a capacitive (capacitor-like) electrode. The battery-type electrode or battery-like electrode or battery-type electrode is an electrochemical electrode. In an embodiment of the present invention, the capacitive electrode is an electrostatic electrode.
[0421] In certain embodiments of the present invention, the term "power supply" may be interchangeable with power supply, current source, voltage source, voltage supply, current supply, and other similar terms as known in the art.
[0422] In embodiments of the present invention, silicon dioxide and silicon oxide are interchangeable.
[0423] In the embodiments of the present invention, 'conductive' means electrically conductive. The unit second is abbreviated as 's', but in some embodiments, it is also referred to as 'sec'.
[0424] In one embodiment, 'active material' refers to an electrode material, such as PPC and / or a metal ion coordinated organic complex. In one embodiment, an active material is a material that donates / accepts electrons during charge or discharge.
[0425] In one embodiment, the metal ion complex and layers comprising the metal ion complex serve as or are referred to as 'hole storage layers' or hole storage materials. In one embodiment, the capacitive (second) electrode (eg, electrode comprising PPC) is referred to as or serves as an electron storage layer.
[0426] In one embodiment, the metal link is referred to simply as 'link'. Oxidation / reduction is sometimes abbreviated as ox / red. The load may be referred to as a power consumer. Some embodiments described herein with respect to conductive oxides are applicable to any conductive material (not limited to oxides) and are included in the present invention.
[0427] In one embodiment, the electrochromic material comprises a metal ion organic complex.
[0428] In some embodiments, the abbreviation 'dec' means 'ten' and is used, for example, in the figures to describe ten, ie, 10.
[0429] In one embodiment, the present invention provides a battery. In one embodiment, the present invention provides a power source, a current generator, or a combination thereof. The embodiments described herein with respect to a battery are applicable to and included in the power source / current generator of the present invention in some embodiments, and in some embodiments, in the preparation and use thereof.
[0430] In one embodiment, 'transmittance' refers to optical transmittance as known in the art.
[0431] In one embodiment, the term "a" or "one" or "an" refers to at least one. In one embodiment, the phrase "two / two or more / more" may be any designation that will suit a particular purpose. In one embodiment, "about" or "approximately" may include a deviation of +1% from the indicated term, or in some embodiments a deviation of -1%, or in some embodiments a deviation of ±2.5%, or in some embodiments a deviation of ±5%, or in some embodiments a deviation of ±7.5%, or in some embodiments a deviation of ±10%, or in some embodiments a deviation of ±15%, or in some embodiments a deviation of ±20%, or in some embodiments a deviation of ±25%.
[0432] Although certain features of the present invention have been illustrated and described herein, many modifications, substitutions, changes and equivalents will now occur to those skilled in the art. Therefore, it should be understood that the appended claims are intended to cover all such modifications and changes as fall within the true spirit of the invention. Example
[0433] Example 1
[0434] Film fabrication and characterization of EC materials
[0435] 1.1 Base
[0436] Of the various transparent conductors available and used in the electrochromic (EC) field and included in embodiments of the present invention, transparent conductive oxides (TCOs) are the most common transparent conductors. However, alternatives to TCOs can also be found. For example, thin metal sheets (e.g., silver or gold); graphene and carbon nanotubes.
[0437] The two most common TCOs used for both research and industrial purposes are indium tin oxide (ITO) and fluorine-doped tin oxide (FTO). Typically these TCOs are deposited on glass, but in the plastic electronics industry, ITO can also be deposited on flexible substrates such as polyethylene terephthalate (PET). These TCOs are included in embodiments of the present invention.
[0438] ITO substrates are widely used due to the fact that they combine unique transparent properties and conductive properties. It is an n-type semiconductor with a high carrier concentration, which results in a low resistivity. In addition, due to its wide bandgap, ITO shows high transmittance in the visible and near IR regions of the electromagnetic spectrum ( Figure 1 ).
[0439] FTO substrates are also widely used, mainly for energy-saving windows in architectural applications. FTO is also an n-type semiconductor with a large band gap, which allows it to be transparent in the visible light range ( Figure 1 ). Among the many advantages of FTO, the following two play a crucial role when considering it as a replacement for ITO: (1) The increasing scarcity of indium leads to the higher cost of ITO. (2) FTO has a rougher surface relative to ITO, which results in a higher surface area (Figure 2). AFM measurement results show that for FTO, the roughness value is 0.8nm, and for ITO, the roughness value is 0.2nm.
[0440] In the following examples, the following substrates were used: FTO and ITO coated glass substrates, ITO coated polyethylene terephthalate (PET) substrates. For each substrate, a suitable cleaning procedure was developed. The clean substrates were kept in a sealed and dark container until further use. It should be noted that other transparent conductive substrates can be used to support the EC materials of the present invention. As known to those skilled in the art, other cleaning procedures can be used to prepare the substrates of the present invention for use.
[0441] 1.2 Deposition methods and techniques
[0442] EC materials can be applied to any of the substrates described above in a variety of deposition methods and techniques. Among the different methods, the following two are the most common: a one-step method - common mainly in the manufacture of polymer-based films; and a layer-by-layer (LBL) method - common mainly when the film is composed of two or more components. There are a variety of techniques that can be combined with each of the two deposition methods described. As examples, roll-to-roll, spin coating, dip coating and spray coating, as well as PVD and CVD techniques can be considered.
[0443] LBL deposition is a well-studied method that exploits various types of interlayer interactions, such as electrostatic interactions and hydrogen bonding. The present inventors have found that when combined with spin coating techniques, very uniform films with a relatively wide range of thicknesses can be quickly and easily produced.
[0444] In this example, this combination of LBL method and spin coating is used as a fabrication technique in order to achieve a well-designed nanostructure. The different layers consist of Fe complexes (compounds 1DB M=Fe or 2DB M=Fe, see Figure 3 ) and Pd linker to form a 3D coordination network. In this embodiment, the benzonitrile ligand of the PdCl2(PhCN)2 linker complex is relatively weakly coordinated to the Pd metal center and is therefore easily replaced by the pyridine binding site of the polypyridyl complex. The film based on compound 1DB or 2DB is manufactured in a step-by-step manner mediated by palladium dichloride, which coordinates the pyridyl part of different building blocks. The manufacturing process includes alternately depositing a solution of PdCl2(PhCN)2 and a polypyridyl complex (1DB or 2DB) using a spin coating LBL method. These two subsequent steps are referred to as a single deposition cycle. The film consists of 18 deposition cycles, wherein after each deposition cycle, the modified substrate is washed with acetone and dried under a N2 flow. The manufacturing process of the film occurs at ambient conditions. However, other temperature / pressure conditions can be used for the manufacturing process. In some embodiments, the film is labeled in the following manner: (pyridyl complex type│number of deposition cycles│substrate type). For example, (Compound 1DB M = Fe|18|FTO / glass).
[0445] In this embodiment, as described in the above procedure, the first deposition step is a palladium dichloride connector. The interaction between the Pd connector and the substrate was studied to determine whether this is a simple physical absorption or a coordination interaction between Pd and the substrate. Previous work has described the affinity of Pd (II)-based complexes to oxide substrates such as silicon dioxide and aluminum oxide through the coordination of Pd with hydroxyl groups on the surface. However, there is no literature to find the absorption of Pd (II)-based complexes on ITO or FTO. In previous studies, a coupling layer and a template layer were used to attach the Pd connector to the substrate. However, the connecting layer has an electrical isolation property, and therefore it affects the electrochemical properties of the film.
[0446] Control experiments were designed to evaluate whether a coupling layer and a template layer between the substrate and the metal connector are required in the case of a spin coating manufacturing process, or whether Pd can be directly attached to the substrate using this technology. Additional experiments were designed to evaluate whether Pd is indeed required for the pyridyl complex layer growth process. In the first two control experiments, the substrate was modified with a coupling layer and a template layer (according to known procedures), and the film was constructed with and without Pd as a connector. In the other two control experiments, the substrate was not modified, and the film was constructed again with and without Pd. The results of these experiments are that effective growth is obvious only in the experiments using Pd. It is concluded that film growth is not based on physical absorption, but on coordination between layers mediated by Pd. In addition, since there is no difference in the growth of the film on the modified substrate relative to the growth on the unmodified substrate, it can be concluded that Pd can be directly attached to the substrate.
[0447] It should be noted that other metal-coordinated organic compounds can be used as metal-coordinated organic complexes, and other metal linkers or other metal linker complexes can be used as metal linkers. Metal-coordinated organic complexes can include other polypyridyl compounds, other complexes containing functional groups other than pyridine, compounds containing both pyridine functional groups and non-pyridine functional groups, linkers containing metals other than Pd, linkers containing other ligands, etc.
[0448] To reinforce the above, and also to test whether Pd is present after further deposition steps, XPS measurements were performed in which the ratio between Pd and Fe was tested. The measurements were performed on films deposited on FTO on glass substrates with different deposition cycle numbers in order to show that the growth is uniform. The results are presented in Table 1:
[0449]
[0450] *The average value between two points
[0451] Table 1. Pd / Fe ratios in films deposited on FTO / glass substrates constructed with different numbers of deposition cycles as extracted from XPS measurements. The expected value for a fully formed network is 1.5.
[0452] In a fully coordinated network, the ratio between Pd and the metal center Fe is calculated to be 1.5 Pd atoms per Fe atom (three Pd atoms coordinated for each complex, each Pd atom shared between two complexes). However, the above results show an average Pd / Fe ratio of 2.8 ± 0.3, which means that Pd is excessive. This shows a porous film structure with embedded Pd atoms between layers. In addition, the uniformity of the film can be seen from the results because the ratio remains unchanged as the number of deposition cycles increases. Without being bound by any theory, it is believed that the embedded atoms are those atoms that are not coordinated with the metal complex in the assembly. These atoms exceed the atoms required to be connected between the complexes / layers by coordination bonds. As mentioned above, the results show that the film is uniform because the ratio remains unchanged as the number of deposition cycles increases.
[0453] The films were characterized by UV / vis spectroscopy, X-ray photoelectron spectroscopy (XPS), cyclic voltammetry (CV), chronoamperometry (CA) and spectroelectrochemistry (SEC). The surfaces of the films were characterized by scanning electron microscopy (SEM), atomic force microscopy (AFM) and optical microscopy.
[0454] 1.3 Membranes on rigid supports—fabrication and characterization
[0455] 1.3.1ITO / Glass
[0456] As described above, ITO substrates have unique transparent and conductive properties. These are substrates with low resistivity and high transmittance in the visible and near IR regions of the electromagnetic spectrum.
[0457] According to the described film fabrication method, compound 1DB M=Fe was deposited on an ITO substrate. Compound 1DB M=Fe has a characteristic metal-to-ligand charge transfer (MLCT) band at λ=578 nm, which increases linearly with the number of deposition cycles ( Figure 5A-Figure 5B ). This growth trend indicates that the same amount of material is deposited in each deposition cycle.
[0458] The modified ITO substrate was used as the working electrode, Pt wire as the counter electrode and Ag / Ag + The electrochemical and spectroelectrochemical properties of the membranes were evaluated in solution using a three-electrode cell configuration with a reference electrode. The CV measurements of the membranes showed that Fe +2 / Fe +3 The reversible redox process of Figure 6 ).
[0459] The oxidation and reduction processes occurring in the film can be detected using spectroscopy: when the film is oxidized, the intensity of the MLCT band decreases significantly, resulting in decolorization, while when it is reduced, the film appears purple. The SEC experiment is performed by applying a double potential step as a function of time and recording the optical response at λ = 578nm as a percentage of transmittance (%T) over time. Double potential step chronoamperometry is a technique in which the potential of the working electrode is stepped forward for a specified period of time and then stepped backward for a specified period of time. The current is monitored and plotted as a function of time. The results show a very high transmittance difference (i.e., contrast ratio) of 54% between the oxidized and reduced states. In addition, even after 160 switching cycles, the film was able to maintain 95% of its maximum contrast ratio.
[0460] 1.3.2FTO / Glass
[0461] According to the described film fabrication method, films with two Fe-complexed compounds 1DB and 2DB were fabricated on FTO / glass substrates. Both films exhibited linear growth with respect to the number of deposition cycles. Compound 1DB M=Fe had a characteristic MLCT band at λ=578nm, which resulted in a purple color, while compound 2DB M=Fe had two distinct MLCT bands at λ=452nm and λ=598nm. The combination of these two bands resulted in a black ( Figure 8A-8B ).
[0462] As the number of deposition cycles increases, the MLCT band increases linearly for both compounds ( Figure 9A-9D). This finding contradicts previous results on these compounds, in which exponential growth was observed for films based on compound 1DB M=Fe grown using dip coating. The difference is that in this example, the film is deposited on a bare substrate, whereas previously it was deposited on a modified substrate. In addition, the deposition method is different (spin coating versus dip coating), which greatly affects the growth trend. In previous work, the EC assembly was deposited on a substrate modified with a template layer using a dip coating deposition method. Using this method, it was found that Pd atoms were temporarily stored and subsequently released, which resulted in an increase in the growth rate and, therefore, an exponential dependence of the absorbance on the number of deposition cycles. In contrast, in one embodiment, the EC assembly deposited using the method of the present invention was deposited on an unmodified substrate. In addition, there was no evidence of delayed release of Pd atoms, and therefore no increase in the growth rate, which resulted in a linear dependence of the absorbance on the number of deposition cycles. Such linear growth of the layer is important in view of applications requiring controlled deposition and uniform layer thickness. Such linear growth enables simple design of layered materials, where the thickness of each layer can be controlled and can be made identical, equivalent, or have a constant thickness ratio relative to the thickness of other layers in the structure.
[0463] Electron microscopy was used to characterize the surface and structure of the film based on compound 1DB M=Fe. The surface area of the film was sampled using optical microscopy and AFM. Both methods showed a granular, uniform surface ( Figure 10A-10B ). The roughness of the film was found to be as high as 40 nm (about one tenth of the film thickness). In addition, a cross section of the film was obtained by milling the film using a focused ion beam (FIB). The cross section was then characterized using SEM, showing the different regions of the film: the glass support, the FTO layer, the film based on compound 1DB M=Fe, and a thin layer of Pt to prevent damage to the film while milling was performed ( Figure 11A-11B The film thickness was found to be 400nm-500nm. The surface of the film was also characterized by SEM and correlated with the findings described above. Fig. 11C ).
[0464] The same fabrication method was used to fabricate membranes of different sizes ( Fig.12 ). A uniform film with identical optical and electrochemical properties was obtained.
[0465] Stability to light and high temperature is one of the characteristics that EC materials should possess. Two samples of films containing compound 1DB M=Fe were tested: one was kept exposed to sunlight and the other was kept at 100°C. Both experiments lasted for more than 120 days and are still running. The results were obtained by UV / vis absorbance. Fig.13 An initial slight decrease in absorbance followed by stabilization is shown for both samples.
[0466] 1.3.2.1 Electrochemical properties of compound 1DB M=Fe
[0467] Electrochemical and spectroelectrochemical properties of films containing compound 1DB M=Fe were investigated using modified FTO substrates, Pt wires, and Ag / Ag + The CV measurements of the membranes showed that the Fe +2 / Fe +3 The reversible redox process of Fig.14 ). In addition, the membrane cycle continued for 2000 redox cycles with a slight decrease in current (<2%). Figure 15A-15B ).
[0468] The oxidation and reduction processes occurring in the membrane can be detected using spectroscopy: when the membrane is oxidized, the intensity of the MLCT band decreases significantly, resulting in achromatism, whereas when the membrane is reduced, it has a purple ( Figure 8A-8B ).
[0469] SEC experiments were performed by applying double potential steps as a function of time and recording the optical response at λ = 578 nm as percent transmittance (%T) over time ( Fig.17 ). The results showed a very high contrast ratio of 61%. Furthermore, even after 800 redox cycles, the film was able to maintain 95% of its maximum contrast ratio.
[0470] The contrast ratio can vary as a function of the switching time: when the switching time is short, the contrast ratio is low. However, even for switching times in the sub-second range, the contrast ratio is still relatively high when compared to equivalent systems ( Figure 18A-18B ).
[0471] The switching efficiency is defined as the time taken to obtain 95% of the maximum contrast ratio. It teaches the time taken for the system to react to the applied potential. The film based on compound 1DB M=Fe exhibited a switching time of 1.92 seconds for oxidation and 1.48 seconds for reduction ( Fig.19 ).
[0472] The electron transfer process can be elucidated by transient response studies, such as by cyclic voltammetry at different scan rates ( Figure 20A-20C). CVs were recorded at different scan rates and the results obtained differ from those known for monolayer systems: the results show an exponential dependence of the current on the scan rate, as well as a linear dependence of the current on the scan rate root. These trends, indicating a diffusion-controlled process, differ from those known for monolayer systems or from those seen in previously studied dip-coating systems. However, these trends are consistent with systems with polymer films of comparable thickness.
[0473] Measuring the electrochemical and spectroelectrochemical properties at different deposition cycles gave information about the structure and internal organization of the films (Fig. 21-Fig. 23).
[0474] 1.3.2.2 Electrochemical properties of compound 2DB M=Fe
[0475] Electrochemical and spectroelectrochemical properties of films containing compound 2DB M=Fe were investigated using modified FTO substrates, Pt wires, and Ag / Ag + The CV measurements of the membranes showed that the Fe +2 / Fe +3 The reversible redox process of Fig.24 ).
[0476] The oxidation and reduction processes occurring in the film can be detected using spectroscopy: when the film is oxidized, the intensity of the MLCT band decreases significantly, resulting in achromatism, whereas when the film is reduced, it has a black ( Fig.25 ).
[0477] The SEC experiments were done by applying double potential steps as a function of time and recording the optical response at λ = 598 nm as a percentage of transmittance (%T) over time. The results showed a contrast ratio of 33%. Furthermore, even after 1000 redox cycles, the film was able to maintain 95% of its maximum contrast ratio ( Fig.26B ).
[0478] 1.3.2.3 Electrochemical characteristics of hybrid systems
[0479] The previous subchapter described membranes based on individual systems of either compound 1DB M=Fe or compound 2DB M=Fe. This chapter presents membranes based on a mixed system of these two compounds. The motivation behind mixing these two compounds comes from the fact that the system based on compound 1DB M=Fe is more opaque (based on its contrast ratio, see Figure 16-17 ), while the system based on compound 2DB M=Fe is more stable and has a black color, which is a color of interest to the EC industry. Therefore, in some embodiments, the combination of the two compounds enhances the overall electrochromic performance of the system.
[0480] The mixing of the two components into one system can be obtained in several ways: by alternating deposition of each compound, by alternating deposition of one layer of each compound, or by deposition in a block configuration: blocks of one compound followed by blocks of the other. In the latter approach, the size of the blocks can be equal or can vary, favoring one compound over the other. The size of each block can be controlled by the number of deposition cycles of each block.
[0481] Another way of deposition is by using a mixed solution of the two compounds in equal or different concentrations. The latter two systems (bulk and mixed solution) were fabricated using the fabrication method disclosed herein.
[0482] The fabrication process using mixed solutions involved alternating deposition of a solution of PdCl2(PhCN)2 and a solution of a mixture of Fe polypyridyl complexes (equal amounts of compounds 1DB M=Fe and 2DB M=Fe). Bulk deposition utilized separate solutions of each complex. Both methods rely on the use of a spin-on-LBL approach. In this example, 18 deposition cycles were fabricated and the growth trend was found to be linear based on UV / vis absorption, similar to the separate system using only one complex ( Figure 27A-27F ).
[0483] Electrochemical and SEC analysis showed a higher contrast ratio for the bulk system, however the mixed system appeared to be the darkest when considering the color obtained ( Figure 28A-28C , Figure 29A-29F , Figures 30A-30D ).
[0484] 1.4 Films on Flexible Supports—Fabrication and Characterization
[0485] The demand for flexible EC films has emerged in the past few years due to their potential applications in the electronics industry, such as flexible displays. This type of film is also interesting because it can allow the EC film to be installed on existing structures, which will reduce production costs compared to newly formed structures.
[0486] In this example, the ITO / PET substrate (10 ohm / cm 2) is purchased commercially. As described above, ITO has unique transparent and conductive properties, which result in low resistivity and high transmittance. When deposited on PET, a flexible transparent electrode is obtained. The ITO / PET substrate is cleaned before further deposition steps. The cleaning procedure involves rinsing with ethanol and then immersing in acetone. The substrate is dried under a stream of air. According to the described film fabrication method, compound 1DB M=Fe is deposited. As disclosed herein, compound 1DB M=Fe has a characteristic metal to ligand charge transfer (MLCT) band at λ=578nm, which increases linearly with increasing number of deposition cycles. ( Figure 31A-Figure 31B ).
[0487] The electrochemical and spectroelectrochemical properties of the films were investigated using modified ITO / PET substrates, Pt wires, and Ag / Ag + The silk was evaluated in a three-electrode cell configuration consisting of the working electrode, counter electrode, and reference electrode. The membrane was maintained in both the unbent and bent configurations. The CV measurements of the unbent membrane showed that the Fe +2 / Fe +3 The reversible redox process of Fig.32 ). In addition, the membrane cycle continued for 1500 redox cycles with a slight decrease in current (<2%) ( Figure 33A-Figure 33B ).
[0488] 1.5 Solid-state / laminated electrochromic devices
[0489] In some embodiments, for real-time applications, the EC film should be incorporated in a solid configuration. The basic structure of an electrochromic device (ECD) consists of two EC layers separated by an electrolyte layer. ECDs can be divided into two main categories: all-solid-state ECDs, in which the electrolyte is a solid organic layer or inorganic layer (not a liquid or gel); and laminated ECDs, in which the electrolyte is a liquid gel. In some embodiments, laminated ECDs are also considered "solid-state systems". Many parameters may affect the performance of the device: the conductivity of the electrodes, the type and size of the spacer, the type and composition of the electrolyte, and the packaging and sealing of the device. Due to the many influencing parameters, a long optimization process is required in order to manufacture a device with good performance. Another major challenge is the lifetime of the device, because the device tends to degrade with increasing number of redox cycles.
[0490] In this example, an ECD was constructed by sandwiching [compounds 1DB and 2DB│18│FTO / glass] and bare FTO with an electrolyte gel between the two electrodes. The contacts were made of silver paste or copper tape, and the spacing between the two electrodes was achieved by introducing a 50 μm double-sided tape. The electrochemical behavior of the ECD was analyzed using cyclic voltammetry and chronoamperometry.
[0491] The electrochemical and spectroelectrochemical properties of the device based on the membrane containing compound 1DB M=Fe were evaluated by applying a double potential step between (-2.5V) and (3V). The potential window required for the operation of such a device is larger than that required for the membrane in the electrolyte solution, due to the fact that in the solid configuration, the viscosity of the (gel) electrolyte is higher, which leads to a higher resistance. The SEC experiments were performed by applying the potential as a function of time and recording the optical response (MLCT band peak) at λ=571nm as the percentage transmittance over time (%T). The results showed a high contrast ratio of 50%. In addition, even after 100 redox cycles, the membrane was able to maintain 95% of its maximum contrast ratio.
[0492] The kinetics of the redox process was tested in the following manner: a suitable potential (e.g., 3 V) was applied, which resulted in the decolorization of the device. This was followed by the potential being switched off and the circuit being disconnected. The device then began to return to its stable state, e.g., colored state, reduced state. Based on the exponential decay of the percent transmittance (%T) over time, the rate of color change was calculated and found to be 0.032 seconds. -1 ( Fig.37 ).
[0493] The same manufacturing method is used to make devices of different sizes. For complete switching of larger devices, longer switching times are required. For example, Figure 38A-Figure 38B The dimensions of the electrochromic device are shown, ( Fig.38A )4 cm x 4 cm device; and ( Fig.38B ) 6 cm×6 cm device, where the working electrode is [1DB M=Fe│18│FTO / glass], the counter electrode is a bare FTO substrate, and the electrolyte is a PMMA-based gel.
[0494] 2. Materials and Methods
[0495] Solvents (AR grade) were purchased from Bio-Lab (Jerusalem), Frutarom (Haifa) or Mallinckrodt Baker (Phillipsburg, NJ). Fluorine-doped tin oxide (FTO)-coated glass substrates (6 cm × 6 cm) and indium tin oxide (ITO)-coated polyethylene terephthalate (PET) substrates were purchased from Xinyan Technology LTD (Hong Kong, China). ITO-coated glass substrates (6 cm × 6 cm) were purchased from Delta Technologies (Loveland, CO). ITO and FTO substrates were cleaned by sonication in ethanol for 10 min, dried under N2 flow, and then cleaned with UV and ozone in a UVOCS cleaning system (Montgomery, PA) for 20 min. The slides were then rinsed with tetrahydrofuran (THF) and dried under N2 flow and 130°C for 2 h. ITO-coated PET substrates were cleaned by immersion in ethanol and acetone, then dried under N2 flow. UV / vis spectra were recorded on a Cary 100 spectrophotometer (200nm-800nm). The modified substrate was fixed in a Teflon holder and a suitable clean substrate was used to compensate for background absorption. All measurements were performed at room temperature. Electrochemical measurements (cyclic voltammetry (CV), chronoamperometry (CA) and spectroelectrochemistry (SEC)) were performed using a potentiostat (CHI660A or CHI660E). The layer-by-layer deposition step was performed using a Laurell spin coater model of WS-400A-6NPP / LITE.
[0496] 3. Multilayer formation
[0497] A drop of 3.0mM PdCl2(PhCN)2 in THF is cast on a FTO substrate, which is loaded on a spin coater platform. The substrate is rotated at a speed of 500 revolutions per minute (rpm) for 10 seconds, then at a speed of 1000rpm for 30 seconds. Subsequently, a drop of 0.6mM EC compound (compound 1DB M=Fe or 2DB M=Fe) in DCM / methanol (1:1, v / v) is cast on the substrate, and rotated according to the same procedure. The substrate is immersed in acetone for 1min, and dried under N2 flow. UV / vis absorption spectra are recorded after each deposition cycle.
[0498] 4. Solid-state settings
[0499] (a) Preparation of electrolyte gel: 70:20:7:3 wt% polymethyl methacrylate (PMMA, 700 mg), trifluoromethylsulfonamide lithium salt (300 mg), dry acetonitrile (7.0 g, ~8.9 mL) and dry propylene carbonate (2.0 g, 1.7 mL) were added to a glass container in a N2-filled glove box and stirred vigorously for 24 h to give a uniform cast electrolyte solution. (b) Device fabrication: Cut a frame of 50 μm-100 μm double-sided tape and stick it on a film slide, leaving an edge for silver paste or copper tape contact. The edges of the bare FTO substrate are also covered with silver paste or copper tape. The bare substrate is placed on top of the film slide in such a way that the two conductive surfaces of the substrate face each other. The sides of the device are sealed using epoxy glue or UV curable glue. Finally, the electrolyte gel is injected between the two substrates using a syringe.
[0500] 5. Electrochemistry in Solution
[0501] The electrochemical behavior of the membranes was tested in a 0.1 M solution of tetrabutylammonium hexafluorophosphate (TBAPF6) in ACN by CV, CA, and SEC. + The measurements were performed in a three-electrode cell configuration consisting of (a) Pt (reference electrode) and (b) Pt wire (counter electrode).
[0502] 6. Solid-state electrochemistry
[0503] The electrochemical behavior of the electrochromic device (ECD) was measured by CA and SEC, which were performed by applying a potential window between -2.5 V and 3 V with a time interval of 4 s.
[0504] 7. Additional Experiments on the Mixed Layer Deposition System
[0505] As discussed above, mixing the two components into one system can be obtained in a number of ways: alternating deposition of each compound, deposition in a block configuration: blocks of one compound followed by blocks of the other. In block deposition, the size of the blocks can be equal or can vary, favoring one compound over the other. Another deposition scheme involves depositing a mixed solution of the two compounds at equal or different concentrations. Such a mixed layer system was fabricated using the described fabrication method comprising LBL and spin coating. The fabrication process involved alternating deposition of a 3 mM solution of PdCl2(PhCN)2 in THF and an equimolar solution of Fe-polypyridyl complexes 1DB M=Fe and 2DB M=Fe (0.3 mM each) in 1:1 DCM:methanol using our spin coating LBL method. These two subsequent steps (Pd linker and Fe complex) are referred to as a single deposition cycle. The membrane consisted of 18 deposition cycles, wherein after each deposition cycle, the modified substrate was washed with acetone and dried under a flow of N2. The fabrication process of the membrane was carried out under ambient conditions.
[0506] Compound 1DB M=Fe has a characteristic MLCT band at λ=578nm, while compound 2DB M=Fe has two distinct MLCT bands at λ=452nm and λ=598nm. The combination of these two compounds produces an MLCT band at λ=589nm, which increases linearly with the number of deposition cycles ( Figure 39A-Figure 39B ).
[0507] Electrochemistry in solution
[0508] Using modified ITO / PET substrate as working electrode, Pt wire and Ag / Ag + The electrochemical properties of these systems deposited on ITO / PET 60ohm / sq were evaluated in a three-electrode cell configuration consisting of silk as counter and reference electrodes, respectively. Chronoamperometry and cyclic voltammetry were measured in order to test the durability of the membrane to bending: the membrane was measured when it was upright, then when it was bent with a radius of curvature of 2.5 cm, and finally when the membrane returned to upright. Electrochemical switching was performed by applying (-0.5V) for 4 seconds and (2V) for 8 seconds for several cycles, while recording CVs at a scan rate of 0.05V / sec in a potential window of 0V-2V. The results did not show significant differences when the membrane was measured before or after bending, as shown in Figure 2. Fig.40 and Fig.41 Displayed.
[0509] Fig.42The photographs in show the colored and decolorized states of such a 1 cm×6 cm device, where (left) the film is upright and (right) the film is bent with a curvature radius of 2.5 cm. Electrochemical switching was performed by applying −0.5 V for 4 sec and 2 V for 8 sec for several cycles. Fig.43 Schematic diagram of a flexible electrochromic device. The substrate is a transparent conductive electrode, and the spacer is 3M 9088 double-sided tape.
[0510] The ECD was constructed by sandwiching such mixed layer Fe-complexed films (1DB and 2DB│18│ITO / PET 60ohm / sq) with bare 60ohm / sq ITO / PET. An electrolyte gel (Li salt in propylene carbonate, with or without PMMA as plasticizer) or an ionic liquid was placed between the two electrodes. The contacts were made of copper tape or silver paste, and the spacing between the two electrodes was achieved by introducing 50μm-200μm double-sided tape. The chronoamperometry was measured in order to test the device's durability to bending: the device was measured when it was upright, then when it was bent with a curvature radius of 2.5cm, and finally when the device was back to upright it was measured again. Electrochemical switching was performed by applying -2.5V for 10 seconds and 3V for 30 seconds for several cycles. The results did not show significant differences when the device was measured before or after bending, as shown in Figure 2. Fig.44 Displayed.
[0511] Fig.45 The colored (left) and achromatic (right) photographs of the flexible electrochromic device shown in , where the working electrode is a film comprising a mixed layer of (Fe complexes 1DB and 2DB│18│ITO / PET 60ohm / sq) and the counter electrode is a bare 60ohm / sq ITO / PET substrate. Electrochemical switching was performed by applying -2.5V for 10 seconds and 3V for 30 seconds.
[0512] Fig.46 Photographs of the colored (left) and achromatic (right) flexible electrochromic device shown in , where the working electrode is a film comprising a mixed layer of (Fe complexes 1DB and 2DB│18│ITO / PET 60ohm / sq) and the counter electrode is a bare 60ohm / sq ITO / PET substrate. Electrochemical switching was performed by applying -2.5V for 10 seconds and 3V for 30 seconds while the device was held at a radius of curvature of 2.5cm.
[0513] 8. Study of other polypyridyl complexes
[0514] The crystal structures of the complexes 1DB M=Fe and 2DB M=Fe were obtained, and the library of complexes was expanded to include the complexes 1DB M=Ru and 1DB M=Os. Figure 47A-47B and the other complexes 1DB M=Ru and 1DB M=Os in Fig.48 Presented in.
[0515] 9. Patterned electrochromic surfaces
[0516] The selective switching of electrochromic surfaces was demonstrated by depositing the EC material on a glass substrate that was only partially coated with ITO according to a specific pattern. Using this technique, selective switching was used for “writing” and “erasing” in response to an external potential (see Fig.51 ).
[0517] 10. Open circuit behavior
[0518] Open circuit stability is defined as the ability of a material to recover its original state after being subjected to an external stimulus. It was found that after being oxidized and thus decolorized, the component (film, i.e., EC material on a substrate in the embodiments as described herein above) is able to be spontaneously reduced and thus colored. The spectroelectrochemical profile of the open circuit experiments is given in Fig.52 The rate constant for the time taken for the assembly to recover its original state was extracted from the decay exponential and was found to be 2.25 ± 0.37 min -1 An application of this characteristic behavior is to use this spontaneous electron flow in order to supply the power of a power consumer, such as an LED. To supply a power consumer, such as an LED, a supply current is required. When restored under open circuit, the device can generate a spontaneous current that can be further used.
[0519] 11. Operation of several devices in parallel
[0520] Connecting several devices in parallel. Such a configuration allows applying the same voltage to all devices while summing the current through each device. Furthermore, connecting several devices together allows increasing the active area and by doing so overcomes the resistivity problems that arise with larger surfaces (see Fig.53 ).
[0521] 12. Charge Trapping System
[0522] When combining two complexes with different redox potentials, the hierarchy of the components becomes an important parameter that determines the electrochemical properties of the components. In this example, a two-component system was studied: a component of (1DB M = Fe and 1DB M = Ru) and a component of (2DB M = Fe and 1DB M = Os). Table 2 presents the redox potentials of the different complexes, which allows the existence of three different results, depending on the hierarchy of the components:
[0523] 1) When the two components are mixed and randomly deposited on a substrate, both complexes should be electrochemically accessible and therefore active. This situation allows for a "three-state system" because the system can exhibit one of three states: (a) both components are reduced; (b) one is reduced and one is oxidized; (c) both components are oxidized.
[0524] 2) When the lower redox potential component is closer to the substrate than the higher redox potential component, oxidation of the top component is impossible, and thus the system cannot reach a fully oxidized (completely decolorized) state.
[0525] 3) When the higher redox potential component is closer to the substrate than the lower redox potential component, reduction of the top component is not possible, which leads to charge trapping because the top part is in its oxidized form, but cannot be reduced. This property of charge trapping can be used as a new battery-like technology because the trapped charge can be released on demand by applying an external stimulus such as light or overpotential. Each external stimulus has its own operating mechanism. Generally, by applying a stimulus, one can overcome the energy barrier that causes charge trapping, and thus the charge can be released.
[0526]
[0527] Table 2. Redox potentials of complexes 1DBFe, 2DBFe, 1DBRu and 1DBOs.
[0528] Three different hierarchical structures (1, 2, 3 above) were studied for the two proposed systems: an assembly including 1DB M=Fe and 1DB M=Ru and an assembly including 2DB M=Fe and 1DB M=Os. In the case of the assemblies 1DB M=Fe and 1DB M=Ru, the lower redox potential component is the complex 1DB M=Fe (a Fe-based complex with a redox potential of 1 V), and the higher redox potential component is the complex 1DB M=Ru (a Ru-based complex with a redox potential of 1.2 V). Figure 54A-Figure 54C Cyclic voltammograms of assemblies containing compounds 1DB M=Fe and 1DB M=Ru at each discussed hierarchy are presented. Fig.54AIn the , the redox waves of the two components are evident. Fig.54B In the , the phenomenon of charge trapping is presented, because in the first redox cycle, there are two oxidation peaks of the two components, however, as the assembly is repeatedly cycled, the top component cannot be reduced and therefore its oxidation wave decreases. Fig.54C In the figure, the reduction waves of the two components are obvious, however, only the bottom component can be completely oxidized.
[0529] In the case of the components 2DB M=Fe and 1DB M=Os, the lower redox potential component is the complex 1DB M=Os (Os-based complex with a redox potential of 0.8 V), and the higher redox potential component is the complex 2DB M=Fe (Fe-based complex with a redox potential of 1 V). Figure 55A-Figure 55C Cyclic voltammograms of assemblies containing compounds 2DB M=Fe and 1DB M=Os at each discussed hierarchy are presented. Figure 54A-Figure 54C The same properties observed in Figure 55A-Figure 55C It was observed that Fig.55A represents a mixed hierarchy, Fig.55B represents a block hierarchy, where complex 1DB M=Os is on top of complex 2DB M=Fe, and Fig.55C An inverse block hierarchy is represented, with complex 2DB M=Fe on top of complex 1DB M=Os.
[0530] Example 2
[0531] Electrochromic supercapacitors
[0532] In this example, the formation of an integrated optoelectronic device is demonstrated, in which the amount of available charge is represented by color. The device has the design and operating characteristics of a hybrid supercapacitor: (i) the battery-like electrode consists of a coordination-based network of metal organic complexes bound to a fluorine-doped tin oxide (FTO)-coated glass. This redox-active component has a dual function as a hole storage layer and a charge indicator, and (ii) the capacitor-like electrode is a combination of multi-walled carbon nanotubes (MWCNTs) deposited on a PEDOT:PSS layer directly attached to the FTO. Combining thin layers of these functional materials results in a new device that can power conventional diodes in electronic circuits.
[0533] In this example, an iron polypyridyl complex is used as a molecular component for forming an electrochromic hole storage layer as a battery-like electrode = [Fe|FTO / glass] ( Fig.56A , Fig.56B As shown above, thin films of these complexes exhibit excellent electrochemical reversibility combined with electrochromism.2+ / 3+ ) controls the light absorption properties of these complexes. Due to metal to ligand charge transfer (MLCT), the divalent iron complex has a strong color (purple), while the trivalent iron complex does not have a strong color (purple). This useful property allows monitoring the amount of charge stored in the device as a function of its color. At the same time, the electrochromic layer acts as a low voltage operable charge storage component (Fe 2+ / 3+ :1.0V relative to Ag / Ag + ). The three pyridyl groups of the iron complex can easily bind to palladium dichloride to form a dense molecular network on the metal oxide, as shown above in this article. The network in this example was formed by iteratively spin coating PdCl2(PhCN)2 (3.0mM) in THF and iron polypyridyl complex (0.6mM) in CH2Cl2 / MeOH (1:1v / v) onto [FTO / glass] (2cm×2cm or 6cm×6cm). For both deposition steps, the substrate was spin coated at 500rpm for 10s and then at 1000rpm for 30s. The process was repeated 18 times and a uniform colored coating was obtained. Such a film has a thickness of ~280nm. In this embodiment, '18 times' means that 18 palladium linker layers and 18 metal ion organic complex layers have been applied.
[0534] Place the capacitive sample electrode on top of the [FTO / glass] ( Fig.56B The conductive substrate was first coated with the polymer poly(3,4-ethylenedioxythiophene):polystyrenesulfonate (PEDOT:PSS), followed by deposition of multi-walled carbon nanotubes (MWCNTs) ( Fig.60A ). It was found that MWCNTs adhered better to the surface of PEDOT:PSS than to the surface of FTO-coated glass. Combining these two conductive materials (MWCNTs and PEDOT:PSS; abbreviated as PPC) resulted in a stable electrode setup. Carbon-based materials and conductive polymers (PEDOT:PSS) have been used by others to make electric double layer capacitors (EDLCs). The high surface area of MWCNT-based layers combined with their high electrochemical stability and porosity make these carbon-based materials ideal candidates for making electronic storage components. Capacitor electrodes were prepared in two steps: (1) PEDOT:PSS / isopropanol (1:1.4 v / v) was spin coated on [FTO / glass] at 500 rpm for 10 s, followed by spin coating at 1000 rpm for 30 s ( Fig.60A). Subsequently, the coating was dried at 120°C for 1 min. (2) Due to van der Waals interactions, MWCNTs tend to bundle and aggregate in solution. Therefore, a perylene diimide derivative (ethyl-propyl perylene diimide, EP-PDI) in an organic solvent (CHCl3) was used to disperse the MWCNTs by non-covalently binding to the walls of the MWCNTs (i.e., the perylene diimide derivative (ethyl-propyl perylene diimide, EP-PDI) non-covalently binds to the walls of the MWCNTs). The MWCNT dispersion was drop-cast onto PEDOT:PSS ( Fig.60B ), (3) washed thoroughly with CHCl3 to remove the organic dispersant and dried in air at 120°C ( Fig.60C ). SEM imaging showed a uniform distribution of tubes on the surface, which was not affected by washing. The resulting PPC was capacitive (10.7 F·g -1 ), as indicated by the linear increase in capacitance with increasing scan rate ( Figure 60D-Figure 60F ). The thickness of the PPC layer was ~15 μm ± 5 μm as indicated by profilometry.
[0535] The laminated electrochromic hybrid supercapacitor (EHSC) consists of: (i) [PPC|FTO / glass], as reference and counter electrodes, (ii) an insulating spacer encapsulating the electrolyte (for details, see below), and (iii) [Fe|FTO / glass], as the working electrode ( Fig.56C The device operates as follows: When a potential of 1.8 V is applied, the iron polypyridyl complex is oxidized (Fe 2+ / 3+ ). This process is accompanied by a purple to transparent transition. Electrons flow from [Fe|FTO / glass] to [PPC|FTO / glass] through an external circuit and form a double layer of ions at the surface of these electrodes. Discharging the device at a potential of -0.4 V involves reducing the iron polypyridyl complex (Fe 3+ / 2+ ), resulting in purple; electrons flow from [PPC|FTO / glass] to [Fe|FTO / glass] ( Fig.56D ). In this illustration, the contacts of the wire are shown as touching the glass. However, in practice, the contacts reach / touch the FTO / active material layer. This is omitted for clarity.
[0536] The electrochemical properties of the device [glass / FTO|Fe||PPC|FTO / glass] were evaluated using cyclic voltammetry (CV) in a two-electrode cell configuration over a potential window of -0.4 V to 1.8 V. The CV clearly showed both capacitance and Faradaic current, which are characteristic of hybrid supercapacitors ( Fig.57A, red line, EHSC). For the charging process (= oxidation current), the capacitive current appears in the potential range of -0.4 V to ~1.2 V, while the faradaic current is visible at higher potentials (~1.2 V to 1.8 V). For the discharging process (= reduction current), the capacitive current is relatively high in the potential range of 1.8 V to ~0.5 V, while the faradaic current is observed at lower potentials (~0.5 V to -0.4 V). The CV of the EHSC shows a significant enhancement of the current due to the capacitor component. This component can effectively store energy by electrostatic forces, resulting in efficient electron transfer, which leads to higher currents. No capacitive current appears in the first CV cycle before reaching ~0.35 V, and due to the oxidation of the iron centers (Fe 2 + / 3+ ) resulting in a clear peak at ~1.46 V being observed ( Fig.61 ). For the 2nd and 3rd cycles, the capacitive current already appears at ~0 V and the oxidation peaks are less pronounced. Apparently, diffusion of electrolyte into the multilayer redox-active network allows the capacitive current to occur at lower potentials and also leads to a change in the redox chemistry. For CV cycles 1-3, the overall charge remains constant (~8 C). [Fe|FTO / glass] is the source of electrons in the EHSC, as there is a nearly linear correlation between the number of redox-active layers (5-18) and the charge ( Fig.62 ). Here, the number of layers (5-18) means that the redox active layer is a layer of a complex of metal ions with organic coordination.
[0537] To demonstrate the synergistic effect of using two different capacitor and battery type electrodes (as shown above for EHSC), two control devices with only one of these electrodes have been fabricated: (A) [Glass / FTO||PPC|FTO / Glass] and (B) [Glass / FTO||Fe|FTO / Glass]. For (A): When both MWCNTs and PEDOT:PSS (=PPC) are used, only a low double layer capacitance ( Fig.57A , black line, PPC). For (B): CV of the assembly of the iron complex shows metal-centered redox chemistry but no capacitance ( Fig.57A, purple line, Fe complex). A large potential is required to oxidize and reduce the metal center (-1.6 V to 2.5 V). Interestingly, two redox pairs were observed: (i) -0.02 V and -0.06 V, (ii) 1.76 V and -0.84 V, which may be related to the distance of the iron complex from the working electrode. The iron complex close to the electrode is easily addressed; therefore, there is a small peak-to-peak separation (ΔE = 0.04 mV). For the distant iron complex, a large peak-to-peak separation (ΔE = 2.6 V) was observed. For the EHSC, the redox potential window is narrower than that of the Fe complex electrode without the PPC electrode. This is due to the higher efficiency of the [PPC|FTO / glass] electrode compared to [FTO / glass]. In the control experiment, one electrode was glass / FTO and the other electrode contained PPC or an Fe ion organic complex, as described in parentheses above this article.
[0538] The relationship between charge-discharge and current density of the EHSC was obtained from the galvanostatic charge-discharge (GCD) profile. -1 To 1.8A·g - GCD profiles were recorded in the potential range of -0.6 V to 2.0 V over a wide current density range ( Fig.57B ). It was found that these profiles depend on the applied current density and the shape of the curve. Fast charging (~2 s, leftmost graph) while applying 1.8 A g -1 The current of the hybrid supercapacitor was 2.3 Wh·kg-1, indicating a small internal resistance drop during discharge using the GCD profile. This drop is due to the equivalent series resistance, which includes the resistance of the electrolyte, electrodes, the interface between them, and the external contacts. The energy density (E) and power density (P) were found to be ~2 Wh·kg-1. -1 and ~2529W·kg -1 , which is within the scope of such a device ( Fig.63 ). For comparison, FIG64 shows the above two control devices [glass / FTO||PPC|FTO / glass] Fig.64A and [glass / FTO||Fe|FTO / glass] Fig.64B Chronopotentiometry (CP) data. These experiments are constant current charge-discharge (GCD) curves of the reference device. CP was recorded at a current of 0.5 mA in the measured / limited potential ranges of -0.6 V to 2 V and -2.0 V to 3.0 V, respectively.
[0539] During device fabrication, a portion of the MWCNT layer (12 mm x 17 mm) at the center of the electrode was mechanically removed to create an optical window (3 mm x 7 mm). This window (=charge indicator) enables monitoring of charge storage and release by UV-vis spectroscopy. Since the MWCNT layer appears black, while the PEDOT:PSS layer is bright, removing a portion of the MWCNT layer enables optical transmittance through this area of the device. Spectroelectrochemical measurements show a correlation between applied potential, amount of stored charge, optical density and color ( Figure 57C-Figure 57F ). UV / Vis spectra and photographs at five different potentials show the colors during operation of the supercapacitor. When the device is fully charged, the charge indicator is transparent (=Fe 3+ ; Fig.57C ), and when discharged, the charge indicator is purple (=Fe 2+ ; Fig.57D ). The relationship between the color of the charge indicator and the amount of charge stored-released is Figure 57E-Figure 57F This experiment involves the -1 GCD profile of current density and in situ transmittance (λ=573nm).
[0540] Both the energy and color stability of the device were checked by GCD measurement. -1 The initial energy density and color (~90%) were maintained for 1000 consecutive charge-discharge cycles ( Fig.58A ). Fig.58B It is shown that the shape of the GCD curve is maintained due to the good Coulombic efficiency of 99% ( Fig.65 , see Coulombic efficiency calculation above in this article). During the GCD measurements, the device temperature was monitored using an infrared thermometer. No changes in the device temperature were observed ( Fig.66 ). Fig.58C The corresponding transmittance variation at λ=573 nm is shown, with the contrast ratio ranging from 27% to 24%. 1 / 2 ~60min) and color (T 1 / 2 ~38min) to show the charge stability ( Fig.58D ). These values are larger than those previously reported for the self-discharge of related devices (i.e., other electrochromic capacitors).
[0541] In addition, an electronic circuit using EHSC as an energy storage device and power source was demonstrated, accompanied by real-time color changes ( Figure 59A-Figure 59B , Fig.67 and Fig.68). Charge the device to 1.8V and the device changes color from purple to transparent. The red LED is used to indicate the current flowing to the device while charging ( Fig.59B , i→ii). The EHSC is used as a power source for a 1V diode connected to a yellow LED. Then, when the electronic circuit switches to power mode, the LED lights up (discharges) and the EHSC is used as an energy source for the diode ( Fig.59B , iii). The color of the EHSC changes to light purple due to the threshold voltage of the diode of 1V ( Fig.59B , iv). After the device is fully discharged, under open circuit, the color of the device turns purple again.
[0542] In summary, this example demonstrates an integrated electrochromic-hybrid supercapacitor (EHSC) and shows two device configurations: functional materials can be stacked in a layered architecture or an in-plane architecture. In this example, a device with a hole in the middle is mentioned. In the area of the hole, there are no CNTs, so the architecture is in-plane, while in other areas where CNTs are present, the architecture is layered.
[0543] The structure with an optical window allows the state of the device to be optically read out in optical transmission mode. Both configurations have similar properties. The metal organic layer has a dual role: as both an electrochromic material and a hole storage layer. The storage of holes in this redox active material is directly related to its color, which allows it to be associated with the charge state of the hybrid supercapacitor. The layered structure of the hybrid supercapacitor is a unique example of a useful synergistic effect that can be achieved by combining a set of completely different materials: in this case: metal oxides, organic polymers, MWCNTs, and metal organic polymers based on coordination (metal ion organic complexes). Polymers with excellent heteroelectrochromic properties. In one embodiment, an electrochromic hybrid supercapacitor can be used to operate in a conventional circuit by powering a diode (= gate) that allows current to light up an LED. In one embodiment, if the circuit has a diode with a threshold of 1V, the higher potential "turns on" the diode, and therefore the LED will light up. Other electronic components can be powered by the capacitors described herein. The capacitors described herein can be used as components in a large number of electronic circuits that require capacitors or supercapacitors. The electrochromic properties can be used to monitor the function and operating state of any electronic circuit including the capacitor of the present invention.
[0544] This first generation device exemplified herein has promising properties as it exhibits high energy density and high power density, high Coulombic efficiency and short charging time. In addition, it shows promising charge-discharge stability combined with electrochromism for 1000 consecutive cycles.
[0545] Experimental Section
[0546] Materials: ethylpropylperylene diimide (EP-PDI), iron polypyridyl complex ( Fig.56A ) and their surface-bound assemblies were prepared as reported herein. Solvents (AR grade) were purchased from Bio-Lab (Jerusalem), Frutarom (Haifa, Israel), or Mallinckrodt Baker (Phillipsburg, NJ). PdCl2(PhCN)2, propylene carbonate (PC), poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS), and poly(methyl methacrylate) (PMMA) were purchased from Sigma-Aldrich. Lithium perchlorate (LiClO4) salt was purchased from Tzamal D-Chem (Israel). Multi-walled carbon nanotubes (MWCNT; diameter 20 nm-30 nm, length 20 μm-30 μm) were purchased from Cheap Tubes (Cambridgeport, VT). Fluorine-doped tin oxide (FTO) coated glass substrates (6 cm × 6 cm and 2 cm × 2 cm, Rs = Rs = 8Ω / □-12Ω / □) were purchased from Xinyan Technology, Ltd. (Hong Kong, China). The substrates were cleaned by sonication in ethanol for 10 min, dried under air flow, and then cleaned in a UVOCS cleaning system (Montgomery, Pa) for 20 min. The substrates were rinsed with tetrahydrofuran (THF), dried under air flow, and dried at 120 ° C for 2 h. A spin coater (Laurell, model WS400A-6NPP / LITE) was used for the functionalization of metal oxide electrodes. The components of the circuit were purchased at Digi-Key (Minnesota, USA) and the circuit was designed using Altium Designer software version 19.0.15.
[0547] UV / Vis spectra. UV / vis spectra were recorded on a Cary 100 spectrophotometer. Absorbance (200 nm-800 nm) was measured using Varian's CaryWinUV-Scan application version 4.20 (468), while transmittance was measured using Varian's CaryWinUV-Kinetics application version 4.20 (468). FTO-coated glass substrates were used to compensate for background absorption.
[0548] Electrochemical characterization. Cyclic voltammetry (CV), chronoamperometry (CA), and chronopotentiometry (CP) were performed using CHI760E and CHI660E workstations. The following configuration of the electrochemical cell was used: [Fe|FTO / glass] or [PPC|FTO / glass] (2 cm × 2 cm) was used as the working electrode, Ag / Ag+ was used as a reference electrode, and a Pt wire was used as a counter electrode. Lithium perchlorate (LiClO4 0.1 M in propylene carbonate:acetonitrile=1:1, v / v) was used as a supporting electrolyte.
[0549] Formation of capacitor electrodes. By weighing a bare [FTO / glass] substrate (2cm × 2cm) and spin coating PEDOT: PSS / isopropanol (0.5mL of PEDOT: PSS and 0.7mL of isopropanol) at 500rpm for 10s, and then spin coating at 1000rpm for 30s. Subsequently, the [PEDOT: PSS | FTO / glass] substrate was dried at 120°C for 1min. For the dispersion of MWCNT, 1.0mL of CHCl3 was sonicated with 1.0mg of MWCNT and 1.0mg of EP-PDI at 0°C for 30min (sonication at low temperature was used to prevent the formation of free radicals). The resulting suspension was drop cast (0.3mL-0.8mL) onto [PEDOT: PSS | FTO / glass]. The electrode was kept at 120°C for 15min and washed with CHCl3 to remove EP-PDI until the CHCl3 solution was colorless. The obtained [PPC|FTO / glass] was dried at 120°C for 30 min. Optical window (3 mm×7 mm, see Figure 57C-Figure 57D ) was produced by removing the MWCNT layer from the center of [PPC|FTO / glass] using a cotton swab in ethanol. The substrate was weighed in order to know the mass of CNT and PEDOT applied on the FTO, i.e. the mass of "active material" in the device.
[0550] Fabrication of electrochromic hybrid supercapacitors (EHSCs). A double-sided tape frame (3M 9088; 210-μm thick) was placed on [Fe|FTO / glass], leaving exposed edges (1mm-2mm) for copper tape contacts. Subsequently, Whatman filter paper (catalog number 1001-070, pore size 11μm, thickness 180μm) used as a dielectric layer was placed in the frame. The electrolyte solution was drop-cast on the filter paper. The [PPC|FTO / glass] electrode (2cm×2cm) was immersed in the electrolyte solution (PC:ACN, 1:1v / v, 0.1MLiClO4) for 1h, and then, the [PPC|FTO / glass] was placed on the top of the frame parallel to the filter paper. The conductive surfaces of the two electrodes faced each other. [Fe|FTO / glass] is the working electrode, and [PPC|FTO / glass] is used as the counter electrode / reference electrode. In this embodiment, the same electrolyte solution is used for paper and for soaking the PPC electrode. Other electrolytes may be used as known in the art.
[0551] Example 3
[0552] Organic memory cells - charge storage and release
[0553] In this embodiment, charge storage and release in multi-layer nanoscale assemblies are described. The step-by-step assembly of nanoscale molecular layers is an attractive and versatile method for designing functional films. This method can manufacture materials that can hold and release charge in response to electrochemical stimulation. Charge storage and release are combined with color changes. In some embodiments, the color change is an indication of the charge state of the device. In this embodiment, the manufacture of multi-level organic memory cells (OMCs) per small piece (bit) containing ruthenium, iron and osmium polypyridyl complexes is demonstrated. OMCs exhibit dual-function storage performance, in which information can be read optically as well as electrochemically.
[0554] introduction
[0555] The field of organic electronics proposes alternative methods for microelectronic compositions and nanoelectronic compositions. Replacing conventional metal components with blends of polymers (copolymers or homopolymers), small molecules, and metal organic compounds provides the design of new electronic systems with unique properties. Combining high electrical conductivity or ionic conductivity with unique physical properties such as mechanical flexibility opens the door to countless innovative inventions, from energy harvesting and wearable items to biomedical applications. Polymers and small molecules contribute to the realization of lightweight, low-cost and sustainable electronic components, and can be used as building blocks for customized manufacturing processes. Such methods can control the composition of the system at the molecular level. In addition, such methods are compatible with new deposition techniques, such as inkjet printing, spinning and spraying, which are useful for the design of complex electronic components prepared to meet the challenges posed by advanced technology. Due to the rapid development and participation of information technology devices (such as mobile phones, digital cameras, and personal computers) in our daily lives, the demand for advanced data storage elements has become essential. Traditional Si, Ge and other semiconductor industries face the challenge of combining miniaturized devices with increased information density. In order to store larger amounts of data, more transistors and capacitors are packed into a single chip, resulting in limited capacity and heating issues. The pursuit of more advanced memory technology has led to the discovery of volatile memory / non-volatile memory based on new architectures and materials, such as molecular memory, macromolecular memory, and ferroelectric memory. Most emerging non-volatile memories are based on two-terminal switching elements, which are good candidates for high-density memory architectures. However, current memory components show a single memory type (RAM, ROM, WORM, etc.) with limited functionality. The combination of more than one type of information storage is conducive to reading data in several different ways. For example, combining a single small piece with random access memory (RAM) and read-only memory (ROM) can replace two separate transistors, and thus can reduce the hardware size. Regarding the memory density challenge, a multi-level per-small-piece memory chip is very attractive because it allows the use of four possible states to store data for two small pieces in each cell.
[0556] Results and Discussion
[0557] In this work, multi-level per-tile organic memory cells (OMCs) are demonstrated, which can be read optically to give a write-once-read-many (WORM) memory and can also be read electrically with a read-while-write memory type (RWW). The proposed memory tile contains a multilayer nanoscale assembly of three metal organic complexes: ruthenium, iron and osmium polypyridyl complexes. Integration of the tile into a conventional electronic circuit enables the charge state of the component to be controlled individually, i.e. switched between four different states based on a charge trapping and release mechanism with gradual release. The states differ due to their color as well as their electronic properties. This results in a dual-functional memory element that can be read in two separate ways: RWW based on electrical input and output, and WORM based on different UV-vis transmittances of the OMC under applied specific voltages.
[0558] States are defined by their color as well as the charge of the state:
[0559] State 0, transparent, charged, all components are oxidized;
[0560] State 1, orange, ruthenium is discharged, while iron and osmium are both charged;
[0561] State 2, red, ruthenium and iron discharge, and osmium charges; and
[0562] State 3, Bordeaux, all three groups are discharged.
[0563] Working electrode (WE): Indium tin oxide (ITO) coated PET (polyethylene terephthalate) was modified by the above mentioned polypyridyl complex using alternate spin coating of PdCl2(PhCN)2 (4 mM, THF) and a solution of a metal organic compound (6 mM, DCM:MeOH=1:1 v / v) as follows:
[0564] The ruthenium complex as an electron mediator element is attached to a conductive and transparent support by combining with a Pd linker layer, forming a dense coordination network with palladium chloride. The ruthenium complex acts as an electron monitoring agent, which can promote or block the transfer of electrons through the entire molecular assembly.
[0565] On top of the ruthenium complex layer, the iron polypyridyl complex and the osmium polypyridyl complex (respectively) are deposited in bulk structures (see Fig.69C The characteristics of the metal center determine the optical and electrochemical properties of the compound. The various possible oxidation states of the complex ([Ru] 0-3+ , [Fe] 1+-3+ , [Os] 2+ / 3+) leads to a variety of redox potentials, which is crucial in order to achieve 4 different memory states. The composition of the molecular components used to form the OMC is selected in a progressive manner according to the redox properties of the components in their ground state: [Ru] 2+ / 3+ , 1.3V>[Fe] 2+ / 3+ , 1.1V>[Os] 2+ / 3+ , 0.8 V. This sequence enables trapping of positive charges on the osmium layer (state 2) and on both the iron complex and the osmium complex (state 1).
[0566] The operation and mechanism of OMC are as follows: The write process starts from state 0.
[0567] However, the as-prepared small piece [Ru]8[Fe]4[Os]4 is in the on state 3, where the components are in their divalent states. Therefore, 1.6V first needs to be applied to enable the components to be oxidized to initiate memory operation (and achieve state 0).
[0568] State 1 is written by applying 0.8 V, causing the ruthenium complex to be reduced ([Ru] 3+ / 2+ ). However, due to the lower oxidation potential of the upper block, positive charge is stored on the upper block. The ruthenium layer hinders the transfer of electrons through the upper layers (iron-based complex and osmium-based complex) by physical isolation and electrically unfavorable reduction pathways. To write state 2, -1.4 V is applied, the ruthenium mediator is reduced to its monovalent form, and an energy rise in its reduction potential (Ru 1+ / 2+ =-1.25 V), this oxidation state allows ruthenium to promote electrons to iron [Fe] 3+ / 2+ , but osmium remains in its trivalent state (see Fig.69E ). To release the positive charge on the osmium block, -2.1 V is applied, and the mediator overcomes the 3-electron reduction ([Ru] 3+ / 0 ) and the native oxidation state ([Ru] 0 ). In this stage, the mediator passes through the iron layer ([Fe] 3+ / 1+ ) triggers a chain reduction reaction toward osmium, and the iron monovalent compound releases osmium ([Os] 3+ / 2+ ) on the surface. This results in the appearance of Bordeaux, state 3.
[0569] The read operation is divided into two orthogonal paths that exhibit two different memory behaviors:
[0570] WORM memory: Due to the different optical properties of the states, one can use spectroscopic methods such as UV / vis absorption to read the implemented information as many times as needed by the optical signature of each individual state. The second memory behavior (RWW) is based on the electrochemical differences between the states. To read out the information, 1.6V is applied and the amount of charge is calculated using chronoamperometry (CA) while the patch returns to state 0. Since the patch consists of more divalent metal centers, the readout charge is higher and can be an indication of the state identity: State 1: 1mc / cm 2 , State 2: 2mC / cm 2 , State 3: 4mC / cm 2 and state 0 shows no current at 1.6V.
[0571] Thus, in some embodiments, optical detection is used to read the state of the device, and in some embodiments, the amount of charge is used to indicate the state of the device. In some embodiments, both optical readout and electrochemical readout can be used in parallel or sequentially to read the state of the device / memory cell.
[0572] Figure 69 shows the organic memory cell, building blocks, fabrication and status. Fig.69A A 3-electrode electrochemical cell consisting of OMCs is shown. Fig.69B Molecular components used to form nanoscale metal-organic assemblies are shown. The positive charges of the complexes and counterions have been omitted for clarity. Fig.69C A layer-by-layer deposition step using a [PdCl2(PhCN)2] complex is illustrated for bonding. Fig.69D It is a schematic diagram of OMC operation and status.
[0573] EDS-transmission electron microscopy (TEM) image of a thin section milled by focused ion beam assisted SEM ( Fig.70 ) clearly shows a continuous composition of small pieces. The components are well defined and not mixed with each other. A continuous coating with an average value of ≈162 nm was observed: [Ru], 64 nm; [Fe], 50 nm and [Os], 48 nm.
[0574] Chronoamperometry and UV / vis absorption measurements demonstrate OMC operation, which involves random read and write voltage sequences ( Fig.71 ), accompanied by max= Optical absorption of the small piece of 570nm. The area below the figure (for the read voltage (1.6V) represents the amount of charge reaching the working electrode: for state 0, no read current is observed at 1.6V (t=10 seconds), indicating that all components are in their trivalent state and the small piece remains transparent, however, further application of 0.2V (t=5 seconds, write voltage) and read voltage (1.6V, t=5 seconds) shows a 1mC / cm 2 The calculated charge and absorbance of 0.075 are for oxidation of state 1. Application of -2.1 V for 0.5 sec triggers a chain reduction reaction in which all components are in their divalent states, resulting in an absorbance of 0.27 ( Fig.71 ), 4mC / cm is calculated when reading the voltage 2 (indicating oxidation of state 3). State 2 was obtained at -1.4 V, and UV / vis data showed small flakes of [Ru] 2+ -[Fe] 2+ -[Os] 3+ The partial reduction of 2 mC / cm 2 .
[0575] The OMC can be used in conventional circuits, with the writing process being done by an electronic hardware potentiostat to implant digital information, and the reading process being done using an electronic keyboard (see Fig.72 ). During the erase / read voltage (1.6V), the keyboard follows the output voltage of the counter electrode (CE).
[0576] To read the information, the threshold voltage is determined to be 1.94V (=V th ), and returns to 1.94V (=V th ) the time required to turn on the LED (see Figures 73A-73E ). On the surface of the bit in state 0, no redox reaction occurs, and therefore, CE remains at 1.6 V without reaching V th The lamp is not turned on at t0 = 0. However, the readout operation of state 1 involves oxidation of the ruthenium mediator block, raising the voltage on CE to 2 V to keep the voltage on the reference electrode constant (1.6 V), and the CE voltage drops back to V at t1 = 0.3 seconds. th States 2 and 3 involve oxidation of the upper block, therefore, a delay is observed in the voltage drop, and the time over threshold (TOT) measured for state 2 is t2=1.3, and the time over threshold (TOT) measured for state 3 is t3=1.3, 2.8 seconds ( Fig.73A). A logic keypad connected directly to the OMC is programmed to read out and differentiate between states based on the time over threshold (TOT), as explained above. The keypad converts the TOT into an electrical output, lighting the corresponding bulb (see Fig.73E By scanning the UV / vis spectrum from 800nm to 350nm, the absorbance characteristics of the four memory states 0-3 can be observed ( Fig.73B ). The absorption spectrum of state 3 is max = 425nm-625nm region shows three overlapping MLCT bands. These bands refer to the iron (λ max =570nm) polypyridyl complex, ruthenium (λ max =500nm) polypyridyl complex and osmium (λ max =514nm) the presence of polypyridyl complexes. The absorption of state 2 in the visible region is at λ max =425nm-625nm region has two overlapping MLCT bands. For state 1, only one MLCT band appears at λ max =500 nm, and it belongs to the ruthenium component. For state 0, MLCT is prohibited because the entire component is in its trivalent state.
[0577] Cyclic voltammogram (CV) measurements combined with UV / Vis spectroscopy were used to investigate the charge trapping phenomenon: the as-prepared hybrid flakes were in state 3 (Bordeaux appearance), and repeated cycles of potentials between 0 V and 2 V were performed, resulting in charge trapping on both the iron and osmium blocks. Evidence for charge trapping was provided by irreversible oxidation of the upper layers ([Fe] 2+ / 3+ and [Os] 2+ / 3+ ) provided by the ruthenium complex, which can be reversibly addressed ([Ru] 2+ / 3+ ). Oxidation of the components reveals two main peaks instead of three (one for each component). The osmium layer is isolated with respect to the electrode, so to address the upper layer, electron passage from the electrode should occur; trace amounts of [Ru] 3+ and [Fe] 3+ It can mediate the oxidation of the osmium layer. When the oxidation potential of the ruthenium bulk is relative to Ag / Ag + At 1.3V, a small amount of [Ru] 3+ It starts to appear at 1.0 V (onset potential) and overlaps with the onset potential of the iron layer, which in turn can charge (oxidize) the osmium layer. As a result, a peak (at 1.1 V vs. Ag / Ag + ), indicating oxidation of both iron and osmium. The CV shows that when scanning from 2V-0V after the first redox cycle, only the ruthenium complex is reduced and the ruthenium mediator is in its divalent state (=Ru 2+) and exists as an insulator that blocks the transfer of electrons to the upper layer (state 1). Spectroelectrochemical measurements at λ max =500nm and shows a sharp increase in transmittance values upon oxidation (20% to 65%), metal to ligand charge transfer (MLCT) is prohibited and ligand charge transfer (LCT) becomes dominant, so state 0 appears transparent, while upon reduction (2V-0V), state 1 is achieved (38% transmittance) and the characteristic orange color of ruthenium appears.
[0578] Spectroelectrochemical (SEC) measurements of a small wafer under ten consecutive read-write voltage cycles are shown and reveal the performance of the OMC with significant state differences. max =Optical write cycle stability at 500 nm: 0: 0.2, 1: 0.422: 0.55 3: 0.65. Notably, the continuous write-read cycles show the optical stability of the OMC, which degrades by 80% after 80 cycles in state 1, 80% after 75 cycles in state 2, and 25 cycles in state 3. The electrical stability calculated as described above shows 85% degradation after 50 write-read cycles in state 1, 70 write-read cycles in state 2, and 50 write-read cycles in state 3. The area under the readout peak clearly reflects the amount of charge passing through the working electrode and the time required to achieve complete oxidation (RWW memory, Fig.73D ): State 1, Q = 1mC / cm 2 , t = 0.25 seconds; State 2, Q = 2mC / cm 2 , t = 0.45 seconds; and state 3, Q = 4 mC / cm 2 , t = 0.9 seconds.
[0579] Overview
[0580] The proposed OMCs show dual-functional memory behavior based on electrochromic redox-active materials deposited on top of a conductive support. Application of various potentials induces changes in the oxidation state of the metal center (M 0-+3 ). Oxidation state-color coupling combined with different charge states allows information readout by optical measurement (WORM) as well as electrochemical methods (RWW). The deposition sequence and the architecture of the thin film setup are carefully chosen and provide charge trapping in the upper layers and gradual release in response to external voltage.
[0581] It should be noted that a wide range of other combinations of different metal ions and a wide range of combinations of build orders of metal ion organic complex multilayer blocks can be used to achieve organic memory cells with varying charge properties, varying optical properties, and with multiple states of the memory cell. The memory cell / data storage device of the present invention can be designed to include different ions, different thicknesses of each ion block, different construction orders of multiple blocks (i.e., which block is closer to the electrode, which block is built first / last / in the middle / on top / below other blocks), different numbers of blocks, different surface areas (electrode surface area) on which the multiple layers are built, etc. Such properties of the device can be modified depending on the number of states required, the charges and ion oxidation states involved, and the spectrum of multiple states of each ion.
[0582] Experimental Section
[0583] Materials and methods
[0584] Solvents (AR grade) were purchased from Bio-Lab (Jerusalem), Frutarom (Haifa, Israel) or Mallinckrodt Baker (Phillipsburg, NJ). Propylene carbonate (PC), poly(methyl methacrylate) (PMMA), PdCl2(PhCN)2 and trifluoromethylsulfonamide lithium salt were purchased from Sigma-Aldrich. Complex 1-Complex 3 were prepared as reported. Indium tin oxide (ITO)-coated poly(ethylene terephthalate) (PET) substrates (10 cm×10 cm, Rs=30Ω / □) were purchased from Xinyan Technology Ltd. (Hong Kong, China). The ITO / PET substrates were cleaned by immersion in ethanol and acetone for 30 s and then dried under air flow. A Laurell spin coater model WS-400A-6NPP / LITE was used to form molecular assemblies (MA).
[0585] UV / Vis spectra. UV / vis spectra were recorded on a Cary 100 spectrophotometer. Absorbance (350 nm-800 nm) was measured using Varian's Cary WinUV-Scan application version 3.00 (182). Transmittance was measured using Varian's Cary WinUV-Kinetics application version 3.00 (182). Bare substrates were used to compensate for background absorption.
[0586] Electrochemical characterization. Electrochemical experiments were performed using a CHI660A or CHI760E electrochemical workstation. The following configuration of the electrochemical cell was used: ITO / PET (3 cm × 3 cm, 0.5 cm × 1 cm) was used as the working electrode, Ag / Ag +was used as reference electrode, and Pt wire was used as counter electrode. Tetrabutylammonium hexafluorophosphate (TBAPF6) in ACN (0.1 M) was used as supporting electrolyte. Spectroelectrochemical measurements were performed in a glove box filled with N2.
[0587] Focused ion beam (FIB) microscopy. Thin sections were prepared using a dual beam FIB-SEM Helios 600. The surface of the sample was scanned with 30 keV Ga + The images were taken at the cross section of FIB milling. First, electron beam assisted deposition was used to locally coat the sample with a 150nm-200nm thick platinum layer, and then a 500nm-600nm thick platinum layer was deposited by ion beam assisted deposition. This coating protects the MA from the damage of the ion beam and provides a clean cross-sectional edge. HAADF (high angle annular dark field) STEM and EDS measurements were performed using Thermo Fisher Scientific Themis Z TEM, which is a double aberration corrected and equipped with a Super-X large solid angle x-ray detector for EDS. Measurement was performed at an accelerating voltage of 200kV.
[0588] Formation of molecular assemblies (MAs). MAs were obtained by iterative spin coating of a solution of PdCl2(PhCN)2 (THF, 4.0 mM) and a ruthenium (1) complex, an iron (2) complex or an osmium (3) complex (CH2Cl2:MeOH=1:1 v / v; 0.6 mM). The PdCl2(PhCN)2 solution was drop cast onto ITO / PET (3 cm×3 cm), the substrate was rotated at 500 rpm for 10 s, and then at 1000 rpm for 30 s. Next, a solution of complex 1, complex 2 or complex 3 was drop cast and the substrate was rotated as described above. The substrate was then immersed in acetone for 30 s and dried under a gentle air flow. The deposition of PdCl2(PhCN)2 and the metal complex (1 or 2) is referred to as a single deposition cycle. For the formation of MAs, the first 6 or 8 deposition cycles were performed with complex 1. After immersing these MAs in acetone for 1 h, 4 deposition cycles were performed with complex 2 and then 4 deposition cycles with complex 3. The resulting MAs were immersed in ACN for 2 h and dried under vacuum overnight.
[0589] Example 4
[0590] Metal-organic components with dual properties: electrochromism and hydrogen production via water electrolysis in neutral aqueous solution
[0591] In this example two different functions of a metal organic film are described. The metal organic film is assembled on the surface of a transparent metal oxide electrode. Two redox active elements are included in the film:
[0592] a. an electrochromic iron polypyridyl complex; and
[0593] b. Catalytically active palladium centers that can operate upon application of different potentials in aqueous solution.
[0594] Regarding the first property, electrochromism, it was found that by electrochemically treating Fe at 0.0-1.0 V (vs. Ag / AgCl), the 2 + / 3+ In the center, the color of the material can cycle from deep purple to colorless for 1500 times. The difference between the transmittance of these two states is high, with ΔT = 52%.
[0595] Regarding the catalytic activity of the palladium ion center, it was found that water oxidation can occur through the in-situ formed palladium oxide particles by applying a higher potential (1.22V-2.0V relative to Ag / AgCl), resulting in the formation of hydrogen (H2) and oxygen (O2). The current density (product output) is stable in an aqueous electrolyte at pH = 6.9 for at least 7 hours, with a Faradaic efficiency (FE) of ~70%.
[0596] introduction
[0597] Environmental sustainability requires a range of new functional materials for efficient catalysis, energy storage, solar-to-electricity conversion, smart glass technology, carbon capture and sequestration, to name a few. Energy solutions based on renewables (i.e. solar, wind) need to be fully integrated with efficient energy storage and release systems. Electrocatalytic production of hydrogen and oxygen from water is ideal because hydrogen can be used for energy storage. Hydrogen is transportable and can be used to process other storage chemicals, such as liquid hydrocarbons. Molecular hydrogen is the ultimate clean fuel because its combustion produces only water.
[0598] In 1982, Meyer's group reported ruthenium polypyridyl complexes as water oxidation catalysts (WOCs). To date, many other molecular catalysts have been reported, however, several problems have hindered their large-scale application, including poor reusability and solubility of the catalysts, the need for sacrificial oxidants (e.g., ammonium cerium nitrate), and harsh (acidic or basic) reaction conditions. Additional limitations include slow reaction rates, low catalyst stability, and cost.
[0599] For the preferred system, low potential is desired to drive the reaction with high current density. In recent years, heterogeneous catalysts on conductive surfaces have been shown to be chemically robust and reusable. Among a variety of materials, transition metal oxides of ruthenium, iridium, manganese, cobalt and platinum and their clusters have been widely studied for electrocatalytic water decomposition. For example, the use of Pd-Mn3O4 and other catalytically active nanoclusters has been reported. Optimization of the catalytic process also includes finding suitable materials that can fix and stabilize the clusters. Recently, the use of polyethyleneimine-modified reduced graphene (rGO) has been shown to support bimetallic gold-palladium nanoparticles for electrocatalysis. Metal organic frameworks (MOFs) have also been shown to be promising electrocatalysts. Using perfluoropolymers (Nafion) containing sulfonic acid groups as binders, MOFs have been drop-cast onto electrodes. Their high porosity allows electrolytes and water molecules to approach the catalytic sites. The electrochemical water oxidation of cobalt-based MOFs formed by atomic layer deposition under alkaline reaction conditions was studied. Another example of electrochemical water oxidation is a MOF doped with a ruthenium catalyst as previously reported.
[0600] The multilayer and device shown in this embodiment are based on a series of nanoscale metal organic components (molecular components MA), which are redox active, thermally stable and highly porous. The coordination-based network of the layer comprising polypyridyl complexes and metal salts has been produced on transparent conductive oxides (TCOs) by automatic spraying or spin coating using layer-by-layer (LBL) assembly. In previous work, although polypyridyl complexes are functional components, metal salts (mainly palladium) are used as crosslinkers combined with the pyridine part of polypyridyl complexes to produce 3D networks. The huge structural versatility of this type of MA leads to diverse and potentially useful functions: interlayers of highly efficient inverted bulk heterojunction solar cells, simulations of logic gates and circuits (including triggers), memory elements, supercapacitors, antibacterial coatings and directional electron transfer. In addition, these materials have excellent charge capture and multi-state electrochromic properties. However, the electrocatalytic properties of such MAs have not yet been explored.
[0601] In this example, a combination of electrochromic and electrocatalytic water splitting is demonstrated. Both electrochromic and catalytic are performed in aqueous electrolytes, and electrocatalytic water splitting is performed using a single functionalized electrode under mild reaction conditions. The demonstration of electrochromic in water is beneficial for the development of laminated devices that do not require the use of volatile organic solvents. The MA used in this example has been prepared using fully automated layer-by-layer (LbL) spin coating.
[0602] The system used in this article is based on two functional components:
[0603] · polypyridyl iron complex (1); and
[0604] Common palladium dichloride salts.
[0605] The coordination of the three pyridyl moieties of the iron complex with the palladium(II) salt forms a dense but still porous network. The network was fabricated on fluorine-doped tin oxide (FTO) coated glass. The coordination-saturated iron(II) complex has excellent electrochromic properties. Due to the unfavorable metal-to-ligand charge transfer (MLCT) in the formed iron(III) complex, it is dark (purple) in the ground state and becomes highly transparent in the visible region upon single-electron oxidation. This single-electron redox process (Fe 2+ / Fe 3+ ) is reversible.
[0606] The palladium entity catalyzes the decomposition of water to produce hydrogen and oxygen without the need for sacrificial materials. The interface engineering of the FTO electrode is a multi-step process that is conveniently performed using fully automated spin coating. The assembly of the different components on the surface is fast enough that the sequential steps can be performed without significant delay time.
[0607] As discussed above, the MA-modified electrode operates as an anode in two distinct electrochemical processes occurring in water under neutral conditions.
[0608] In the electrochemical water splitting cell (EWSC), water is converted into oxygen at the MA-modified anode, and hydrogen is evolved at the platinum cathode.
[0609] MA was prepared by alternately spin coating a solution of PdCl2(PhCN)2 (4.0 mM, THF) and a polypyridyl iron complex (1:0.6 mM, DCM:MeOH=1:1 v / v) on FTO / glass (2 cm×2 cm). The fully automated deposition sequence was repeated 15 times and included a washing step using a common organic solvent. The protocol yielded an electrode with both the desired electrochromic and catalytic properties within 70 minutes. The electrode was visually uniformly coated with a deep purple MA. Such assemblies prepared by LbL dip coating, automated spray coating, or by manual spin coating are known to have excellent electrochromic properties in non-aqueous electrolyte solutions in acetonitrile. The number of depositions can be used to control the color intensity of the film.
[0610] MA / FTO / glass as working electrode (= anode) and Pt wire and Ag / Ag have been used. + A three-electrode cell configuration was used as the counter electrode and the quasi-reference electrode, respectively. An aqueous solution of LiClO4 (0.1 M) was used as the electrolyte at pH 6.9. Cyclic voltammogram (CV) measurements recorded at a scan rate of 0.1 V / s showed a half-wave redox potential E of 0.56 V (vs. Ag / AgCl; 0.1 M LiClO4 / H2) at 0.69 V and 0.44 V. 1 / 2These observations are due to the reversible redox process of Fe 2+ / 3+ Indication of redox pairs. These redox processes occur at lower potentials compared to using organic mediators. CV measurements were performed at different scan rates (0.1-0.9 V / s). Clear exponential and linear correlations (for all fitted R 2 >0.9) was observed between the peak current and the scan rate and its square root. These correlations indicate that the redox process is diffusion controlled. For both the oxidation and reduction processes, the diffusion coefficient D f , for MA1 is ~3.7×10 -8 cm 2 ·s -1 This value is calculated using the Randles-Sevcik equation.
[0611] Spectroelectrochemical (SEC) measurements recorded in transmission mode show that the iron(II) complex max The characteristic, broad metal-to-ligand charge transfer (MLCT) band at ≈575 nm is observed in Fe 2+ Under single electron oxidation of the centers, the MLCT band disappears. This redox process is fully reversible and is accompanied by a colored-colorless-colored transition, as clearly observable by the naked eye. The high transparency of the MA upon application of an oxidative current indicates that, at the applied scan rate, all metal centers are electrochemically addressable.
[0612] To demonstrate the reversibility of this redox process in water, alternating potentials of 0.0 V and 1.0 V were applied at 3 s intervals while monitoring the MA at λ max = Optical absorption at 575 nm. These SEC measurements show that a ΔT% maximum of -52% is achieved in -0.9 s, with ≥97% retention of the initial ΔT% for at least 1500 cycles. The coloration efficiency is estimated to be -155 cm 2 / C. The electrochromic properties of such a component are not affected by the use of an aqueous electrolyte solution.
[0613] The electrochromic function demonstrated above occurs at potentials below that required for electrocatalytic water splitting. When the potential is increased above 1.22 V, as in the case of colorless MA (active surface area = 2.4 cm 2 ) and the Pt wire surface, catalytic oxidation of water occurs. The CV indicates oxygen evolution by the increase in the catalytic wave. The catalytic current is significantly higher than that observed for bare FTO / glass. The corresponding Tafel plot shows a 230 mV dec -1The slope of , as has been observed for electrocatalysis by MOFs. Electrolysis at a constant potential of 1.75 V (vs. Ag / AgCl) showed a gradual increase in current density until a plateau was reached (1.5 h) and ~7.2 mA / cm 2 The current density was maintained for another 5.5h. Also in this experiment, under the same conditions, bare FTO / glass showed a much lower (= four times) catalytic current. Gas chromatography (GC) analysis of the gas mixture in the top space of the working compartment of the airtight electrochemical cell confirmed the formation of 537μmol of H2 (≈268.5μmol of O2) after 4.5h reaction time. Controlled potential electrolysis (CPE) indicated that 148C of charge passed, corresponding to a Faraday efficiency (FE) of 70%. The conversion frequency (TOF) was found to be 0.12s -1 . Anodic oxidation has been observed by others and indicates an electrochemically driven process to activate the catalyst. The initial anodization process of ~1.5 h significantly increased the catalytic activity and is likely associated with structural changes within the membrane. When the electrolyte solution was replaced after 6 h of electrolysis and the experiment was continued with the same MA for another 8 h, the catalytic current seemed unaffected. Therefore, changes in the electrolyte solution or the accumulation of H2 and O2 do not seem to play a role in the efficiency of the catalytic process. Under the oxidizing conditions applied in water, palladium oxide particles are expected to form, as indicated by scanning electron microscopy measurements (SEM, see below).
[0614] In order to strictly exclude the role of the polypyridyl iron complex (1) in water oxidation, we functionalized the FTO electrode with MA2 without this electrochromic component. A solution of PdCl2(PhCN)2 (4.0 mM, THF) and the vinylpyridine ligand L (2.0 mM, DCM:MeOH=1:1 v / v) was spin-coated on FTO / glass (2 cm×2 cm) using fully automated spin coating (for details, see below: “Formation of molecular assemblies (MA1 and MA2)”). This deposition sequence was repeated 15 times. The UV-Vis spectrum shows a linear growth process, as can be seen by plotting the growth rate at λ max=The absorption intensity at 333 nm observed relative to the number of deposition cycles. The CV measurements recorded under the same conditions as for MA1 do not show the oxidation and reduction peaks that have been attributed to complex 1. The observed starting potential and catalytic current are similar to the values observed in the case of MA1. The Tafel slope of 217 mV / dec and the current density from CPE at a constant applied potential of 1.75 V relative to Ag / AgCl during 7 h are also similar. Bubbles can be clearly observed at the working electrode and the counter electrode. GC analysis of the gas mixture indicated that 896 μmol of H2 (≈448 μmol of O2) were produced after 6.5 h. CPE indicated that for 2.4 cm 2 With an active surface area of 264C, 264C of charge passed, corresponding to a Faradaic efficiency (FE) of 67%. An anodic oxidation process similar to that observed for MA1 was also observed here. These observations are evidence that the effect of complex 1 is limited to electrochromism and indicate that the palladium component catalyzes the water decomposition of both MAs.
[0615] The obvious question is whether palladium nanoparticles are forming that operate as water splitting catalysts. Scanning electron microscopy (SEM) is a technique used to detect small to large particles in metal organic films. The results are an excellent tool for the preparation of palladium (0) nanoparticles. In this method, oxidizing potentials are used, so the formation of metallic particles is not expected. However, it is known that palladium salts can form particles of palladium oxide in water under oxidizing potentials. SEM imaging of the two MAs was performed before and after electrocatalysis for 7 h. These measurements show the presence of a granular, continuous coating after electrocatalysis. After electrocatalysis, the presence of small amounts of particles has been observed. Redox cycling (0 V to 1 V) (×1500) does not change the texture, and due to the use of lower potentials, no such particles were observed ( Fig.88 The EDS spectra indicated the presence of a uniform distribution of the expected elements, however the resolution did not allow verification of the composition of the particles. The CV measurements of the membranes used for the CPE measurements were consistent with the formation of palladium oxide. These measurements also showed that after about 2 h, the iron complex (1) underwent irreversible structural changes that led to a loss of electrochemical reversibility. Regardless of these changes, it is noteworthy that the membranes showed relatively long catalytic stability without significant material leakage into the electrolyte solution and without changes in the surface texture.
[0616] X-ray photoelectron spectroscopy (XPS) was used to investigate the elemental composition and metal oxidation states of the upper 15 nm-20 nm of both MAs before and after 7 h of electrolysis. 3 / 2 ) and 720eV(2p 1 / 2 ) observed that the Fe 2+There are two distinct peaks for the 2p orbital of Pd. The binding energy does not change, and there is no peak indicating the formation of iron oxide. The overall oxidation state of Pd (2+) is also unaffected, but the peak for the 3d orbital increases from 337 eV (3d 5 / 2 ) and 342eV(3d 3 / 2 ) slightly shifted to 338 eV (3d 5 / 2 ) and 343eV(3d 3 / 2 ). These deviations can indicate Cl - With ClO4 - The exchange of Cl, which is present in excess in the electrolyte solution and is consistent with the formation of palladium oxide particles as shown by SEM. - The amount of ClO4 was significantly reduced and - The change in the oxidation state of the palladium center during the reaction may promote this anion exchange. XPS analysis of MA2 showed a similar effect.
[0617] in conclusion
[0618] This embodiment highlights the electrochromic performance of metal organic films in aqueous electrolytes compared to organic electrolytes without sacrificing switching stability and optical properties. These findings can eliminate the use of volatile organics in sol-gel devices and can be a new entry point for the application of non-toxic chemicals in electrochromic and electronic devices based on metal organic films. In addition, the film formed in this embodiment is shown to have orthogonal properties. By applying different potentials, water decomposition occurs under mild (neutral) conditions, indicating that such materials are promising for electrocatalysis. Mechanistically, the anodic oxidation process is consistent with the formation of nanoparticles that have been observed experimentally. The exact structure of these particles is unclear, but it is expected that these particles are palladium oxides formed in water under applied oxidizing conditions. Although supporting evidence for the formation of such nanoparticles has been obtained, if water decomposition occurs only by these particles, there is no experimental proof of this. Another interesting observation is the correlation between the number of catalytic performance and deposited layers, as well as the similarities between different molecular assemblies (MA1 / MA2) as observed from the cyclic voltammogram measurements. For both assemblies, the catalytic performance increases for up to 10 layers and then levels off when increasing the thickness of the assembly. Although several factors may contribute to this effect, it should be noted that these structurally different assemblies have indistinguishable surface textures and roughnesses. Most likely, the molecular assembly-water interface plays a dominant role, as is an established fact for many heterogeneous catalytic systems. To this end, the first study shows that the performance of the disclosed MA is comparable to other MOFs on the surface.
[0619] It should be noted that catalyst ions other than Pd can be used in embodiments of the present invention. In addition, multilayer catalysts of the present invention can be used to solve the catalysis of processes other than water decomposition. In some embodiments, in addition to catalytic ions (such as Pd ions), catalysts of the present invention also include electrochromic entities (for example, Fe ion centers as mentioned above or different metal ions with electrochromic properties). In some embodiments, there is no electrochromic entity, and the multilayer includes ions (such as Pd) providing catalytic activity, is combined with catalytic ions to form multilayer ligands and does not include other electrochromic entities (for example, no electrochromic iron ions).
[0620] Experimental Section
[0621] Materials and methods
[0622] Solvents (AR grade) were purchased from Bio-Lab (Jerusalem), Frutarom (Haifa, Israel) or Mallinckrodt Baker (Phillipsburg, NJ). Lithium perchlorate (LiClO4) and PdCl2(PhCN)2 were purchased from Sigma-Aldrich. Fluorine-doped tin oxide (FTO)-coated glass substrates (2 cm×2 cm, Rs=10Ω / □) were purchased from Xinyan Technology, Ltd. (Hong Kong, China). The FTO-coated glass substrates were cleaned by sonication in ethanol for 10 min, dried under a N2 flow, and then cleaned in a UVOCS cleaning system (Montgomery, Pa) for 20 min. The substrates were then rinsed with tetrahydrofuran (THF), dried under a N2 flow and oven-dried at 130°C for 2 h. A Laurell automatic spin coater model WS-65MZ-8NPPB was used to form molecular assemblies (MAs).
[0623] UV / Vis spectra. UV / vis spectra were recorded on a Cary 100 spectrophotometer. Absorbance (200 nm-800 nm) was measured using Varian's Cary WinUV-Scan application version 3.00 (182), while transmittance was measured using Varian's Cary WinUV-Kinetics application version 3.00 (182). Bare substrates were used to compensate for background absorption.
[0624] X-ray Photoelectron Spectroscopy (XPS). XPS measurements were performed with a Kratos AXIS ULTRA system using a 75 W monochromatic Al Kα X-ray source (hυ=1486.6 eV) and detection pass energies in the range between 20 eV and 80 eV. Curve fitting analysis was based on the application of Shirley or linear background subtraction and Gauss-Lorentz line shape.
[0625] Scanning electron microscopy (SEM) and energy dispersive x-ray spectroscopy (EDS) patterns. The SEM images of [MA│FTO / glass] (1.0 cm×1.0 cm) were recorded using The Zeiss Sigma 500 operated at 5 keV. Images were collected in secondary electron mode and backscattered electron mode using an in-lens detector, respectively. The pore size was 30 microns. The SEM-energy dispersive x-ray spectroscopy (EDS) patterns were performed using an EDS Bruker XFlash / 60mm at an accelerating voltage of 10 kV. The pore size was 60 microns.
[0626] Gas chromatography (GC) analysis. HP 6890 Series GC system; column: SUPELCO 1-2382, 5Ft×1 / 8InS.S.SUPPORT 45 / 60CARBOXENTM 1000, packed column. Inlet: 87°C, detector: TCD 250°C; carrier gas: He; flow rate: 29.1mL / min; oven: 35°C, hold for 2min; 10°C / min to 60°C, hold for 0min; 30°C / min to 200°C.
[0627] Electrochemical characterization. Oxygen evolution reaction (OER) measurements were performed using a CHI760E electrochemical workstation. The following configuration of the electrochemical cell was used: working electrode MA1 or MA2 on FTO / glass, reference electrode: Ag / AgCl, and counter electrode: Pt wire. Lithium perchlorate (LiClO4, 0.1 M) in H2O was used as a supporting electrolyte (pH≈6.9). Cyclic voltammetry (CV) was performed at a scan rate of 0.1 V. The function, η=a+b log j, was used to extract the Tafel slope b(V dec -1 ). The overpotential and current density are given by η(V) and j(A cm -2 ) is presented.
[0628] Formation of molecular assemblies (MA1 and MA2). MAs were formed by using an automatic spin coater equipped with three syringes containing PdCl2(PhCN)2 and complex 1 or ligand L: (Syringe 1) PdCl2(PhCN)2 (4.0 mM) in THF, (Syringe 2) complex 1 (0.6 mM) or ligand L (1.8 mM) in DCM / MeOH (1:1 v / v), and (Syringe 3) acetone for washing. A solution of PdCl2(PhCN)2 was drop cast (0.7-0.8 mL, Syringe 1) onto FTO / glass (2 cm×2 cm), followed by spinning the substrate at 500 rpm (acceleration 250 rpm / s) for 10 s, and then spinning the substrate at 1000 rpm (acceleration 500 rpm / s) for 30 s. Next, the solution of complex 1 or ligand L was drop cast (0.7mL-0.8mL, syringe 2) on the substrate after 80s, and the substrate was rotated as above. Finally, acetone was drop cast (syringe 3) after 80s and rotated at 1000rpm (acceleration 500rpm / s) for 40s. The PdCl2(PhCN)2 / 1 or PdCl2(PhCN)2 / L deposition steps are referred to as single deposition cycles. The deposition cycle was repeated 15 times.
[0629] Initial overpotential calculation
[0630] Onset overpotential = onset potential - thermodynamic potential
[0631] ·Starting potential = 1.22V (vs. Ag / AgCl)
[0632] Thermodynamic potential = E 0 -0.059pH (where E o =1.23V, pH≈6.9)
[0633] Therefore, the initial overpotential is: η = E(Ag / AgCl)-[E 0 -0.059pH]=0.397V
[0634] Transition frequency (TOF) calculation from CV.
[0635] TOF estimated at 1.75 V vs. Ag / AgCl
[0636] TOF = J / (nFC)
[0637] Where, the current density J = 4.27 mA cm -2 , the number of electrons transferred per catalytic site n = 4, the Faraday constant F = 96485 C mol -1 , and C Fe is the estimated number of electrochemically active iron centers. CFe= Q / F=3.5mC cm -2 / 96485mol C -1 =3.6×10 -8 mol cm -2 The ratio of Pd / Fe = 2.5 (from XPS), so the total number of Pd centers (C Pd )=9×10 -8 mol cm -2 Therefore, TOF = 0.12s -1 .
[0638] The turnover frequency (TOF) was calculated after electrolysis.
[0639] TOF was determined at 1.75 V vs. Ag / AgCl after CPE,
[0640] TOF = amount of H2 produced after electrolysis / catalytically active metal sites (C) × time (s) = 0.18 s -1
[0641] The amount of H2 produced after 4.5 h was 0.537 mmol
[0642] Catalytically active metal sites = 18 × 10 -8 mmol(9×10 -8 mol cm -2 ×2cm 2 )
[0643] Time (4.5h) = 16200s
[0644] Calculation of Faradaic efficiency of MA1
[0645] Faradaic efficiency (FE, %) was calculated using a procedure adapted from the literature.
[0646] FE=η(O2) 实验 / η(O2) 理论
[0647] Theoretical value (η(O2) 理论 ) was determined from controlled potential electrolysis (CPE) measurements of MA1 using the following reaction conditions. Electrocatalysis was performed at 1.75 V relative to Ag / AgCl in a solution of 0.1 M LiClO4 (pH≈6.9). The total charge (Q) was 148 C for a period of 4.5 h. The active surface area = 2 cm×1 cm. The number of electrons passing can be derived from: Q / e - =148 / 1.6×10 -19 =92.5×10 19The formation of an O2 molecule requires 4 electrons, so 92.5×10 19 / 4=23.1×10 19 O2 molecules (assuming a 100% yield). 1 mole = 6.023 × 10 23 molecules, therefore, η(O2) 理论 =383 μmol.
[0648] Experimental value η(O2) 实验 It is calculated by quantifying the amount of H2 gas.
[0649] Quantitative gas evolution measurements: To quantify the gases evolved (H2 and O2) over time, bulk electrolysis has been performed at 1.75 V (vs. Ag / AgCl) using a custom designed gas-tight catalytic cell (Figure 93). Prior to electrolysis, the headspace of the cell was purged with argon for 1 h. Before and after electrolysis, samples of the gas mixture in the headspace of the electrolytic cell were directly injected into a GC equipped with a thermal conductivity detector (TCD) (Figure 93- Fig.94 The hydrogen peak area is used for quantification. Based on Faraday's law of electrolysis and GC data, the Faraday efficiency of O2 evolution has been calculated (Figure 93- Fig.94 ).
[0650] η(O2) 实验 Determination of
[0651] For the quantification of H2, use Fig.94 The calibration curve is shown in . 0.1 mL of gas was sampled from the headspace (total volume = 26 mL). Gc analysis indicated 0.05 mL of H2 in 0.1 mL of injected gas, indicating that 13 mL of H2 was formed. One mole of gas occupies a volume of 24.2 L. Therefore, 13 / 24.2 = 537 μmol of H2 and 268.5 μmol of O2 are formed (because O2 = 1 / 2 H2) FE = η(O2) 实验 / η(O2) 理论 =268.5 / 383=70%
[0652] Calculation of Faradaic efficiency of MA2
[0653] From the CPE, it was found that 448 μmol of O2 was formed, and at 1.75 V (vs. Ag / AgCl), 264 C of charge was passed for 6.5 h of electrolysis, corresponding to a FE of 67%. Active substrate area = 2.4 cm 2 .
Claims
1. A capacitor, comprising: Electrolytes; a first electrode comprising a first substrate layer in contact with a first conductive oxide layer, the first conductive oxide layer in contact with an electrochromic film, wherein the electrochromic film is in contact with the electrolyte; and a second electrode comprising a second substrate layer in contact with a second conductive oxide layer, the second conductive oxide layer in contact with a polymer-containing layer, the polymer-containing layer in contact with a carbon-containing layer, wherein the carbon-containing layer is in contact with the electrolyte; The electrochromic film comprises an organic complex coordinated by metal ions.
2. The capacitor according to claim 1, wherein the metal ions are Fe ions.
3. The capacitor of claim 1 wherein the carbon comprises carbon nanotubes. The capacitor of claim 3 , wherein the carbon nanotubes are multi-walled carbon nanotubes.
5. The capacitor of claim 1 wherein the polymer comprises PEDOT and PSS.
6. The capacitor of claim 1, wherein the conductive oxide is selected from the group consisting of indium tin oxide (ITO) and fluorine doped tin oxide (FTO).
7. The capacitor of claim 1 wherein the conductive oxide is attached to silicon oxide.
8. The capacitor of claim 1 wherein the first substrate, the second substrate, or a combination thereof is selected from the group consisting of silicon dioxide and an organic polymer.
9. The capacitor of claim 1 wherein the first substrate, the second substrate, or a combination thereof comprises a material selected from glass, quartz, polyethylene terephthalate, PDMS, or any combination thereof.
10. The capacitor of claim 1, wherein the capacitor is a supercapacitor.
11. The capacitor of claim 1, wherein the capacitor is a hybrid capacitor, and wherein the first electrode is a battery-type electrode and the second electrode is a capacitive electrode. 12 . The capacitor according to claim 1 , wherein the electrochromic film comprising a metal ion coordinated organic complex has a transmittance difference between an oxidized state and a reduced state of 10% and more. 13 . The capacitor according to claim 1 , wherein the electrochromic film comprising a metal ion coordinated organic complex has a transmittance difference between an oxidized state and a reduced state of 64% and more.
14. The capacitor of claim 1 wherein the electrochromic film comprising a metal ion coordinated organic complex is capable of maintaining at least 40% of its maximum contrast ratio after 50 switching cycles between an oxidized state and a reduced state.
15. The capacitor of claim 1 wherein the electrochromic film comprising a metal ion coordinated organic complex is capable of maintaining at least 54% of its maximum contrast ratio after 1000 switching cycles between an oxidized state and a reduced state.
16. A capacitor, comprising: A first electrode, the first electrode comprising: a first substrate comprising a first conductive oxide surface; and an electrochromic film attached to the first conductive oxide surface; A second electrode, the second electrode comprising: a second substrate comprising a second conductive oxide surface; and a layer comprising a capacitive material attached to the second conductive oxide surface; An electrolyte in contact with: the electrochromic film of the first electrode; and The second electrode is a layer of the capacitive material.
17. The capacitor of claim 16, wherein the layer of capacitive material comprises a polymer or carbon or a combination thereof.
18. The capacitor of claim 17 wherein the layer of capacitive material comprises a polymer layer attached to a layer comprising carbon.
19. The capacitor of claim 16, wherein the first conductive oxide and the second conductive oxide each independently include an electrical contact capable of independently connecting the conductive oxide to an external device.
20. The capacitor of claim 1 wherein said metal ion coordinated organic complex comprises a metal ion polypyridyl complex.
21. The capacitor according to claim 1, wherein the electrochromic film containing a metal ion coordinated organic complex comprises from 2 to 80 layers of the metal ion coordinated organic complex, the layers being connected to each other by a metal interconnector.
22. The capacitor of claim 21 , wherein the metal ion in the metal interconnect is at least one metal ion selected from the group consisting of Zn, Os, Ru, Fe, Pt, Pd, Ni, Ir, Rh, Co, Cu, Re, Tc, Mn, V, Nb, Ta, Hf, Zr, Cr, Mo, W, Ti, Sc, Ag, Au, and Y.
23. The capacitor of claim 20, wherein the metal ion coordinated organic complex comprises a polypyridyl complex represented by Formula I: in M is a transition metal selected from Mn, Fe, Co, Ni, Cu, Zn, Ti, C, Cr, Rh or Ir; n is the formal oxidation state of the transition metal, wherein n is 0-6; X is a counterion; m is a number ranging from 0 to 6; R1 to R 18 Each is independently selected from H, halogen, -OH, -N3, -NO2, -CN, -N(R 20 )2.-CON(R 20 2. -COOR 20 、-SR 20 , -SO3H, -CH=CH-pyridyl, -(C1-C 10 )alkyl, -(C2-C 10 )alkenyl, -(C2-C 10 )alkynyl, -(C1-C 10 ) alkoxy, cycloalkyl, heterocycloalkyl, aryl, heteroaryl, wherein the (C1-C 10 )alkyl, (C2-C 10 )alkenyl, (C2-C 10 ) alkynyl, cycloalkyl, heterocycloalkyl, aryl or heteroaryl may be optionally substituted with halogen, -OR 20 、-COR 20 、-COOR 20 、-OCOOR 20 、-OCON(R 20 )2, -(C1-C8)alkylene-COOR 20 、-CN、-N(R 20 )2, -NO2, -SR 20 , -(C1-C8)alkyl, -O-(C1-C8)alkyl, -CON(R 20 )2 or -SO3H substituted; A1 to A6 are each independently 19 A group of formula III or a group of formula IV attached to the ring structure of the complex of general formula I R 19 Each is independently selected from a covalent bond, H2C-CH2, HC=CH, C≡C, N=N, HC=N, N=CH,H2C-NH,HN-CH2-COO-,-CONH-,-CON(OH)-,-NR 20 -,-Si(R 20 )2-, an alkylene group, a phenylene group, a biphenylene group, optionally interrupted by one or more heteroatoms selected from O, S or N, a peptide moiety consisting of 3 to 5 amino acid residues, R x and R y Each is independently selected from H, halogen, -OH, -N3, -NO2, -CN, -N(R 20 )2.-CON(R 20 2. -COOR 20 、-SR 20 , -SO3H, -CH=CH-pyridyl, -(C1-C 10 )alkyl, -(C2-C 10 )alkenyl, -(C2-C 10 )alkynyl, -(C1-C 10 ) alkoxy, cycloalkyl, heterocycloalkyl, aryl, heteroaryl, wherein the (C1-C 10 )alkyl, (C2-C 10 )alkenyl, (C2-C 10 ) alkynyl, cycloalkyl, heterocycloalkyl, aryl or heteroaryl may be optionally substituted with halogen, -OR 20 、-COR 20 、-COOR 20 、-OCOOR 20 、-OCON(R 20 )2, -(C1-C8)alkylene-COOR 20 、-CN、-N(R 20 )2, -NO2, -SR 20 , -(C1-C8)alkyl, -O-(C1-C8)alkyl, -CON(R 20 )2 or -SO3H; and R 20 Each is independently H, (C1-C6) alkyl or aryl.
24. The capacitor of claim 20, wherein the metal ion coordinated organic complex comprises a polypyridyl complex represented by Formula II: in n is the formal oxidation state of Fe, where n is 0-6; X is a counterion; m is a number ranging from 0 to 6; R1 to R 18 Each is independently selected from H, halogen, -OH, -N3, -NO2, -CN, -N(R 20 )2.-CON(R 20 2. -COOR 20 、-SR 20 , -SO3H, -CH=CH-pyridyl, -(C1-C 10 )alkyl, -(C2-C 10 )alkenyl, -(C2-C 10 )alkynyl, -(C1-C 10 ) alkoxy, cycloalkyl, heterocycloalkyl, aryl, heteroaryl, wherein the (C1-C 10 )alkyl, (C2-C 10 )alkenyl, (C2-C 10 ) alkynyl, cycloalkyl, heterocycloalkyl, aryl or heteroaryl may be optionally substituted with halogen, -OR 20 、-COR 20 、-COOR 20 、-OCOOR 20 、-OCON(R 20 )2, -(C1-C8)alkylene-COOR 20 、-CN、-N(R 20 )2, -NO2, -SR 20 , -(C1-C8)alkyl, -O-(C1-C8)alkyl, -CON(R 20 )2 or -SO3H substituted; A1, A3 and A5 are each independently 19 A group of formula III or a group of formula IV connected to the ring structure of the complex of general formula II R 19 Each is independently selected from a covalent bond, H2C-CH2, cis / trans HC=CH, C≡C, N=N, HC=N, N=CH, H2C-NH, HN-CH2-COO-, -CONH-, -CON(OH)-, -NR 20 -,-Si(R 20 )2-, alkylene, phenylene, biphenylene, optionally interrupted by one or more heteroatoms selected from O, S or N, a peptide moiety consisting of 3 to 5 amino acid residues, R x and R y Each is independently selected from H, halogen, -OH, -N3, -NO2, -CN, -N(R 20 )2.-CON(R 20 2. -COOR 20 、-SR 20 , -SO3H, -CH=CH-pyridyl, -(C1-C 10 )alkyl, -(C2-C 10 )alkenyl, -(C2-C 10 )alkynyl, -(C1-C 10 ) alkoxy, cycloalkyl, heterocycloalkyl, aryl, heteroaryl, wherein the (C1-C 10 )alkyl, (C2-C 10 )alkenyl, (C2-C 10 ) alkynyl, cycloalkyl, heterocycloalkyl, aryl or heteroaryl may be optionally substituted with halogen, -OR 20 、-COR 20 、-COOR 20 、-OCOOR 20 、-OCON(R 20 )2, -(C1-C8)alkylene-COOR 20 、-CN、-N(R 20 )2, -NO2, -SR 20 , -(C1-C8)alkyl, -O-(C1-C8)alkyl, -CON(R 20 )2 or -SO3H substituted; B1 to B3 are each independently selected from H, halogen, -OH, -N3, -NO2, -CN, -N(R 20 )2.-CON(R 20 2. -COOR 20 、-SR 20 , -SO3H, -CH=CH-pyridyl, -(C1-C 10 )alkyl, -(C2-C 10 )alkenyl, -(C2-C 10 )alkynyl, -(C1-C 10 ) alkoxy, cycloalkyl, heterocycloalkyl, aryl, heteroaryl, wherein the (C1-C 10 )alkyl, (C2-C 10 )alkenyl, (C2-C 10 ) alkynyl, cycloalkyl, heterocycloalkyl, aryl or heteroaryl may be optionally substituted with halogen, -OR 20 、-COR 20 、-COOR 20 、-OCOOR 20 、-OCON(R 20 )2, -(C1-C8)alkylene-COOR 20 、-CN、-N(R 20 )2, -NO2, -SR 20 , -(C1-C8)alkyl, -O-(C1-C8)alkyl, -CON(R 20 )2 or -SO3H; and R 20 Each is independently H, (C1-C6) alkyl or aryl.
25. The capacitor of claim 20 wherein the metal ion coordinated organic complex comprises a polypyridyl complex represented by one of the following formulae, or a mixture of the following formulae, or a combination of the following formulae and molecules containing different metal centers or ligands: 。 26. The capacitor of claim 20 wherein the polypyridyl complex is a mixture of polypyridyl complexes.
27. A method of using the capacitor of claim 1, the method comprising: independently connecting the first electrode and the second electrode of the capacitor to a power source; charging the capacitor using the power supply; connecting the capacitor to a load; discharging the capacitor through the load; The charging and the discharging are accompanied by a color change of the first electrode.
28. The method of claim 27, wherein the color change is indicative of a charge / discharge level of the capacitor.
29. The method of claim 27, wherein the capacitor is in a colorless state when charged and the capacitor is in a colored state when discharged.
30. The method of claim 29, wherein the colored state is the more stable state of the molecule and the decolorized state requires an applied potential.
31. The method of claim 27, wherein the color change is detected by an optical detector.
Citation Information
Patent Citations
Metal-based TRIS-bipyridyl complexes and uses thereof in electrochromic applications
WO2015075714A1
An electrochromic device
KR102066259B1
Optically variable thin film with electrochemical capacitance property and use thereof
US20140146381A1
Ionically reconfigurable organic photovoltaic and photonic devices with tunable common electrode
US20140150859A1
Sequence dependent assembly to control molecular interface properties for memory devices, solar cells and molecular diodes
WO2014061018A2